Sesamol-loaded PLGA nanoparticles attenuate HFD-induced MASLD by modulating Nrf2/HO-1, mitochondria cascade, and TLR4/NF-κB signaling pathways in rats - Elsayed S.I. Mohammed; Mohamed Shawky El Sayed; Tahani Ahmad Al-Matrafi; Roshmon ‎Thomas Mathew; Mohamed Ashour; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Tissue and Cell, 2027)

Titanium dioxide and gold nanoparticles toxicity in albino rats: Biochemical, anatomical, histopathological, and immunohistochemical studies - Yasmine A. Mansour; Alaa H. Elsayed; Fady Sayed Youssef; Sameh H. Ismail; Gehad Genidy Mohamed; Meray N. Ramsis; Samar Kamel; Basma A. Elkhadrawey; Mujtaba Farooq Rana; Heba H. Mahboub; Aya M. Mekkawy (Tissue and Cell, 2027)

BDNF and GSK-3β signaling in depression: molecular mechanisms underlying neural plasticity dysfunction - Hayder M. Al-kuraishy; Shimaa A Abass; Hitham Alaa Mohammed Mahana; Osama Ashraf Elbanna; Ibrahiym Yasser Shahin; Abdelrahman Ali Radwan; Omar El-sayed MohamedMohamed; AbdAlRhman Mohamad Lotfy Baktoot; Gaber El-Saber Batiha (Molecular Biology Reports, 2026)

Decoding the modulatory role of long non-coding RNAs in embryogenesis: a comprehensive review - Ahmed A. El-Husseiny; Sara M. Sayed; Nada S. Ali; Morkoss M. Fakhry; Rowyda M. Salman; Mohamed A. Haroun; Mona S. Awed (Molecular Biology Reports, 2026)

CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Lactose-decorated, alginate-coated chitosan nanoparticles loaded with Coomassie Brilliant Blue G-250 protect colonic barrier integrity in experimental colitis - Maha M. Amer; Ahmed Y. Kira; Sameh Saber; Abdulaziz A. Alsalloom; Mostafa M. Khodeir; Hala A. Elashry; Rabab S. Hamad; Adel Alhomaidi; Hamad Alsaykhan; Mohammed Alorini; Mohamed R. Abdel-Hamed; Huda Eltayeb; et al. (Tissue and Cell, 2026)

Realized heritability, mode of inheritance, and fitness costs of Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) resistance to chlorantraniliprole - El-Sayed M. S. Mokbel; Nourhan A. El-Said; Eman A. Fouad (Ecotoxicology, 2026)

Comparative Toxicity of PFAS in Nile Tilapia (Oreochromis Niloticus): Oxidative Stress, Nephro-Immunotoxicit, and Histopathological Alterations - Mohamed Hamed; Seham A. Mobarak; Shimaa M. Kteeba; Sally M. Salaah; Christopher J. Martyniuk; Alaa El-Din H. Sayed (Water, Air, & Soil Pollution, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Protective effects of zinc against testicular dysfunction, oxidative stress, and disturbances in biochemical, molecular, and tissue structure induced by hexavalent chromium - Ali Y. Naoom; Ali B. Jebur; Raghda A. El-Sayed; Mohamed M. Abdel-Daim; Fatma M. El-Demerdash (BioMetals, 2026)

Estimation of economic injury levels and action thresholds for the two-spotted spider mite, Tetranychus urticae Koch, on strawberry plants - Eman M. Abdelmaksoud; Shoukry A. El-Refai; Kadry W. Mahmoud; Walaa El-Sayed; Mohamed E. Ragab (Experimental and Applied Acarology, 2026)
Strawberry ( Fragaria × ananassa Duch.) is a high-value global crop, yet its productivity is severely constrained by the two-spotted spider mite, Tetranychus urticae Koch. Developing localized economic thresholds is a cornerstone of sustainable Integrated Pest Management (IPM) to mitigate yield losses and reduce acaricide reliance. This two-season field study (2019–2020) investigated the quantitative relationship between T. urticae population density and strawberry yield in Egypt. Using varying infestation levels established via Chitosan (Top9 0.1%) treatments, linear regression and Chi-square (χ 2 ) analyses were employed to determine four critical economic levels: General Equilibrium Position (GEP), Economic Threshold Level (ETL), Economic Injury Level (EIL), and Economic Damage Level (EDL). Results revealed a highly significant negative correlation between mite density and yield ( r = -0.96*** in 2019; r = -0.97*** in 2020), with an average yield reduction of 1.25% per mite. The estimated EIL and ETL were 4.0 mites/leaf in 2019 and 3.4 mites/leaf in 2020. These findings provide a precise decision-making framework for mite management in Mediterranean strawberry production. The low estimated thresholds suggest that proactive, preventive management strategies are more effective than reactive control to maintain strawberry yield.

Novel production of vinblastine by immobilized cultures of mutant strain of the endophytic Alternaria alternata - El-Sayed R. El-Sayed; Rofaida S. Abdelkader; Heba S. Moustafa; Samah A. Yousef; Mohamed A. Taha; Sahar M. Ouda (World Journal of Microbiology and Biotechnology, 2026)

Preparation and evaluation of a monovalent Foot and Mouth Disease vaccine as a rapid response to the emerging serotype SAT1 in Egypt - Sonia A. Rizk; Hany I. Abu-Elnaga; Hend M. Daoud; Wael Mossad; Ehab El-Sayed Ibrahim; Mohamed A. Gamil; Nermeen G. Shafik; Mohamed S. Abousenna; Samir A. Nassif; Mohamed A. Saad (Veterinary Immunology and Immunopathology, 2026)

Life-stage–resolved responses of maize storage insects to ozone, phosphine, and ECO2Fume and associated effects on grain composition and oxidation - Laila A. Al-Shuraym; Hosny H. Kesba; Wael H. Elmenofy; Sherif M. El-Ganainy; Mustafa Shukry; Samy M. Sayed; Ahmed A.A. Aioub; Ahmed S. Hashem (Journal of Stored Products Research, 2026)

Gamma Radiation–Induced Synthesis of Pectin/Arabic Gum-Based Nanocomposite Hydrogels for Enhanced Water Remediation - Asmaa Sayed; D. M. Aboelkhir; Razan Mohamed; Ayman Amin; Ghada A. Mahmoud (Water, Air, & Soil Pollution, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Berberine attenuates liver damage, hematological, biochemical, and molecular changes induced by cadmium chloride via inflammation, apoptosis, and oxidative stress suppression - Ali B. Jebur; Raghda A. El-Sayed; Mohamed M. Abdel-Daim; Fatma M. El-Demerdash (Tissue and Cell, 2026)

Microalgae-based aquafeeds for penaeid shrimp: progress toward improved growth, immune modulation, and sustainable production - Samia Elbahnaswy; Eman Zahran; Mai A. M. El-Son; Amany M. Shosha; El-sayed H. Eissa; Mohamed AbdElrahman; Mohamed E. Abd El-Hack; Hanan H. Abdelhafeez; Mahmoud G. El Sebaei (Veterinary Research Communications, 2026)

Dietary yeast-derived nucleotides enhance reproductive efficiency, blood metabolic profile, antioxidant status, and immune function in rabbit does - Noura H. Gouda; Sameh A. Abdelnour; Elsayed S. I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Roshmon Thomas Mathew; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; Ehab El-Haroun; Mahmoud S. Abd-Allah (Veterinary Research Communications, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Techno-Economic Analysis of Microalgal Biofuels: Evaluating Cost Competitiveness Through Biotechnology Advancements - Tareq Kareri; Aman Khan; Muhammed K. Alhassan; Sedky H. A. Hassan; Mohammed Jalalah; Fahad M. Almutairi; El-Sayed Salama (International Journal of Environmental Research, 2026)

Therapeutic and research frontiers in fibromyalgia: integrating pathophysiology with innovative drug repurposing - Sheer A. Joodi; Dalia A. Nawwar; Nora O. Abdel Rasheed; Weam W. Ibrahim; Helmy M. Sayed (Inflammopharmacology, 2026)

Immunometabolic reprogramming in multiple sclerosis: from pathogenic amplifier to therapeutic target in neuroinflammation and remyelination - Ghada A. Badawi; Rehab M. El-Sayed; Mohamed N. Fawzy (Inflammopharmacology, 2026)
Multiple sclerosis (MS) has conventionally been considered a prototypical autoimmune disorder. While modern immunotherapies effectively control relapsing conditions, they fail to avert progressive neuroinflammation, neurodegeneration, and remyelination failure. This review offers an evidence-based recontextualization. The pathogenesis of multiple sclerosis is multifactorial, resulting from the interaction of genetic predisposition (especially HLA alleles), environmental factors (particularly Epstein-Barr virus infection), B-cell-mediated autoimmunity, and localized CNS inflammation. In this intricate environment, cellular metabolic dysregulation is a notable factor and potentially adjustable enhancer of disease progression, functioning within the extensive multifactorial pathogenic context, where the bioenergetic programming of immune and neural cells determines inflammatory or protective responses. Proinflammatory Th17 cells and M1 microglia depend on aerobic glycolysis and glutaminolysis regulated by mTOR and HIF-1α, whereas regulatory T cells, M2 microglia, and neurons require fatty acid oxidation and oxidative phosphorylation via AMPK. In multiple sclerosis, glycolysis disrupts metabolic equilibrium, sustaining chronic neuroinflammation and obstructing repair processes. Established multiple sclerosis therapies, dimethyl fumarate and teriflunomide, exhibit direct, previously unrecognized metabolic effects, validating this pathway as therapeutically viable. Emerging strategies intentionally target these vulnerabilities: glutaminase inhibitors to counteract pathogenic Th17 cells, AMPK activators such as metformin to enhance remyelination, mTOR inhibitors to restore immune tolerance, and NAD + precursors to rejuvenate mitochondrial function. Transitioning from broad immunosuppression to specific metabolic reprogramming offers remarkable opportunities for tackling chronic neuroinflammation and correcting remyelination deficits in progressive multiple sclerosis. Immuno-metabolic pharmacology is a promising field; however, its clinical application necessitates stringent validation via meticulously designed trials and dependable biomarkers.

Development of dry and oil-based formulations of Metarhizium anisopliae using carrier materials for effective control of red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Nahdia Perveen; Abu Bakar Muhammad Raza; Muhammad Arshad; Panagiotis Eliopoulos; Samah F. Ibrahim; Mustafa Shukry; Samy Sayed; Hanan M. A. Hamada (BioControl, 2026)

Correction to: Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El‑Hanafy; Eman Hamza; Eslam Habba; Doaa A. El‑Hanafy; Nashwa Eltantawy; Reham A. Al‑Dhelaan; Kholoud H. Radwan; Abeer A. El‑Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Physiological, Biochemical, and Histopathological Alterations in Bufo Regularis Tadpoles Co-Exposed to Polyethylene Nanoplastics and Doxycycline - Alaa El-Din H. Sayed; Fathy M. Elshaer; Esraa A. Anwari (Water, Air, & Soil Pollution, 2026)

Exploring the therapeutic potential of Lupeol isolated from Ochrosia elliptica Labill. leaves in polycystic ovarian syndrome - Essam Abdel-Sattar; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Shimaa R. Emam; Heba Hozyen; Marwa Zakaria; Samar M. Mouneir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Combination of sitagliptin and mangiferin mitigates testicular damage induced by paclitaxel via mediating Sestrin2/Keap1/Nrf2 signaling pathway - Kareman M. El-Beheiry; Nagla A. El-Shitany; Magda El-Sayed El-Sayad; Alaa E. Elsisi (Molecular and Cellular Biochemistry, 2026)

Effect of milling on natural radioactivity of Egyptian zircon sand: an assessment of alpha and beta radiation emissions - Kolthoum I. Othman; Ola Makld; Mahmoud A. Mosleh; M. El-Sayed Ali; S. El-Houte (Environmental Geochemistry and Health, 2026)
This study aims to investigate the effect of milling on the natural radioactivity of Egyptian zircon sand, focusing on the gross alpha (α) and goss beta (β) activity concentrations, with additional evaluation of calcination and sulfuric acid leaching. Zircon samples were milled for different durations, and their gross α and gross β activity concentrations were measured using an ATOMTEX AT1329 sample counter. The measurements showed that both gross α and gross β apparent activity concentrations increased with milling time, reaching maximum values of 3.5 ± 1.4 Bq/g and 7.2 ± 2.2 Bq/g, respectively, in the sample milled for 36 h. These values increased to 7.7 ± 3.1 Bq/g and 14.72 ± 4.4 Bq/g after calcination, while acid leaching resulted in a pronounced decrease in these values to 4.5 ± 1.7 Bq/g for alpha and 9.6 ± 2.9 Bq/g for beta. Milling reduces particle size and increases the escape probability of α and β particles from the sample bulk, while calcination removes the polyamide layer formed during milling, which acts as a barrier to particle detection. These findings highlight the potential radiation hazards associated with zircon sand processing to safeguard occupational health and environmental safety in industries working with this material.

Synergistic effects of Spirulina-loaded chitosan nanoparticles on the growth performance and nutritional profile of intensively cultured Red Tilapia (Oreochromis sp.) - Heba S. El-Sayed; Hussein Oraby; Khaled A. Fadel; Khouloud M. Barakat; Ghada E. Hegazy (Algal Research, 2026)

Integrating remote sensing, geophysical and geochemical approach for targeting intrusion-associated hydrothermal gold deposits: insights from Northeastern Desert in Egypt - Mahmoud Abd El-Rahman Hegab; Yousef M. Youssef; Kareem Hamed Abd El–Wahid; Hanaa A. Megahed; Ahmed A. El-Sheikh; Sayed A. Mohamed; Hafsa M. Atia; Heba El-Bagoury; El Sayed A. Saber (Advances in Space Research, 2026)

Thiazolidinedione-triazole hybrids: design, synthesis, and biological evaluation as dual inhibitors of α-amylase and aldose reductase with antioxidant activity for antidiabetic therapy - Eman E. Nasr; Mohamed R. Elnagar; Nahed Nasser Eid El-Sayed; Marwa I Serag; Mostafa M. Elbadawi; Adel S. El-Azab; Simone Brogi; Hazem A. Ghabbour; Abdelrahman Hamdi; Alaa A.- M. Abdel-Aziz (Molecular Diversity, 2026)

Host–virus miRNA crosstalk in ebola virus disease - Ahmed S. Doghish; Gharieb S. El-Sayyad; Hamdi Bendif; Ahmed I. Abulsoud; Aya Salman; Hend H. Mohamed; Akram N. Salah; Ghadir A. Sayed; Nourhan H. Elshami; Hebatallah Ahmed Mohamed Moustafa; Mohamed Bakr Zaki; Osama A. Mohammed; et al. (Folia Microbiologica, 2026)

Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El-Hanafy; Eman Hamza; Eslam Habba; Doaa A. El-Hanafy; Nashwa Eltantawy; Reham A. Al-Dhelaan; Kholoud H. Radwan; Abeer A. El-Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Enhancing the nutritional value of date palm leaves via solid-state fermentation and its impact with single-cell protein on lambs’ performance - Hany M. Gado; Faisal S. Al Barakeh; Zeinab R. Mohammed; Hend A. Sayed; Abdelfattah Z. M. Salem (Tropical Animal Health and Production, 2026)
The study looked at how solid-state fermentation affects date palm leaves (DPL) and how it influences lamb performance, both with and without single-cell protein. DPL was fermented using three different strains of microbes. Using the Cornell Net Carbohydrates and Protein System, the nutritional value of DPL treatments, including fermented date palm leaves (FDPL) and DPL supplemented with single-cell protein designated as high protein (HP), was assessed under the study for chemical composition. To assess FDPL, eighteen crossbred male lambs, with an average live weight of 25 ± 0.2 kg, were divided into two groups. Whereas the second group got 40% concentrate feed mix (CFM), 50% FDPL, and 10% HP, the first group was fed a meal comprising 40% CFM and 60% FDPL. Compared with unfermented DPL, FDPL increased crude protein by 60% and reduced crude fiber by 28.7%. The calculated total digestible nutrients (TDN) value increased from 38.7 to 46.8% (+ 21.0%). Supplementing FDPL with HP further increased crude protein from 8.0 to 15.8% (+ 97.5%) and increased TDN from 46.8 to 66.7% (+ 42.5%). In the feeding trial, HP supplementation increased crude protein, TDN, and metabolizable energy intake, improved nutrient digestibility, feed conversion ratio, and feed efficiency, increased final body weight and average daily gain. Serum total protein, globulin, urea, and glucose increased, whereas AST and ALT remained within the normal physiological range. Overall, solid-state fermentation improved the feeding value of DPL, and the addition of a protein-rich single-cell protein product to FDPL further enhanced lamb performance without evidence of adverse health effects.

Genetic Diversity Analysis Using Start Codon Targeted (SCoT) and Sequence-Related Amplified Polymorphism (SRAP) Markers and Some Leaf Anatomical Traits in Sixteen Rutaceae Taxa - Mohamed A. Abdein; Samah O. Osman; Amr M. M. Mahmoud; Sahar A. M. Shamseldin; Mai M. Wahba; Sayed Y. Mohamed; Emadeldin A. H. Ahmed; Salwa El-Habashy; Rania A. E. Abdelzaher; Noha A. Sukar; Amany M. Mousa; Amal Ahmed Alyamani; et al. (Plant Molecular Biology Reporter, 2026)

Chemopreventive and therapeutic roles, and mechanistic insights of flavonoids activity during pandemics: A comprehensive review - Hamdoon A. Mohammed; Sayed M. Saleh; Manel Dhahri; Ayman M. Mousa; Riaz A. Khan; Alaaeldin M. Komila; Suliman A. Almahmoud; Lotfi M. Aroua (Phytochemistry Reviews, 2026)

Perindopril and L‑arginine protect against arsenic trioxide–induced neurotoxicity via Keap1/Nrf2/HO‑1 activation and suppression of neuroinflammation and apoptosis - Basel A. Abdel-Wahab; Ahmed M. Abd-Eldayem; Ehab A. M. El-Shoura; Saad Misfer; Ahmed A. N. Ahmed; Eman K. Rashwan; Hend Mostafa Selim; El-sayed Gawesh; Olfat E. Mostafa; Sabrin A. Abdel Wahab; Rania A. Gad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Shifting Cassia javanica Cultivation From Shallow to In-hole Systems Maintains Microbial Activity and Plant Cover in the Urban Landscapes - Mahmoud O. Hassan; Mohamed Al-zharani; Wesal S. Tanko; Bader Z. Albogami; Yehia Hazzazi; Lina M. Alneghery; Fahd A. Nasr; Amany A. H. Abeed; Howida Y. Mohamed; Maha H. Khalaf; Khaled N. M. El-Sayed (Journal of Soil Science and Plant Nutrition, 2026)

The possible effects of folic acid and postbiotic yeast on doxorubicin–induced cardiotoxicity in rats: interactions among the gut microbiota, antioxidants, and NLrp3 activities - Heba M. Galal; Marwa H. Bakr; Dalia A. Elgamal; Nahla M. Elsherbiny; Doaa M. Raafat; Asmaa M. Ismail; Sally A. Sayed (Journal of Molecular Histology, 2026)

Network pharmacology and in vivo experimental analysis for validating the antifibrotic potential of Punica granatum leaves against skin scleroderma: the role of oxidative stress, inflammation and TGF-β1/Snail 1/p-Smad 3 signaling pathway - Sara M. Baraka; Zeinab A. El-Gendy; Eman A. W. El-Abd; Ahmed F. El-Sayed; Enayat A. Omara; Marwa M. Elbatanony (Inflammopharmacology, 2026)

Diverse Fertilizers to Boost the Production of Seedless Grapevines Grown on Sandy Soil - Abdullah Abdelaziz Abdul Radi; Sabry A. Hegab; Mohamed A. M. Abada; Asem M. A. Abdel-Gawad; Hassan M. Al-Sayed (Applied Fruit Science, 2026)

Geospatial Insights into Land Use Dynamics: Remote Sensing and GIS for Agricultural Sustainability in Assiut and Minya, Egypt - R. A. Ali Moursy; A. E. Mohamed AbdelRahman; M. Hassan Al-Sayed; M. Ahmed Ali; A. Moatez El-Sayed (Agricultural Research, 2026)

Biosynthesis of Magnetite Nanoparticles and its Impact on Productivity and Biochemical Components of Chili Pepper Under Saline Conditions - Mansour E. Ramadan; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Ahmed A. El-Sayed (Agricultural Research, 2026)

Modulation of growth, blood physiology, disease resistance, molecular immune-antioxidant gene expression, and tissue integrity in european seabass (Dicentrarchus labrax) fed Moringa oleifera flower-enriched diets - Roshmon Thomas Mathew; Mohamed Ashour; Ehab El-Haroun; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Hailah M. Almohaimeed; Nehal A. Younis; Moaheda E.H. Eissa; El‐Sayed Hemdan Eissa (Frontiers in Marine Science, 2026)
Herbal-based additives are now recognized as effective tools of growth and immunity in aquaculture. Seeking these botanical alternatives is a practical necessity for sustainable farming and chemical reduction. Moringa oleifera flowers (MOF), in particular, offer significant potential due to their established history in treating inflammation and respiratory conditions. However, the potential of these additives to enhance growth, physiological status, and tissue health in European seabass ( Dicentrarchus labrax ) has not yet been evaluated. A 70-day feeding trial was conducted to evaluate the effects of graded dietary levels of M. oleifera flower (MOF) on the growth performance, immune- and antioxidant-related genes, physio-metabolic profile, and redox homeostasis of European seabass and resistance to Vibrio alginolyticus challenge. Fish were allocated to four experimental groups and fed either a basal diet (control, MOF0) or the basal diet supplemented with MOF at concentrations of 1 (MOF1), 2 (MOF2), and 3 (MOF3) g/kg. Dietary MOF supplementation significantly enhanced growth indices and the whole-body proximate composition of D. labrax compared to the control group (P< 0.05). Furthermore, fish fed MOF-enriched diets exhibited significant elevations in hematological parameters, including (hemoglobin, RBCs, MCH, MCHC, and WBC) counts (P< 0.05). Metabolic and antioxidant profiles were similarly improved, characterized by a significant increase in total serum protein and a concomitant reduction in glucose, cholesterol, and hepatic enzyme activities (AST, ALT, and ALP) (P< 0.05). Dietary MOF inclusion mitigated oxidative damage by decreasing MDA levels while simultaneously enhancing the enzymatic antioxidant defense system (SOD, CAT, and GPx) (P< 0.05). These biochemical improvements were supported by molecular data showing a significant upregulation of growth genes ( IGF-I and GH ), pro-inflammatory and complement system genes (IL-1β and C3 ), and antioxidant enzymes ( SOD and GPx ) (P< 0.05). MOF inclusion in the diets of D. labrax supported systemic tissue health by improving the structural integrity of the intestinal mucosa and preventing degenerative changes in the hepatic parenchyma and muscle fibers. These findings underscore the multi-tissue cytoprotective efficacy of MOF in D. labrax . Following the V. alginolyticus challenge, fish in the MOF2 and MOF3 groups exhibited significantly higher survival rates and enhanced pathogen resistance compared to the MOF0 and MOF1 cohorts (P< 0.05). Consequently, our data suggest that a dietary inclusion of 2 g/kg of M. oleifera flowers represents an effective strategy for optimizing growth performance, immunocompetence, and antioxidant capacity in European seabass.

Correction: Geospatial Insights into Land Use Dynamics: Remote Sensing and GIS for Agricultural Sustainability in Assiut and Minya, Egypt - R. A. Ali Moursy; A. E. Mohamed AbdelRahman; M. Hassan Al-Sayed; M. Ahmed Ali; A. Moatez El-Sayed (Agricultural Research, 2026)

Drying kinetics, moisture diffusivity, and quality preservation of mint leaves using an IoT-assisted hybrid solar dryer with air recirculation - El-Sayed Gomaa Khater; Adel Hamed Bahnasawy; M. Alhumedi; Atef Fathy Ahmed; Ali Majrashi; Bassem N. Samra; Ramadan ElGamal; Abdallah Elshawadfy Elwakeel; Amged El-Harairy; Mohamed Hamdy Eid; Aml Abubakr Tantawy; Khaled A. Metwally (Journal of Stored Products Research, 2026)

Comparative analysis of the morphological heterogeneity of smooth muscle cells in two avian species: the muscovy Duck (Cairina moschata) and the Japanese quail (Coturnix japonica): ultrastructural and histochemical study - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Basma Mohamed Kamal; Hesham Ismail; Sherief M. Abdel-Raheem; Mahmoud H. A. Mohamed; Ahmed M. A. Meligy; Soha A. Soliman (Protoplasma, 2026)

Assessment of a Novel Synbitotic of Pomegranate Peels Extract and Multi-Specie Probiotics as an Antibiotics Alternative in Ruminants - Nesrein M. Hashem; Nourhan S. Hosny; Nagwa El-Desoky; Gomaa Abo El Lail; Yosra A. Soltan; Ahmed A. Elolimy; El-Sayed M. Abu-Tor; Sobhy M. A. Sallam (Probiotics and Antimicrobial Proteins, 2026)

Antimicrobial and antibiofilm actions of iridoids: a comprehensive mechanistic review - Ahmed H. Elosaily; Ahmed M. El-Dessouki; Marwa Ali-Tammam; Mona Ismail; Momen Lotfy; Haidy A. Abbas; Mohamed S. Abd El Hafeez; Riham A. El-Shiekh; Dalia El Amir; Ghadir A. Sayed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Olive (Olea europaea) phenolics for the control of psoriasis via targeting SMYD2 and IL-17A protein–protein interaction networks - Md Ashiq Mahmud; Mohamed M. Mohyeldin; Md Towhidul Islam Tarun; Abu Bakar Siddique; Sitanshu S. Singh; Khalid A. El Sayed (Journal of Natural Medicines, 2026)

Macromodeling and experimental investigation of RC frames infilled with clay bricks and autoclaved aerated concrete blocks under cyclic loading - Ahmed M. El-Kholy; Huda Sayed; Ibrahim M. Metwally; Ayman A. Shaheen (Bulletin of Earthquake Engineering, 2026)
This study investigates the cyclic behavior of reinforced concrete (RC) frames infilled with autoclaved aerated concrete (AAC) blocks—a novel and environmentally friendly material—compared to traditional clay masonry infill commonly used in Egypt. In addition, the RC frames were reinforced with an advanced type of reinforcing steel designed to enhance seismic resistance. Three 2/3-scale RC frames were experimentally tested under cyclic lateral loading. Both infill types contributed approximately equally to increasing the lateral strength of the RC frame (around 60% improvement); however, the AAC infill significantly outperformed the brittle clay infill in terms of ductility enhancement. To characterize the response, trilinear and quadlinear backbone curves were developed for the clay and AAC infills, respectively. Alongside the experimental work, numerical macromodeling of the infill panel as multi-strut and single-strut macromodels using SeismoStruct and SAP2000, respectively, was conducted. Additionally, both concentrated and distributed plasticity approaches were employed to model the nonlinear behavior of the RC elements. A suitable constitutive steel model was used to numerically track the experimental hysteresis response of the steel reinforcement. The multi-strut macromodel demonstrated superior accuracy in capturing the hysteresis behavior of the infilled RC frames compared to the single-strut model. The strut width and its post-cracking degradation rate, the shear-to-axial stiffness ratio, and the strain in the infill at peak stress were key parameters influencing the accuracy of the complex multi-strut macromodel in distinguishing between the brittle behavior of clay infill and the ductile response of AAC infill.

New bioactive mono-acyl glycerol ester from the Red Sea marine coral Sclerophytum levi - Basma H. Farouk; Asmaa M. Abdel-Tawab; Mohamed E. Mostafa; Fawzia Z. El-Ablack; El Sayed A. E. Hamed; Seif-Eldin N. Ayyad (Natural Product Research, 2026)

Date seed–and licorice–derived nanoemulsions inhibit clinostomid metacercariae recovered from naturally infected Nile tilapia (Oreochromis niloticus): First report - Olfat A. Mahdy; Mai A. Salem; Fady Sayed Youssef; Mohamed S. Kamel; Reem M. Ramadan (Veterinary Parasitology, 2026)

Prenatal exposure to the fungicide flutolanil induces developmental and hepatic toxicity in pregnant rats and their fetuses: Insights from In Vivo and In Silico studies and the protective role of Chlorella vulgaris - Samah S. Arafa; Mohammed Adel; Osman F. Abdelzaher; Sultan A. Alfawaz; Nermeen M. Nooreldien; Ruaa Yasir Altayeb Mohamed; Asmaa M. Abd El-Azez; Hanaa A. Abd El-Gawwad; Salah M. EL-Sharkawy; Eman Sweed; Shimaa Abdelsattar; Asmaa A. EL-Dahshan; et al. (Reproductive Toxicology, 2026)

Production of environmentally-friendly diesel fuel through designation of polystyrene-based hybrid nanocomposites for efficient photocatalytic desulfurization - Esraa M. El-Fawal; Ahmed M.A. El Naggar; Hussien A. El Sayed; Adel A. El-Zahhar; Majed M. Alghamdi; Fathi S. Soliman (Journal of Environmental Chemical Engineering, 2026)

The impact of Spirulina platensis supplementation on performance and immune response in laying hens - Mohammed Al-Rasheed; Mohamed Shawky El Sayed; Khaled M. A. Ramadan; Eslam S. A. Bendary; Sherief Mohmaed Abdel-Raheem (Veterinary Research Communications, 2026)

Exploring the effect of bronopol exposure length on the suppression of Aeromonas hydrophila infection in nile tilapia (Oreochromis niloticus L.) - Zizy I. Elbialy; Eman M. Moustafa; Amira A. Omar; Abdallah S. Salah; Ahmed Elsheshtawy; Mohammed M. Zayed; Marwa F. Abdel-Kader; Hani Y. Labib; Hossam I. Kadira; Dina B. Barsem; Ahmed E. Elshafey; Sayed M. Aboleila; et al. (Veterinary Research Communications, 2026)

Effect of stinging nettle powder (Urtica dioica) supplementation on productive and physiological performance of laying hens - Magdy Sayed Hassan Hassan; Inas Ibrahim Ismail; Ahmed Mohamed Dief Youssef; Ahmed M. Hussein; Nahla A. Elrazik; Ibrahim Abd El hamed Fathy; EIham Salah Mohamed Ahmed; Waleed Sobhy El Saqa; José del Carmen Rodríguez-Castillo; Mona M. M. Y. Elghandour (Tropical Animal Health and Production, 2026)

Time-domain moment tensor inversion of moderate earthquakes in the northern red sea: Velocity model sensitivity and bootstrap uncertainty quantification - Mohamed A. Taha; Sayed S. R. Moustafa; Mohamed Metwaly; Ahmad M. Faried (Journal of Seismology, 2026)

Phytochemical characterization, bioefficacy, and economic potential of seaweed tannin-based emulsifiable concentrates for cotton pest management - K. Madasamy; K. Sahayaraj; Lamya Ahmed Alkeridis; Lalia A. Al-Shuraym; Hosny H. Kesba; Hanan M. A. Hamada; Samy M. Sayed (Journal of Applied Phycology, 2026)

Ursolic acid, a pentacyclic triterpene from Ochrosia elliptica Labill leaves and its role in the management of polycystic ovary syndrome (PCOS) - Shimaa R. Emam; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Heba F. Hozyen; Marwa Zakaria; Essam A. Abdel-Sattar; Samar M. Mouneir (Inflammopharmacology, 2026)
Ursolic Acid (UA), a naturally occurring pentacyclic triterpene, was isolated from Ochrosia elliptica . Polycystic Ovary Syndrome (PCOS) a prevalent endocrine disorder characterized by hyperandrogenism, insulin resistance, and chronic inflammation. In this study, we investigate the role of UA in alleviating the symptoms of PCOS, focusing on its biochemical, hormonal, and histopathological effects in a rat model. Using adult female Wistar Albino rats, PCOS was induced through letrozole administration. The rats were then treated with UA at two different doses (25 and 50 mg/kg), alongside a control group and a standard ovulation-inducing medication, clomiphene citrate (1 mg/kg). Biochemical analyses showed that PCOS induction significantly increased serum malondialdehyde (MDA) levels by approximately 1.21-fold, while markedly reducing superoxide dismutase (SOD) and catalase (CAT) activities ( p ≤ 0.05) by approximately 0.48-fold, relative to negative control. Treatment with UA (50 mg/kg) dose-dependently restored oxidative balance, reducing MDA (~ 0.82-fold) and elevating SOD (~ 2.39-fold) and CAT (~ 2.11-fold) activities toward PCOS values ( p ≤ 0.05). Hormonally, PCOS rats exhibited elevated luteinizing hormone (LH) and testosterone levels by approximately 1.70-fold, compared to the negative control ( p ≤ 0.05). Both doses of UA significantly lowered LH and testosterone, with the 50 mg/kg dose achieving reductions comparable to clomiphene citrate ( p ≤ 0.05). Histopathological examination showed improved ovarian morphology with reduced cystic follicles and increased corpus lutea in UA-treated groups. Furthermore, UA downregulated key genes involved in steroidogenesis and oxidative stress response, suggesting a multifaceted mechanism of action. The findings highlight UA’s potential as a novel therapeutic option for managing PCOS symptoms, emphasizing the need for further research into its efficacy and safety in clinical applications.

Infection control and wound care innovations in plastic surgery: a multidisciplinary approach - Rasha Abu-Khudir; Ahmed S. Doghish; Reda M. Mansour; Ghadir A. Sayed; Nourhan H. Elshami; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ahmed O. Abdulkader; Sherif S. Abdel Mageed; Osama A. Mohammed; Rabab S. Hamad; Ahmed I. Abulsoud; et al. (Folia Microbiologica, 2026)

Estimation of pesticide residues in certain Gharbeya watercourses, Egypt: Insight into bacterial abundance and Metallothionein Biomarker in snails - Sara S. M. Sayed; Rania M. Abd El- Hamid; Omnia A. Mohamed; Hassnaa A. Saleh (Bulletin of Environmental Contamination and Toxicology, 2026)

Evaluation of sanitation-related pathogenic exposure and epidemiology: bacterial contamination in soil from pit latrines and association with childhood diarrhea - Bolor-Erdene Buyanjargal; Monika Sharma; Sedky H. A. Hassan; Fahad M. Almutairi; El-Sayed Salama (Environmental Monitoring and Assessment, 2026)

Integrating hydrogeochemical analysis and machine learning to assess surface–groundwater interactions in an arid basin (Middle Egypt) - Ahmed A. Abdelhady; Mamdouh S. Morsi; Nouria E.A. Aboshaala; Mahmoud M. Khalil; Hadi M. Elshourbagi; Esam Ismail; Esam El Sayed; Ashraf M.T. Elewa; Emad Youssef; Basma A.A. Balboul (Journal of African Earth Sciences, 2026)

Developmental and neurobehavioural toxicity of per- and polyfluoroalkyl substances in aquatic organisms: mechanistic insights from molecular disruption to behavioural dysfunction - Mohamed Hamed; Mohamed Abbas; A K M Munzurul Hasan; Shimaa M. Kteeba; Hesham Taher; Mohammed Abdel-Wahab; Rashad E.M. Said; Zeinab Bakr; Douglas P. Chivers; Jae-Seong Lee; Alaa El-Din H. Sayed (Aquatic Toxicology, 2026)

Guava leaf (Psidium guajava) byproducts in animal and fish diets: a review of health benefits, immunomodulation, and sustainable applications - Khaled M. Al-Marakby; Islam G. Abdelghani; Ehab El-Haroun; Zeinab Mahasneh; Roshmon Thomas Mathew; Asmaa M. Sheiha; Mohamed F. Abo El-Maati; El-Sayed Hemdan Eissa; Md Altafur Rahman; Sameh A. Abdelnour (Tropical Animal Health and Production, 2026)

Compost-mixed Biochar Improves Saline Soil Properties and Enhances Brassica Oleracea var. Capitata physio-biochemical Responses - Ahmed R. Abd EL-Tawwab; Abdelsattar Abdelkhalik; Ahmed Shaaban; Basma R. Abdel-Moatamed; Khaulood A. Hemida; Ali A.S. Sayed; Mostafa M. Rady; Hani S. Saudy; Mohammed A.H. Gyushi (Journal of Soil Science and Plant Nutrition, 2026)
The present research aimed to correlate changes in saline soil properties and cabbage agro-physiological attributes under compost-biochar co-application. The treatments used prior to cabbage cultivation were soil applications of compost/biochar mixtrure (CMB) at rates of 0 (CMB 0 ), 10 (CMB 10 ), and 20 (CMB 20 ) t ha –1 in a randomized complete block design with three replications. The CMB 20 was the effective practice for reducing dry bulk density, saturated hydraulic conductivity, pH, and electrical conductivity, while improving total porosity, water-holding pores, soil moisture at field capacity, organic matter, cation exchange capacity, and nutrient availability. CMB 20 also improved plant relative water content, membrane stability index, and chlorophyll a and b concentrations. Hydrogen peroxide and malondialdehyde decreased by 13.5% each under CMB 20 treatment. Cabbage plants grown in saline soil produced greater phenolics content (56.0%) with higher superoxide dismutase (17.2%) activity in CMB 20 -treated plots than CMB 0 . Leaf nitrogen, phosphorus, and potassium contents enhanced by 10.1, 28.1, and 18.4%, respectively, compared with CMB 0 . Finally, CMB 20 achieved the maximal improvements in leaf number plant − 1 (41.8%), leaf area plant − 1 (216.2%), above-ground biomass (174.5%), head circumference (38.2%) and marketable yield (101.6%) of cabbage. It could be concluded that amending saline soil with CMB is regarded as a promising treatment for alleviating the salinity hazards on cabbage via modulating soil properties and physiological responses. Hence, CMB application, 20 t ha –1 , can be recommended as an agronomic practice for cabbage production to obtain high yield and quality.

Energy and environmental impacts of wheat production: a comparative study of diesel and photovoltaic irrigation systems - Mahmoud A. Abdelhamid; Hassan A. A. Sayed; Tarek Kh. Abdelkader; Fatma M. Shaaban; Ashrf A. Anwer; Mohamed A. Refai (Environment, Development and Sustainability, 2026)
Increasing energy demand and environmental concerns have led to interest in renewable energy for agricultural irrigation to promote sustainable agriculture. Therefore, this research aims to assess and compare the environmental impacts and energy of wheat production in Egypt under diesel-driven (Sc-I) and solar PV-driven (Sc-II) irrigation systems. The data was collected from 181 wheat farms during the 2022–2023 season. The environmental assessment was conducted using a life cycle methodology from cradle to farm gate, and one kg of harvested wheat grains was used as the functional unit. The results showed that total energy inputs reached 108,506.97 MJ ha − 1 for Sc-I and 38,480.04 MJ ha − 1 for Sc-II, whereas the corresponding energy outputs were 153,735.55 and 144,192.30 MJ ha − 1 , respectively. Among the energy sources used for Sc-I, fuel for the irrigation system accounted for 63.2%, followed by fertilizer (17.3%). On the other hand, total fertilizer has the largest share in Sc-II (44.7%), followed by water (24%). Moreover, Sc-II led to a 64.5% reduction in total energy input. The global warming potential is estimated at 1.09 kg CO₂-eq kg − 1 for Sc-I and 0.19 kg CO₂-eq kg − 1 for Sc-II. Sc-II resulted in lower impacts across most environmental categories; however, slight increases were observed in abiotic depletion and freshwater aquatic ecotoxicity compared with Sc-I. While for agricultural operations, Sc-II led to a reduction in all environmental impact categories. Furthermore, solar PV-powered irrigation systems can substantially reduce energy consumption and emissions, providing a practical pathway towards sustainable agricultural production.

Chemical composition and biological activities of nine essential oils obtained from Algerian plants - Chaima Guendouz; Hadjira Guenane; Boulanouar Bakchiche; Roberta Ascrizzi; Guido Flamini; Sanaa K. Bardaweel; Ahmed M. Sayed; Mosad A. Ghareeb (Natural Product Research, 2026)

Melatonin Mitigates Central Sensitization and Nociplastic Pain in Spinal Cord and Dorsal Root Ganglia of FM Rat Model: Modulation of SIRT1/PGC-1α/MAPK/NF-κB Signaling - Jehad Osama; Amira A. El-Gazar; Ghada M. Ragab; Nesrine S. EL-Sayed; Ahmed S. Kamel (Journal of Neuroimmune Pharmacology, 2026)
Fibromyalgia (FM) is a central sensitization syndrome characterized by neuroinflammation and synaptic hyperexcitability, which amplifies pain signals in the spinal cord (SC) and dorsal root ganglia (DRG). Melatonin (MEL) has demonstrated analgesic and antinociceptive properties in experimental models, supporting its clinical application in various pathological conditions. This study aimed to elucidate the impact of Melatonin on neuroinflammation and glutamatergic dysregulation in the spinal cord and DRG using a Reserpine-induced fibromyalgia model (RIFM). RIFM was induced in female rats by administering Reserpine (1 mg/kg/day, s.c.) for three consecutive days. Melatonin (10 mg/kg, orally) was administered for three days following the peak of pain on day 7. Melatonin significantly ameliorated stimulus-evoked pain in thermal and mechanical tests, with a resolution of spontaneous pain noted by the rat grimace scale. Moreover, motor activity in the open field task and depressive behavior in the tail suspension test (TST) were alleviated following Melatonin administration. Fibromyalgia pain was associated with enhanced glutamatergic transmission, as shown by immunohistochemical assessment of synaptophysin and PSD95 in the DRG along with VGLUT, PSD95, NMDA, NMDA receptor 2B, and AMPA in the spinal cord. Reserpine-induced disturbances in mitochondrial biogenesis markers, SIRT1 and PGC-1α, were followed by an upsurge of TNF-α, NFkB, and P38-MAPK. This neuroinflammatory milieu was marked by elevated ionized calcium-binding adaptor molecule-1 (Iba-1) in activated microglia within the spinal cord. These pathological findings were notably mitigated by Melatonin, as reflected by increased expressions of spinal MT1 and MT2 receptors. In conclusion, Melatonin exhibited antinociceptive and anti-inflammatory effects by modulating glutamate neurotransmission, mitochondrial dysfunction, and microglial activation, thereby alleviating nociplastic pain in the experimental RIFM. Graphical Abstract The potential role of Melatonin in modulating Reserpine-induced fibromyalgia in rats through MT1R and MT2R receptors

Ultrasonic irradiation for ZnO NPs Synthesis and their hepatoprotective effect against acetaminophen induced hepatic toxicity in albino rats: Biochemical, physiological, and histopathological assessments - Yasmine A. Mansour; Fady Sayed Youssef; Shaymaa Hussein; Hanan F. AbdEl_Halim; Sameh H. Ismail; Gehad G. Mohamed; Abdelfattah M. Abdelfattah; Rasha M.M. Ezz-Eldin; Heba H. Mahboub; Sherin Ibrahim (Tissue and Cell, 2026)

Bi2MoO6/Bi2Fe4O9@FeCuMOF heterojunction for dual-routes of hydrogen production via underground chemistry and photocatalysis - Esraa M. El-Fawal; Ahmed M.A. El Naggar; Hoda A. Mohammed; Hussien A. El Sayed (Fuel, 2026)

Molecular docking and pharmacokinetics of Roweothuria polii compounds with in vivo anti-Eimeria papillata activity - Felwa A. Thagfan; Mohamed A. Dkhil; Rania G. Taha; Youssef A. El-Sayed; Seifeldin Elabed; Rewaida Abdel-Gaber; Shaimaa M. Kasem (Veterinary Research Communications, 2026)

Optimization of Beet Thick Juice Storage: Impact of Storage Conditions on the Rheological Behavior - Marwa Abdelhak; El-Sayed A. Abdel-Rahman; Adel A. Abdellah; Mohamed M. Abd El-Wahab; Mahmoud N. Abdelmoez (Sugar Tech, 2026)
Establishing a manufacturing period for concentrated beet juice is a promising strategy to increase the productivity of white sugar and address climatic variability. Key parameters including temperature and stabilization treatments are crucial to optimizing the storage process at a reasonable cost. To this end, a pilot-scale plant was built with 12 tanks, three levels of storage temperatures (15, 25, and 35 °C), and three disinfection treatments. A rheological evaluation, during six months of storage, was investigated in relation to physiochemical and microbiological changes. The rheological behavior fits well with the power law model at different test temperatures of 25, 55 and 85 °C. The data demonstrated that thick juice is non-Newtonian fluid, displaying dilatant trend (1.0 < flow index ( n ) < 1.15) at low temperature of 25 $$^°$$ ∘ C and pseudoplastic (0.7 < n < 0.99) at higher temperatures of 55 and 85 $$^°$$ ∘ C. The consistency coefficient showed a temperature-dependent decline, with activation energy (E a ) values ranging from 17.18 to 29.57 kJ/mol. At a constant shear rate of 50 s −1 , apparent viscosity remained stable before and after storage across most treatments, except for a significant decrease observed in the untreated sample at 35 °C due to microbial deterioration. The findings highlight the off-season potential for sugar production and demonstrate that under optimal storage conditions, thick juice can be preserved in hot climates for a prolonged duration without degradation or significant impact on rheological behavior.

Agricultural Yield Forecasting Using LLM-Informed Preprocessing and Neural ODE Models Optimized via the Football Optimization Algorithm - Mai Alduailij; Sayed Elkenawy; Amel Ali Alhussan; Ebrahim A. Mattar; Amal H. Alharbi; Doaa Sami Khafaga; Safaa Zaman; Marwa M. Eid (Potato Research, 2026)

Hybrid Metaheuristic Feature Selection with Binary Puma Optimizer–Stochastic Fractal Search for Robust Potato Price Prediction - Sayed Elkenawy; Amel Ali Alhussan; Khaled Sh. Gaber; Ebrahim A. Mattar; Marwa M. Eid; Safaa Zaman; Mohamed Saber (Potato Research, 2026)

Potato Irrigation Suitability Assessment via Ninja Optimization Algorithm-Tuned RegNet on Physicochemical Quality Data - Sayed Elkenawy; Ebrahim A. Mattar; Amel Ali Alhussan; Mahmoud Shabrawy; Marwa M. Eid; Mohamed E. Ghoneim (Potato Research, 2026)

A self-organized fuzzy neural model for the pressurizer system in nuclear power plants - Elsayed H. Ali; Amal A. Sheta; Sayed M. El-Araby; Mohammed I. Mahmoud; Tarek A. Mahmoud (Annals of Nuclear Energy, 2026)

Remote sensing and geological characterization of the polydeformed Atud Basin and surrounding rocks, Eastern Desert, Egypt - Sayed M. Sayed; Safinaz A.A. Mahmoud; Reda Abdu Yousef El-Qassas; Amin Esmail Khalil; Yahia A. El Kazzaz (Journal of African Earth Sciences, 2026)

Oil sludge from an environmentally hazardous pollutant to an efficient source for energy production via thermal/ catalytic pyrolysis routes - Mohamed N.A. Mahmoud; Esraa M. El-Fawal; Ahmed M.A. El Naggar; Asmaa I. Zahran; Hussien A. El Sayed; Islam M. El-Sewify; Bassem H. Heakal; Mostafa M.H. Khalil (Fuel, 2026)

Metabolomic and biofunctional insights into lemon-ginger mixture protection against heated oil hepatotoxicity - Nehal S. Ramadan; Ahmed Zayed; Magdy M. El-Sayed; Tarik A. Mohamed; Rasha S. Mohamed; Karem Fouda; Mohamed A. Farag (Food Research International, 2026)

Amelioration of intestinal ischemia reperfusion injury by diacerein via regulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin pathways in juvenile rats - Marwa Monier Mahmoud Refaie; Nada Amgad Mohamed Abdel Majeed; Sayed Shehata; Asmaa A. Muhammed; Salma M. Hassan; Hoda S. Sherkawy; Fatma F. Ali; Mohamed Rabie Saad; Mousa Mohsen; Shereen Mohammed Mohammed Elsaghir; Enas Fathy; Olivia N. Beshay (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Intestinal ischemia reperfusion (II/R) is an abdominal critical case especially in neonates and during childhood affecting not only the intestinal tissue but also it could damage other remote organs including cardiac tissue even following surgical intervention. Immune homeostasis during II/R has a major role in controlling its progression. Thus, finding additive medical treatment besides the surgical one becomes an urgent need to keep the tissue. So that, we aimed to evaluate the possible ameliorative effect of diacerein (DIA) on II/R-induced injury in juvenile rats. Forty juvenile rats of Wistar albino species were randomly allocated into four different groups: sham group, DIA given group, II/R group via clamping superior mesenteric artery, DIA-treated group (50 mg/kg) with induction of II/R. Data of current model revealed a significant elevation of the measured cardiac enzymes, cleaved caspase-3, and nuclear factor kappa β (NF-κB) in the untreated ischemic group with disturbed oxidative stress parameters, accompanied with dysregulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin signaling cascades. Fortunately, upon co-administration of DIA, there is a significant decrease of cardiac enzymes, cleaved caspase-3, and NF-κB with normalization of oxidative stress parameters and regulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin pathways confirmed by marked mitigation of the histopathological changes. This effect of DIA is greatly attributed to its pharmacological properties including IL-1β antagonist effect, anti-oxidant, anti-apoptotic, and anti-inflammatory properties. Thus, DIA could be considered as an adjuvant future medical therapy for those cases of II/R. Graphical abstract

Molecular mechanisms underlying cyclophosphamide-induced ovarian injury and protective strategies - Ehab E. Sharata; Taha Bakry; Habiba Gamal Atta; Habiba Atef Mohammed; Nazema Shaker Diab; Rofaida Ashraf Atef; Roaa Sayed Hosney; Mahmoud Mohamed Omar; Ramadan A. M. Hemeida (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Cyclophosphamide (CP) is an anti-cancer medication that also treats chronic inflammatory illnesses caused by the immune system. Although CP is widely used, it can occasionally have limited therapeutic efficacy due to its significant combined toxicities. Ovarian damage caused by CP is a major problem for patients, and premature ovarian failure (POF) is a serious side effect of CP that commonly affects female patients. Mechanistic investigations have implicated oxidative stress, inflammatory responses, and apoptosis as critical components in the etiology of CP-induced POF, although the exact process by which this ovarian toxicity occurs remains unclear. After CP causes ovarian cells to generate proinflammatory cytokines, including interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B (NF-κB) is activated. The activation of the NLRP3 inflammasome is the subsequent stage. In addition, Nrf2/HO-1 has been identified as an important signaling pathway that mitigates oxidative stress in CP-induced POF due to its anti-inflammatory and antioxidative characteristics. Moreover, several recent studies highlighted the role of α-klotho deficiency in ovarian aging. Quercetin, resveratrol, berberine, curcumin, irbesartan, mirtazapine, sildenafil, atorvastatin, donepezil, cilostazol, moxibustion, LCZ696, buspirone, levomilnacipran, melatonin, diosmin, and azilsartan are some of the agents that may protect against ovarian injury caused by CP, as shown in Graphical abstract. Our goal in writing this study is to provide a concise overview of the possible redox molecular pathways that cause ovarian harm in CP and how to potentially ameliorate them. Finally, investigation into these molecular pathways may pave the way for early ovarian damage relief and for the development of different agent strategies to alleviate CP-mediated POF. Graphical Abstract

Tranexamic acid for spontaneous intracerebral hemorrhage: hematoma control without clinical benefits? A meta-analysis of RCTs - Mahmoud M. Elhady; Eslam Mohammed Rabea; Samah Bahy Mohammed Ebaed; Manar Adel; Moustafa Z. Elattar; Mahmoud Eleisawy; Ahmed A. Lashin; Ahmed A. Elfeky; Mohamed Hesham Gamal; Mohamed Sayed Zaazouee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Spontaneous intracerebral hemorrhage (sICH) is a serious form of stroke associated with high mortality and poor functional outcomes. Hematoma expansion critically affects prognosis, necessitating early intervention. Tranexamic acid (TXA), an antifibrinolytic, has an uncertain role in sICH. This meta-analysis synthesizes evidence from randomized controlled trials (RCTs) to evaluate the efficacy and safety of TXA in sICH. Comprehensive searches of PubMed, Scopus, Web of Science, and Cochrane Library identified RCTs comparing intravenous TXA to placebo in sICH, focusing on hematoma expansion. Data on functional outcomes, mortality, thromboembolic events, and quality of life were extracted. Cochrane RoB2 assessed the quality of studies. RevMan 5.4 was used for data analysis, employing fixed-effects models. Subgroup analyses were conducted based on time windows and patient subgroups. Eight RCTs (2974 patients) were included. TXA significantly reduced 24-h hematoma volume (MD = − 1.17 mL, 95% CI = − 1.97 to − 0.36), particularly when administered within 8 h (MD = − 1.71 mL, 95% CI = − 2.68 to − 0.74). However, odds of expansion, functional outcomes, 90-day mortality, thromboembolic events, and quality of life were similar between groups. Another subgroup analysis based on study populations revealed a significant effect of TXA on hematoma volume in studies involving sICH without a specific subgroup classification. However, no significant effect was observed in other subgroups, including sICH with spot sign, hypertensive ICH, and NOAC-associated ICH. TXA has been shown to reduce hematoma expansion in sICH, particularly when administered within 8 h of symptom onset, without a corresponding increase in thromboembolic events. However, this benefit has not translated into significant improvements in functional outcomes, mortality, or quality of life. As such, current evidence does not support the routine use of TXA in sICH, and further high-quality research is warranted.

Cerium oxide nanoparticles attenuate hepatic failure via blocking TGF-β/Smads and upregulating Nrf2/HO-1 signaling pathways in liver fibrosis rat model - Noha A. Mowaad; Sara M. Baraka; Saber Ibrahim; Doaa A. Mansour; Reda M. S. Korany; Ahmed F. El-Sayed; Arwa A. Hassan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
T his article is aimed at assessing the anti-fibrotic action of plant-based fabricated cerium oxide nanoparticles (CeO 2 NPs). The Carissa carandas aerial parts methanolic extract was utilized to prepare CeO 2 NPs, where the dispersal of particle size distribution and zeta potential value was 61.9 nm and − 18.94 mV, respectively, verifying the successful synthesis of CeO 2 NPs. In rats, CeO 2 NPs were intravenously injected at doses of 0.1 and 0.5 mg/kg twice a week for a month, in parallel with thioacetamide (TAA, 200 mg/kg, i.p). Our findings revealed that CeO 2 NPs alleviated the alteration in serum GPT, GOT, ALP, total bilirubin, albumin, and total protein levels induced by TAA. Additionally, the hepatic oxidative insult due to TAA was inferred by elevation in malondialdehyde and reduction of glutathione content, which in combination with downregulation of SIRT1, Nrf2, and HO-1 in hepatic tissues was improved by CeO 2 NPs. A clear repression in hepatic fibrosis was observed in CeO 2 NP-treated groups as demonstrated by significant downregulation in TGF-β1 and p-Smad 2 and 3 proteins and COL1A1, MMP-2, and α-SMA expressions in hepatic tissues. The histopathological outcomes exhibited a considerable accumulation of collagen fibers in hepatocytes in TAA-challenged rats, which was ameliorated by CeO 2 NPs. Also, CeO 2 NPs dampened the death of hepatic cells via blocking caspase 3 activation as indicated by the immunohistochemical results. The in silico investigations documented the powerful binding affinities of TGF-β1, COL1A1, MMP-2, p-Smad2, p-Smad3, SIRT1, Nrf2, and HO-1 proteins with CeO 2 NPs. In conclusion, this study emphasized the efficacy of CeO 2 NPs as a potent anti-fibrotic agent through upregulating SIRT1/Nrf2/HO-1 and downregulating TGF-β1/Smads pathways.

miRNAs in Amyotrophic Lateral Sclerosis: Tiny Molecules, Tremendous Impact - Sherif S. Abdel Mageed; Ghadir A. Sayed; Ahmed Mahdy; Walaa A. El-Dakroury; Ahmed O. Abdulkader; Hebatallah Ahmed Mohamed Moustafa; Reda M. Mansour; Osama A. Mohammed; Mohammed S. Elballal; Ahmed E. Elesawy; Ahmed S. Doghish (Molecular Neurobiology, 2026)

Hydrogen sulphide modifies the therapeutic potential of bone marrow mesenchymal stem cells in an adjuvant-induced polyarthritis rat model through the mitigation of angiogenesis, ectopic lymphoid tissue formation, and osteoclastogenesis - Sara M. El-Sayed; Mohamed R. Mohamed; Mohamed M. Naguib; Hadeer A. Aglan; Hanaa H. Ahmed (Inflammopharmacology, 2026)
Among the chronic and progressive autoimmune disorders that primarily affect joints in the hands, wrists, and knees, rheumatoid arthritis (RA) is a highly prevalent one. A significant number of patients develop severe adverse events, display weak responses, or cannot afford long-term use of the current RA medications, requiring more efficient and safer curative alternatives. increasing evidence recommends the application of mesenchymal stem cells (MSCs)-based therapy for mitigating chronic inflammation and boosting tissue renewal in intractable disorders. Moreover, sodium hydrosulphide (NaHS) has recently been found to have anti-inflammatory effects. Therefore, this study compared the therapeutic outcomes of four approaches; bone marrow-derived mesenchymal stem cells (BM-MSCs), their conditioned media (CM), BM-MSCs pre-conditioned with NaHS, and their conditioned media in a rat model of adjuvant-induced polyarthritis. The process involved the isolation of MSCs from rat bone marrow, propagation, and characterization of the isolated cells. polyarthritis was induced in male Wistar rats via intradermal injection of type II collagen on day 0 and day 21. Affected rats were treated with naproxen, BM-MSCs, BM-MSCs-CM, NaHS, BM-MSCs preconditioned with NaHS, or BM-MSCs preconditioned with NaHS-CM. The results indicated that the administered cells homed to the bone marrow and bone trabeculae of the knee joint tissue of the afflicted rats. The proposed treatments brought about significant down-regulation of peptidyl arginine deiminase 2 (PAD2) and chemokine ligand 13 (CXCL13) genes as well as angiopoietin-1 (Ang-1) protein expression, along with substantial upregulation of the galectin-1 (GAL-1) gene and osteoprotegerin (OPG) protein expression. Compared with BM-MSCs therapy, the treatment with BM-MSCs preconditioned with NaHS and their CM exhibited superior effect, with values close to those of the controls. In addition, treatment with the CM of BM-MSCs offered a lesser effect compared to BM-MSCs therapy alone. In conclusion, NaHS has the potential to improve the therapeutic capability of BM-MSCs for RA in rats by enhancing their anti-inflammatory, immunomodulatory, and regenerative capacity.

Chitosan-based Zeolitic Imidazolate Framework-8 for water remediation: kinetic and isotherm insights into the removal of organic and inorganic pollutants - Alaa I. E. Abdelaziz; Reem Kamal Farag; Abdulraheim M. A. Hasan; Ahmed A. Farag; Mohamed Keshawy; Ragaa E. El-Azabawy; Manar El-Sayed Abdel-Raouf (Environmental Science and Pollution Research, 2025)

Tracing contamination status and comprehensive risk assessment of potentially toxic elements in seawater impacted by shipping activities: The Red Sea, Egypt - Alaa M. Younis; Said Hanafy; Abdel-Aziz Y. El-Sayed; Mahmoud A. Ghandour; Eman M. Elkady; Naglaa F. Soliman (Marine Pollution Bulletin, 2025)

Neuroprotective efficacy of royal jelly and propolis against cadmium-induced dysregulation of neurogenesis and neurotransmitters in the brain of rats: Molecular mechanisms and ultrastructure investigations - Norhan S. El-Sayed; Eman M. Omar; Esraa S. Habiba; Sahar A. Harby; Amany Attaallah; Maria Augustyniak; Abeer El Wakil; Lamia M. El-Samad; Mohamed A. Hassan (Journal of Trace Elements in Medicine and Biology, 2025)

Comparative analysis of nutritional, rheological, and sensory attributes of biscuits enriched with white and black chia seed powders: Evaluation under Egyptian cultivation conditions - Clara R. Azzam; Sayed M. Mostafa; Mokhtar S. Rizk; Ramadan A. Arafa; Emad A. Salem; Ahmed M.S. Hussein (Innovative Food Science & Emerging Technologies, 2025)

Guar gum-based systems formulated with encapsulated propolis extract for minimally processed fruits and confectionery packaging - Rowaida K. Khalil; Nadeen B. El-Sayed; Rawan H. El-sayed; Rahma M. Sallam; Asmaa Y. Abdelnabi; Nouran S. Soliman; Rawan A. Ibrahim; Menna-tallah A. Ibrahim; Muhammed R. Sharaby; Dalia S. Abdelrahim (Food Hydrocolloids, 2025)

Triazole-functionalized compounds as promising antifungal agents: Synthesis, biological evaluation, and mechanistic insights - Basmah Almohaywi; Hany E. A. Ahmed; Ahmed Kotb; Abdullah Ashraf; Moaz Alsedawy; EL-Sayed E. Habib; Ahmed K. B. Aljohani; Khalid A. Alosaimi; Aryam S. Alharbi; Samar F. Miski; Mohamed M. Elsebaei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

MALAT1 SNP (rs619586) shows a protective effect against type 1 diabetes mellitus, while the miR-146a SNP (rs57095329) is linked to an increased risk of developing the disease - Soha M. Hamdy; Heba A. Ibrahim; Omayma O. Abdelaleem; Olfat G. Shaker; Sherin K. Hussein; Sara M. A. K. Massoud; Ola N. Sayed (Molecular Biology Reports, 2025)

Efficient CO2 Assimilation and Harmonization of Defensive Mechanisms Via Whey Protein or Ascorbic Acid Plus Humic Acid Applications to Enhance Fruit Yield and Quality in Salt-Stressed “Cara Cara” Orange Trees - Ahmed M. Fikry; M. S. Aboryia; A. Osman; A. M. Abo-Ogiala; Hany G. Abd El-Gawad; Hani S. Saudy; El-Sayed M. Desoky (Journal of Soil Science and Plant Nutrition, 2025)
The variety of navel orange known as “Cara Cara” trees are greatly affected by soil salinity, which adversely influences yield and quality. Therefore, adopting the use of safe and inexpensive materials is crucial in this case. Herein, bio-stimulants (whey protein hydrolysates, and humic acid), and ascorbic acid could be utilized to promote plant growth in both normal and salt-stress environments. Two field trials were implemented to investigate the response of navel orange trees to whey proteins hydrolyzed (WPH) with pepsin (PEH at a concentration of 1000 mg L −1 ) and papain (PAH at a concentration of 1000 mg L −1 ), or ascorbic acid (ASA) at a concentration of 1000 mg L −1 , and/or humic acid (HA) (applied to the soil at a concentration of 1000 mg L −1 ). The changes in fruit yield, fruit quality, physio-biochemical attributes, and antioxidant defense systems under salinity stress (with an electrical conductivity of 5.14 dS m −1 ) were estimated. All treatments involving HA with WPH or ASA significantly improved various fruit yield and quality traits, physiological and photosynthetic performance attributes as well as enzymatic and non-enzymatic antioxidants, comparing to the check treatment in both seasons. In this context, PEH + HA treatment was the efficient practice for increasing fruit yield per tree by 80.3 and 82.7%, total acidity by 162.3 and 250.0%, vitamin C by 10.7 and 13.6%, total soluble solids by 12.5 and 8.3%, net photosynthetic rate by 82.3 and 80.9%, relative water content by 27.9 and 28.0%, and membrane stability index by 44.2 and 43.0%, while decreasing electrolyte leakage by 56.0 and 57.0%, and malondialdehyde by 57.8 and 58.3% during two seasons, respectively, as compared to check treatment. Also, PEH + HA treatment showed the highest potentiality for ameliorating the defensive mechanism indices elevating catalase by 17.3 and 17.2%, super oxide dismutase by 122.2 and 122.1%, and glutathione by 97.9 and 99.0%, while suppressing hydrogen peroxide by 45.7 and 45.6% and superoxide radical by 47.9 and 49.3%, during the two seasons, respectively, as compared to the check treatment. Furthermore, it should be mentioned that the values of most fruit yield and quality traits, photosynthetic efficiency, physiological performance and ant-oxidative indices obtained with application of PAH + HA and ASA + HA treatments were as similar as those of gained by PEH + HA. Therefore, the outcomes of the current study indicated that using integrated PEH + HA, PAH + HA and ASA + HA treatments are considered helpful practices for growing citrus plants and maintaining yield and quality in saline soil circumstances.

Facies evolution of the Eocene–Oligocene succession in Northern Bahariya Depression (Western Desert, Egypt): depositional controls, palaeoenvironments, and palaeobiogeography - Nada A. Ayoub; Sayed M. Ahmed; Rifaat A. Osman; Mervat S. Hassan; Emad S. Sallam (Journal of Sedimentary Environments, 2025)

Sustainable integrated oil-palm livestock practice to enhance soil organic matter and carbon sequestration potential - Y. Umar; K. Sayed; M. I. Syakir; T. K. Al-Saedi; B. Azhar; K. A. Tohiran; F. Nobilly (International Journal of Environmental Science and Technology, 2025)

Innovative perspectives on glioblastoma: the emerging role of long non-coding RNAs - Ahmed S. Doghish; Abdelhamid Mahmoud; Mai A. Abd-Elmawla; Mohamed Bakr Zaki; Nora M. Aborehab; Abdulrahman Hatawsh; Abdullah F. Radwan; Ghadir A. Sayed; Rewan Moussa; Mustafa Ahmed Abdel-Reheim; Osama A. Mohammed; Hanan Elimam (Functional & Integrative Genomics, 2025)

From fatty liver to fibrosis: the impact of miRNAs on NAFLD and NASH - Reda M. Mansour; Sherif S. Abdel Mageed; Ahmed I. Abulsoud; Ghadir A Sayed; Radwa H. Lutfy; Farah A. Awad; Mohamed M. Sadek; Abanoub A. S. Shaker; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Hanan Elimam; Ahmed S. Doghish (Functional & Integrative Genomics, 2025)

Role of long non-coding RNAs and natural products in prostate cancer: insights into key signaling pathways - Ahmed S. Doghish; Sherif S. Abdel Mageed; Mohamed Bakr Zaki; Mai A. Abd-Elmawla; Ghadir A. Sayed; Abdulrahman Hatawsh; Nora M. Aborehab; Rewan Moussa; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Hanan Elimam (Functional & Integrative Genomics, 2025)

Microbiota-based therapies in oral health and disorders - Akram N. Salah; Youssef A. Doghish; Shaimaa O. Abbass; Reda M. Mansour; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Ahmed I. Abulsoud; Mohamed Bakr Zaki; Esraa M. Mosalam; Mahmoud A. Elrebehy; et al. (Folia Microbiologica, 2025)
The human oral microbiome is a complex, dynamic ecosystem critically involved in maintaining oral health and contributing to systemic well-being. Many bacteria and fungi are involved in oral cavities such as Penicillium , Rhodotorula , Saccharomycetales , Streptococcus , Veillonella , Neisseria , Actinomyces , and Schizophyllum. Disruption of microbial homeostasis, or dysbiosis, underpins a wide spectrum of oral diseases, including dental caries, periodontal disease, endodontic infections, and mucosal conditions. Recent advances in microbiome research have elucidated the mechanisms by which pathogenic microbial consortia, such as the red complex ( Porphyromonas gingivalis , Tannerella. forsythia , and Treponema denticola ), synergistically promote disease progression through virulence factors, metabolic interactions, and biofilm formation. Emerging microbiome-based therapies, comprising probiotics, postbiotics, predatory bacteria, and using bacteriophages, offer promising adjuncts or alternatives to traditional antimicrobial approaches by restoring microbial balance, reducing pathogenic load, and modulating host immune responses. For instance, probiotic strains like Streptococcus salivarius and Lactobacillus spp. have demonstrated efficacy in reducing plaque, gingival inflammation, and pathogenic bacteria, as well as having significant immunological modulation, while postbiotics provide similar benefits with enhanced safety and stability. Additionally, predatory bacteria such as Bdellovibrio bacteriovorus show potential for selective bacterial elimination and combating periodontal diseases that are driven by Gram-negative anaerobes. Bacteriophages offer another precision tool for targeting oral pathogens by lysing bacteria upon replication. Finally, oral microbiota transplantation aimed at treating periodontal disease by restoring a balanced microbial community in the oral cavity. These innovative strategies, combined with a nuanced understanding of biofilm dynamics and host–microbe interactions, pave the way for personalized and ecologically sustainable oral health interventions. Continued research is essential to translate these promising approaches into clinical practice, optimize delivery systems, and elucidate long-term safety and efficacy.

Acaricidal activity of Astragalus polysaccharides nanoemulsion against camel tick, Hyalomma dromedarii - Shimaa Abdel-Radi; Mai A. Salem; Fady Sayed Youssef; Mohamed S. Kamel; Mohamed M. El-Bahy; Reem M. Ramadan (Experimental and Applied Acarology, 2025)
Hyalomma dromedarii ( H. dromedarii ) is a major ectoparasite of camels in arid regions such as Egypt, where it causes significant economic losses and transmits several zoonotic pathogens. This study evaluated the acaricidal efficacy of a novel, locally prepared Astragalus polysaccharides nanoemulsified formulation (APS-NE) against various developmental stages of H. dromedarii infesting camels. APS-NE was prepared using ultrasonic emulsification and characterized by dynamic light scattering, transmission electron microscopy, and GC–MS, revealing uniform nanoparticle size (30–53 nm), good water solubility, and bioactive constituents including palmitic acid and quercetin derivatives. The formulation exhibited strong biological activity with very low toxicity and a wide safety margin in mice. In vitro bioassays showed a clear concentration-dependent acaricidal effect following short immersion periods: at 2% APS-NE, mortality reached 100% for eggs, larvae, nymphs, and unfed adults. Mortality rates at lower concentrations (0.5–1.5%) ranged from 63.6% to 94.6% in eggs, 33.6% to 84.3% in larvae, 53.3% to 93.6% in nymphs, and 31% to 87% in unfed adults, with larvae being the most susceptible stage. APS-NE also significantly impaired reproductive parameters in engorged females, including reductions in egg production index, egg mass, and hatchability compared to the reference drug. Strong positive correlations were observed between APS-NE concentration and tick mortality, with negative correlations for reproductive metrics. These results highlight APS-NE as a safe, eco-friendly alternative to conventional acaricides for effective H. dromedarii control, supporting integrated tick management strategies.

Efficacy and safety of nitazoxanide and escitalopram as adjuvant therapies in patients with rheumatoid arthritis: a randomized controlled study - Tarek M. Mostafa; Abeer A. El-Sayed; Abdel Moaty A. Afifi; Dalia R. El-Afify (European Journal of Clinical Pharmacology, 2025)
Objective This research aimed at evaluating the effectiveness and safety of nitazoxanide and escitalopram as adjuvant therapies in patients with rheumatoid arthritis (RA). Methods In this randomized controlled parallel study, 90 patients with active RA were randomized into three groups; group 1 (control group; n = 30) which received traditional therapy, group 2 (Nitazoxanide group; n = 30) which received traditional therapy plus 1 gm/day oral nitazoxanide, and group 3 (Escitalopram group; n = 30) which received traditional therapy plus 10 mg/day oral escitalopram for three months. At baseline and 3 months after treatment, clinical and functional assessments were done through the 28-joint count disease activity score using C-reactive protein (DAS28-CRP), the health assessment questionnaire-disability index (HAQ-DI), and the patient’s global assessment (PGA). Also, serum levels of high-sensitivity C-reactive protein (hs-CRP), signal transducer and activator of transcription-3 (STAT-3), Janus kinase-2 (JAK-2), toll-like receptors 4 (TLR-4), interleukin-1 beta (IL-1β), and malondialdehyde (MDA) were assessed. Data were analyzed using paired t -test and one-way analysis of variance, followed by Tukey’s HDS test. Results Three months after treatment and as compared to the control group, the nitazoxanide group showed a significant decline in PGA ( P = 0.042), and serum levels of STAT-3 ( P < 0.001), JAK-2 ( P < 0.001), TLR-4 ( P < 0.001), and IL-1β ( P < 0.001). On the other hand, the escitalopram group produced a significant decrease in DAS28-CRP score ( P = 0.029), HAQ-DI score ( P = 0.001), and serum levels of JAK-2 ( P = 0.001), TLR-4 ( P < 0.001), IL-1β ( P < 0.001), and MDA ( P < 0.001). As compared to nitazoxanide group, the escitalopram group produced a significant decline in fatigue score ( P < 0.001) and serum levels of both IL-1β ( P = 0.023) and MDA ( P < 0.001). Both medications were safe; however, chromaturia was the only significant nitazoxanide-related adverse effect. Conclusion Nitazoxanide and escitalopram could serve as potential adjuvant therapies for patients with RA based on their effectiveness and safety data.

Paleoenvironmental setting and facies analysis of the Middle Miocene carbonate platform in north Western Desert, Egypt - Ibrahim M. Ied; Sherif Farouk; Sayed Abd El-Azeam; Mohammad Abd-Elazez; Ibtsam A. Abd EL-Rauf (Carbonates and Evaporites, 2025)
The Marmarica Formation in the north Western Desert (NWD) of Egypt is predominantly composed of Middle Miocene carbonate rocks. A detailed microfacies and paleoenvironmental analysis was conducted on six representative surface sections extending from the Siwa to Matruh areas: Dakrur, North Siwa (NS), Siwa-Matruh 1 (SM1), Siwa-Matruh 2 (SM2), Abu Khrait, and Agiba. Field observations and lithological data indicate that the Marmarica Formation can be subdivided into three informal members: lower, middle, and upper. A distinct facies shift is observed from interbedded shale and carbonate in the Siwa area to predominantly carbonate facies towards the north in the Siwa-Matruh and Matruh areas. Microfacies analysis of the studied sections identified twelve distinct microfacies types, which are grouped into three main facies associations, corresponding to three paleoenvironmental settings: restricted lagoonal platform interior, open marine shelf (platform top), and high-energy platform shoal. Based on the vertical and lateral distribution of these facies, a homoclinal ramp depositional model is proposed, revealing a clear deepening trend from south to north. In the southern Siwa area, the depositional system evolves vertically from a protected, restricted lagoon to open shelf and shoal settings. Towards the north, the environment becomes progressively deeper, dominated by fluctuations between open marine shelf and high-energy shoal environments. Sequence stratigraphic analysis identified three third-order transgressive-regressive (T-R) depositional sequences (SQ1, SQ2, SQ3), each comprising transgressive system tracts (TST) and highstand system tracts (HST) and are separated by two sequence boundaries (SB1 and SB2). These sequences correspond to global eustatic cycles—such as Haq et al. 1987 and Hardenbol et al. 1998- and correlate with equivalent Miocene carbonate systems in the Tethyan realm highlighting the interplay of eustatic sea-level changes and regional tectonics on carbonate platform evolution during the Langhian–Serravallian stages.

Decrease of AFM1 concentration in cow milk by chitosan and bentonite clay application: impact on sensory and compositional attributes - A. H. Adam; Salwa A. Aly; Rasha M. H. Sayed-ElAhl; M. F. Saad (Brazilian Journal of Microbiology, 2025)

Transcriptomic insights into the healthspan-enhancing effects of C. chinensis seed and E. ulmoides bark extracts in Caenorhabditis elegans - Shimaa M. A. Sayed; Anna Pitas; Christian Schmitz-Linneweber; Nadine Saul (Biogerontology, 2025)
Healthspan, the disease-free period of life, has become a central focus in aging research. Cuscuta chinensis seed and Eucommia ulmoides bark extracts, two traditional Chinese medicine (TCM) remedies, have shown promising healthspan-extending effects in Caenorhabditis elegans . In this study, RNA-seq analysis of aged worms treated with these extracts revealed significant transcriptomic alterations. Gene ontology and KEGG pathway analyses indicated upregulation of genes involved in immune defense, lysosomal function, and protein homeostasis, which may underlie the shared phenotype of enhanced stress resistance and lifespan extension. Beyond these effects, C. chinensis further improved multiple health parameters. Consistent with its broad spectrum of phenotypes, C. chinensis induced extensive transcriptomic remodeling involving over 3000 differentially expressed genes. Modulating collagen-, unc -, and muscle-related genes may explain improved locomotion, while upregulation of mec genes could contribute to enhanced mechanosensation. Notably, far-3 , encoding a fatty acid- and retinol-binding protein, was upregulated more than 150-fold, and RNA interference assays demonstrated that FAR-3 is necessary for C. chinensis -induced healthspan improvement. Furthermore, C. chinensis influenced genes linked to antagonistic pleiotropy and insulin-like signaling, suggesting a systemic, hormesis-driven reprogramming of aging processes. Together, these findings uncover both shared and distinct molecular mechanisms through which C. chinensis and E. ulmoides promote healthspan in C. elegans .

Dietary co-supplementation of Pediococcus acidilactici and bergamot essential oil improves growth, immune response, and disease resistance in sea bream (Sparus aurata) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Hesham Abdallah Hassanien; Abdullah Sheikh; Huda Ahmad Alamer; Hailah M. Almohaimeed; Ehab El-Haroun; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Effects of quadric probiotic blend supplementation on growth, biochemical markers, organ histology, immunity, antioxidant status, and gene expression in Nile tilapia (Oreochromis niloticus) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Ouda Nasser Aldakhillalla; Mohamed Shawky El Sayed; Layla A. Almutairi; Zulhisyam Abdul Kari; Abdelazeem M. Algammal; Helal F. Hetta; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Aquaculture International, 2025)

Small‐Scale Fishers Livelihood Strategies Amid Coastal Reclamation in Malaysia - Salmen A. Bamasood; Khalid Sayed; M. I. Syakir; Mohd Hafiidz Jaafar; Mark Zuknik (Fisheries Management and Ecology, 2025)
Large‐scale coastal reclamation projects threaten small‐scale fisheries that are critical to food security, economic stability, and cultural heritage. We investigated if and how livelihood strategies mediated impacts of reclamation on economic and social resilience of small‐scale fishery communities in Penang, Malaysia. We used the sustainable livelihoods framework (SLF) to explore how fishers adapted to environmental and economic shocks and the effectiveness of strategies for maintaining livelihoods. A mixed‐methods approach combined structured surveys and semi‐structured interviews. However, due to limited access to reclamation projects, only two of five planned interviews with community leaders were completed. Secondary data were also examined from reports by governmental authorities and environmental impact assessments. Human, natural, and social capital provided significant bottom‐up contributions to resilience adaptive livelihood strategies, while financial capital was less effective in improving sustainability because of structural constraints on access to subsidies and alternative jobs. Our findings highlight the need for targeted policy approaches to facilitate capacity building, financial access, and community‐based resource management. Our findings contribute to a policy discussion that balances economic development, social justice, and environmental sustainability so that growing nations do not leave behind their most marginalized fishing communities.

Potential symbiotic effects of date palm seed extract on growth, immunity, antioxidant activities, gut microbiota, expression levels, and Vibrio parahaemolyticus resistance in Shrimp - Roshmon Thomas Mathew; Nashi K. Alqahtani; Hesham S. Ghazzawy; Ehab El-Haroun; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Nagarajan Ganesan; Amel M. El Asely; Layla A. Almutairi; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Frontiers in Marine Science, 2025)
Date Palm Seed Extract (DPSE) is known to possess beneficial health-promoting and growth-boosting properties, but its specific influence on whiteleg shrimp ( Litopenaeus vannamei) health and physiology has yet to be fully explored. Hence, this study examined how dietary DPSE inclusion impacted growth performance, antioxidant status, immune response, hepatic tissue health, inflammation-related gene expression, and resistance to Vibrio parahaemolyticus in shrimp. The study involved four experimental groups of shrimps that were fed diets with varying DPSE inclusions: 0 (DPSE0), 1 (DPSE1), 2 (DPSE2), and 4 (DPSE4) g/kg diet over a 70-day period. The results indicated that dietary DPSE supplementation led to significantly higher (P<0.05) concentrations of whole-body composition (crude protein, gross energy, and crude lipid) in the treated groups. Conversely, the ash content was significantly reduced (P<0.05) in all DPSE-treated shrimp groups compared to the shrimp fed the control diet. Shrimp-fed DPSE-supplemented diets showed a significantly higher total hemocyte count (THC) compared to the control group (P<0.05). The levels of immunological parameters (phagocytosis, phenoloxidase, and lysozyme) and antioxidant status (superoxide dismutase and catalase) were significantly improved with increasing dietary DPSE levels, indicating a dose-dependent effect (P<0.01). The supplementation of DPSE at 1, 2, and 4 g in shrimp diets significantly improved the mRNA expression of immune-related genes ( LGBP, PX, PPA ) and antioxidant genes ( cytMnSOD , mtMnSOD ) compared to the control group (P<0.001). Both total aerobic bacteria and total enteric bacteria were significantly reduced in all DPSE-supplemented groups (P<0.05) compared to the control diet. Dietary inclusion of DPSE improved hepatopancreas tissues and significantly increased resistance to Vibrio parahaemolyticus in shrimp. The results indicate that the dietary inclusion of DPSE can enhance the growth, disease resistance, and overall health of shrimp by regulating immune function, antioxidant status, and immune associated genes regulation. This highlights its potential for sustainable and environmentally beneficial applications in aquaculture.

Hepatoprotection conferred by curcumin against emamectin benzoate-induced oxidative stress, biochemical, molecular, and histological disturbances in rats - Fatma M. El-Demerdash; Reda A. Soker; Hoda M. Nasr; Raghda A. El-Sayed; Wenyi Kang (Toxicon, 2025)

Enhanced preservation of Domiati cheese using edible nanocoating's of carboxymethyl chitosan loaded with pomegranate peel extract - Eman S. El-Ashaal; Hisham A. Elshoky; Nayera M. El-Sayed; Nahed A.A. Elwahsh (Food Research International, 2025)

Integrative use of maize grain embryo extract and bioactive compounds to enhance salinity tolerance in bread wheat (Triticum aestivum L.) - El-Sayed M. Desoky; Enas M.W. Abdel-Hamed; Taia A. Abd El‑Mageed; Ali Majrashi; Atef F. Ahmed; Hoda M. Abou-Elsebaa; Walid F.A. Mosa; Ahmed M. Saad; Mohamed T. El-Saadony; Synan F. AbuQamar; Khaled A. El-Tarabily; Ahmed Shaaban (Field Crops Research, 2025)

Corrigendum to “Rational design of chitosan/guar gum/zinc oxide bionanocomposites based on Roselle calyx extract for Ras cheese coating” [Carbohydr. Polym., Volume 239, 1 July 2020, 116,234] - Samah M. El-Sayed; Hoda S. El-Sayed; Osama A. Ibrahim; Ahmed M. Youssef (Carbohydrate Polymers, 2025)

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

Regeneration of Hibiscus syriacus L. plant via specific Nano-metal oxides in vitro - Iman M. El-Sayed; Shimaa A. Shaaban; Lobna S. Taha; Walaa H. Salama; Rasha A. El-Ziat (Biocatalysis and Agricultural Biotechnology, 2025)

Preconditioning of bone marrow mesenchymal stem cells with sodium hydrosulfide enhances their therapeutic potential in type II collagen–induced arthritis rat model - Sara M. El-Sayed; Hanaa H. Ahmed; Hadeer A. Aglan; Mohamed M. Naguib; Mohamed R. Mohamed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
This study was conducted to evaluate the impact of sodium hydrogen sulfide (NaHS) on the therapeutic efficacy of bone marrow mesenchymal stem cells (BM-MSCs) in the treatment of collagen-induced arthritis (CIA) rats. MSCs were isolated and cultured from rat bone marrow, and their characteristics were determined. The CIA model was induced in rats by intradermal injections of type II collagen on days 0 and 21. A variety of treatments were administered, including naproxen, BM-MSCs, BM-MSC-conditioned media, NaHS, BM-MSCs preconditioned with NaHS, and BM-MSCs preconditioned with NaHS-conditioned media. The infused BM-MSCs homed to the bone trabeculae and cartilage of the knee joint, leading to significant improvements in gait scores and a reduction in paw withdrawal frequency (PWF). Treatment with BM-MSCs and NaHS also significantly suppressed serum levels of CRP, RF, and 14-3-3η, while downregulating TNF-α gene expression and MMP-1 protein levels in the synovial membrane. Histopathological analysis confirmed these biochemical and molecular genetic findings. Notably, CIA rats treated with BM-MSCs preconditioned with NaHS showed the most significant improvements, with outcomes closely resembling those of healthy controls. This study concludes that NaHS enhances the therapeutic efficacy of BM-MSC therapy for rheumatoid arthritis (RA) by augmenting their anti-inflammatory, immunomodulatory, and regenerative properties.

Preparation and optimization of eco-friendly inorganic geopolymer membrane - A. M. El-Sayed; H. Abdallah; M. Abdel-Goad; R. Abobeah; Sh. K. Amin (International Journal of Environmental Science and Technology, 2025)
The most common and widely used technique for water and wastewater treatment is membrane separation. This research was applied to fabricate an eco-friendly, low-cost, and sustainable geopolymer membrane that can be used in water treatment. A geopolymer membrane is fabricated using fired clay brick waste, the effect of several variables on the apparent porosity, compressive strength of the membrane, iron and manganese rejection was studied using response surface methodology, the studied variables are zeolite addition in the range of 0–25% by weight, curing temperature at the range from 50 to 90 °C and curing time ranging from 1 to 3 days. According to experimental results, the optimum membrane is prepared using only fired clay brick waste, cured at 70 °C for 1 day. Long-term performance test and fouling test were performed to ensure membrane durability, thus the flux recovery ratio was 97.94%, while the total fouling ratio was 3.66%, of which 1.6% was reversible. These membranes were further characterized through Fourier transform infrared spectroscopy, scanning electron microscope, and pore size distribution, and the results confirmed that the membrane had micropores with an average pore diameter of 0.1212 µm. The optimum membrane was used in a real water application and the manganese and iron rejection reached 99.8% and 90% respectively.

Therapeutic potential of purpurin, a natural anthraquinone dye, in neuroprotection and neurological disorders - Aya M. Mustafa; Ghadir A. Sayed; Shymaa Hatem; Roxane Abdel-Gawad Moussa; Dina M. Hal; Mahmoud A. Mansour; Mohamed S. Abd El Hafeez (Inflammopharmacology, 2025)
Purpurin (1,2,4-trihydroxy-9,10-anthraquinone) is a naturally occurring anthraquinone pigment derived primarily from Rubia species. Beyond its traditional use as a natural dye, purpurin has recently gained attention for its multifaceted pharmacological activities, particularly in neuroprotection. This review outlines the biosynthetic pathways leading to anthraquinone formation via the shikimate, mevalonate, and methylerythritol phosphate routes, culminating in the generation of purpurin. Structure–activity relationship analyses highlight the critical role of hydroxyl substitutions in modulating antioxidant, anticancer, antibacterial, and neuroprotective properties through radical stabilization, DNA intercalation, and metal chelation. Evidence from preclinical studies indicates that purpurin exerts beneficial effects in Alzheimer’s disease, depression, ischemic stroke, and age-related cognitive decline, primarily through anti-tau aggregation, cholinesterase inhibition, serotonergic modulation, antioxidant activity, and anti-inflammatory mechanisms. While purpurin exhibits low acute toxicity and promising pharmacodynamics, its therapeutic translation remains limited by poor solubility, rapid metabolism, and low brain bioavailability. Nanotechnology-based formulations and molecular modifications are being explored to overcome these challenges. Collectively, purpurin represents a versatile bioactive scaffold with considerable potential for the development of multifunctional neuroprotective agents.

Chitosan-stabilized selenium nanoparticles stimulate performance, feed utilization, health biomarkers, and histological integrity in Litopenaeus vannamei - Mohammed A. Abdel-Ghani; Ahmed F. Fath El-Bab; Sayed F. Elhawari; Sherief M. Abdel-Raheem; Mohamed El-Sayed El-Sharawy; Mohammed A. E. Naiel (Aquaculture International, 2025)

First report of Astragalus polysaccharide nanoemulsion efficacy against Clinostomid metacercariae in Nile Tilapia - Mai A. Salem; Olfat A. Mahdy; Fady Sayed Youssef; Mohamed S. Kamel; Reem M. Ramadan (Veterinary Parasitology, 2025)

Phytochemical insights and hepatoprotection evaluation of Heliotropium arbainense: Analyzing gene expression and therapeutic potential - Alsayed E. Mekky; Albayoumi A. Fouda; Osama Mohammad Mohammad Abdelhay; Kamal Rady Mohammed; Mohamed Arafat Mohamed Mansour; Mohamed A.M. El-Tabakh; Abeer Mahmoud Mohammad; Amani Alhejely; Taiseer Ahmed Shawky; Eslam S. Abdelmouty; Mohamed Khedr; Mahmoud Radwan; et al. (South African Journal of Botany, 2025)

Microplastic abundance, characteristics, and associated ecological risk assessment in the selected coastal areas of Baybay City, Leyte, Philippines - Abu Sayed Al Helal; Abu Bakar Siddique; Teofanes A. Patindol; Kleer Jeann G. Longatang; Deejay M. Lumanao; Anabella B. Tulin; Molla Rahman Shaibur (Regional Studies in Marine Science, 2025)

Poly(styrene-alt-chitosan malonate)/poly(ether sulfone) blend membranes for ultrafiltration with enhanced antifouling performance - Mosaed S. Alhumaimess; Ibrahim Hotan Alsohaimi; Raghad Ayed Alenazi; Mohamed Y. El-Sayed; Abdullah M. Aldawsari; M.R. El-Aassar; Ahmed A. Alshahrani; Hassan M.A. Hassan (Journal of Water Process Engineering, 2025)

Butylated hydroxytoluene (BHT) improved semen quality and sperm DNA of frozen-thawed Arabian stallions preserved in modified INRA-82 extender - Amal M. Aboelmaaty; Islam El-Sayed El-Seadawy; Mohamed Saeed Kotp; Alaa A. Mohamed; Hazem Ahmed El-Debaky; Diya A. El-Badry; Abeer M. Anwer; Tsvetan Tsvetkov; Teodora Daneva; Mahmoud A. Elgabry (Journal of Equine Veterinary Science, 2025)

Development of novel ferrocene-functionalized NH2-MIL-125 MOF for efficient photocatalytic degradation of indigoid dyes under visible light - Mostafa A. Sayed; Osama A.S. Rafea; Ali M. Abdel-Aziz; Reda M. Abdelhameed; Ibrahim H.A. Badr (Journal of Environmental Chemical Engineering, 2025)

Choline hydroxide mediated eco-friendly synthesis of 5-arylidene thiazol-4(5H)-one clubbed coumarin: antimicrobial evaluation and in silico studies - Muneera S. M. Al-Saleem; Jehan Y. Al-Humaidi; Ahmed A. Elhenawy; Sayed M. Riyadh; Magdi E. A. Zaki; Ohoud A. Jefri; Sobhi M. Gomha (The Science of Nature, 2025)

Evaluation of the newly recorded alga Phyllymenia gibbesii compared with six Egyptian native species as biofertilizers to enhance growth and yield of potato cultivars - Sayed S. Aboshosha; Nader A. Ashmawy; Nihal G. Shams El-Din; Mai M. A. Abd El-Ghany (Journal of Applied Phycology, 2025)
Seaweeds are acknowledged for their potential as biofertilizers and biostimulants, contributing to enhanced growth and yield of various crops globally due to their appropriate amount of macro- and microelements, plant growth regulators, and their richness in bioactive compounds. In the current study, the seaweeds Ulva lactuca , Ulva intestinalis , Corallina officinalis , Ellisolandia elongata , Jania rubens , Colpomenia sinuosa , and the newly recorded red alga Phyllymenia gibbesii were collected from the eastern coast of Alexandria, Egypt (Mediterranean Sea) from April 2015 until June 2016 and were evaluated as biofertilizers to enhance the growth and yield of potato cultivars (cv. Hermes and cv. Bellini). The chemical contents of macroelements (Ca, Na, N, P, and K) and the microelements (Zn, Cu, Ni, Cd, Co, Pb, and Fe) were determined in the dry seaweed powder and its water extracts. For short-term use of SWEs, the results showed that all the measured microelements and Na in seaweed extracts were below the permissible levels according to FAO/WHO. For long-term use of SWEs, the Co concentration exceeded the permissible level in all SWEs according to FAO/WHO . The same pattern was observed for Cd, except for C. officinalis and P. gibbesii . The concentration of Cu and Ni exceeded the permissible levels in U. intestinalis and C. officinalis (0.28 and 0.36 mg L −1 ), respectively, for Cu and (0.41 and 0.31 mg L −1 ), respectively, for Ni. For the analyses of carbohydrates and protein in seaweeds, P. gibbesii had the highest concentration of carbohydrates (56.2 ± 3.8%), followed by U. lactuca (53.6 ± 5.1%), while the protein content showed the inverse pattern. The growth-regulating hormones (IAA, Kinetin, GA 3 , and ABA) were quantified in the seaweeds. Ulva lactuca had the highest concentrations of (IAA, GA 3 , and ABA) (1 µg g −1 FW, 0.12 µg g −1 FW, and 0.006 µg g −1 FW), respectively. The highest concentration of kinetin occurred in C. sinuosa (0.168 µg g −1 FW). In the greenhouse experiment, the seaweed extracts were applied (autoclaved and non-autoclaved) to evaluate their effects on the potato cultivars. The algal extracts, particularly C. sinuosa , U. lactuca , and P. gibbesii , were promising for potato growth and yield parameters for both cultivars. Due to the high concentrations of some microelements in seaweed extracts, which exceeded the permissible levels for long-term use according to FAO/WHO, they are recommended to be used only for short-term irrigation.

Adsorption of light green dye using Mg–Al-layered double hydroxides (LDHs) with carbonate and nitrate anions - S. F. Al-Furhud; R. M. K. Mohamed; I. Alsohaimi; M. M. Kamel; M. Y. El-sayed; H. M. Youssef; A. M. Aldawsari; H. M. A. Hassan (International Journal of Environmental Science and Technology, 2025)

Phage therapy and its role in cancer treatment and control - Heba Ibrahim Abd El-Moaty; Ahmed S. Doghish; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Mahmoud A. Elrebehy; Kareem AlFarsi; Amr M. Abdelfatah; Aly M. Waseem; et al. (Folia Microbiologica, 2025)

Evaluation of spawning induction, egg incubation, and larval rearing of sea bass (Dicentrarchus labrax) in groundwater and seawater resources through different water management systems - Reham M. K. Negm; Heba Saad El-Sayed; Hadir A. Aly (Aquaculture International, 2025)
This study evaluated the viability of using groundwater (GW) compared to seawater (SW) in European sea bass ( Dicentrarchus labrax ) aquaculture. Wild broodstock were captured 2 months before spawning and acclimated to tanks with either SW or GW 1 week prior. Females received HCG injections in both water types. Fertilized eggs were collected into six conical tanks supplied with SW or GW. At 7 days post-hatch (dph), larvae were transferred to 12 rearing tanks with SW or GW, using either flow-through or static water systems (three replicates per treatment). Growth performance and survival were monitored up to 60 dph. The results revealed that spawning induction of European sea bass broodstock failed in GW while succeeded with egg fertilization and hatchability up to 97 ± 1% in SW. Hatching was 96 ± 1% for the fertilized eggs transferred from SW to GW incubators. However, the newly hatched larvae suffered high mortality up to 7 dph, which gradually decreased with the start of exogenous feeding. During the period from 7 to 60 dph, larvae and post-larvae showed normal viability and survival with either flow-through or static water systems in SW and GW. At the end of the experiment, the results indicated that water sources in combination with the water-rearing systems significantly affected post-larvae performance. Larval survival was significantly higher in both GW systems (static: 88.8 ± 2.1%, flow-through: 89.9 ± 5.6%) and in the static SW system (84.15 ± 2.8%) compared to the flow-through SW system (70.4 ± 5.8%). Moreover, the final length of larvae at 60 dph was significantly higher in the static GW system (2.27 ± 0.09 cm). In addition, larvae reared in static GW had higher final weight (140. 00 ± 4.24 mg). Total protein and total lipid contents were significantly higher in larvae reared in GW than those reared in SW for both water systems. The study suggested a static GW system for European sea bass larval rearing starting from 7th dph onwards to achieve better larval quality and higher survival. Future research is needed to enhance GW with new technologies to accommodate D. labrax– induced spawning and newly hatched larval rearing.

Salinity-dependent vulnerability of whiteleg shrimp (Litopenaeus vannamei) to Vibrio parahaemolyticus: growth performance and antioxidant response - Lamiaa A. Okasha; Enas A. H. Farag; Rasha M. H. Sayed-ElAhl; El-Sayed H. Eissa; Ahmed H. Sherif (Aquaculture International, 2025)
Whiteleg shrimp (Litopenaeus vannamei) became one of the most cultured crustacea in marine farms in North Egypt. The bacteriological examination of two shrimp farms (water salinity 4.28 and 28.5 g/L) that exhibited high mortality rates revealed the causative agents, which were three Vibrioparahaemolyticus strains VHLA1-3. They were identified by detecting three genes: integral membrane protein (toxR) and haemolysin genes ( tdh and trh ). The strains were multidrug-resistant and were sensitive to ciprofloxacin and florfenicol; also, their median lethal doses (LD 50 ) were 3.78 × 10 5 , 1.99 × 10 5 , and 1.95 × 10 5 CFU/mL, respectively. In the experiment, 180 healthy shrimp (5.3 ± 0.03 g, body weight) were reared in three different water salinities 7, 35, and 50 g/L for 8 weeks and then were challenged with LD50 of the isolates VHLA1-3. At salinity of 50 g/L, shrimp experimentally infected with VHLA1, VHLA2, and VHLA3 showed a higher MR of 60%, 80%, and 80% compared to those of 7 and 35 g/L; florfenicol treatment resulted in mortality rate ranged between 10 and 20% regardless water salinity. Bacterial re-isolation (RI%) was 100% in challenged-untreated shrimp, whereas RI% was decreased after florfenicol treatment by 20%, 30 to 40%, and 0% at salinity of 7, 35, and 50 g/L, respectively. Experimental shrimp reared in high salinity (50 g/L) showed significantly higher final weight (15.6 g), specific growth rate (1.54%/fish/day), and low FCR compared to those of low salinity water (35 and 7 g/L). At salinity of 50 g/L, the expression of catalase CAT and superoxide dismutase SOD genes was significantly higher compared to those of low salinity, while the heat shock protein Hsp70 expression was significantly raised in 50 g/L, followed by 7 g/L then 35 g/L in the hepatopancreas of shrimp. It was obvious that V. parahaemolyticus was the causative agent in shrimp mortality, with different patterns of virulent genes. Water salinity was the control factor in antioxidant status and V. p arahaemolyticus infection. Shrimp reared at salinity extremities, 7 and 50 g/L, exhibited high mortality and bacterial re-isolation. So, florfenicol treatment is recommended in V. parahaemolyticus infection, and salinity extremities (7 and 50 g/L) should be avoided during rearing whiteleg shrimp.

Biological, biochemical, hormonal effect, and histological perturbations of Procambarus clarkii (Crustacea: Cambaridae) hemolymph on Biomphalaria alexandrina snails - Salwa A. H. Hamdi; Sayed Abd El-Monem; Amina M. Ibrahim; Mona F. Fol; Nesma A. Mostafa (Aquaculture International, 2025)
Schistosomiasis is a severe illness carried by snails of the genus Biomphalaria , which have a large distribution in Egypt. Control of the intermediate host snail is critical in limiting schistosomiasis spread. On the topic of snails’ management, bioactive products extracted from aquatic invertebrates have gained more interest. Here, for the first time, the current research intended to identify the bioactive compounds present in hemolymph collected from the freshwater crayfish Procambarus clarkii and to assess its molluscidal activity against Biomphalaria alexandrina snails. Results showed that following exposure to the sub-lethal concentrations (LC 10 34.9 and LC 25 42.8 mg/l) of hemolymph, a reduction in survival and reproductive rates of B. alexandrina was detected, as well as a substantial increase in transaminases (AST and ALT) activities, while a reduction in total protein and albumin levels. Also, levels of testosterone and 17β-estradiol hormones decreased compared to the control group. Histopathological examination of the digestive gland of treated B. alexandrina displayed a shrinkage of the tubules and an increase in the inter-tubular spaces, and also, degeneration in the oocytes and spermatocytes of the hermaphrodite glands with a loss of connective tissues between the acini was observed. Thus, based on these results, a new strategy should be developed for a better use of these agents in schistosomiasis control.

Perichondral telocytes and their role in cartilage development and regeneration: Insights from histochemistry, immunohistochemistry, and TEM - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Hesham Ismail; Sherief M. Abdel-Raheem; Ahmed M.A. Meligy; Soha A. Soliman (Research in Veterinary Science, 2025)

Stage-wise monitoring of microplastics (MPs) in wastewater treatment plants (WWTPs): Abundances, characteristics, polymer types, and removal - Wenbo Kong; Mabkhoot Alsaiari; Mohammed Jalalah; Farid A. Harraz; Ibrahim M. Hegab; Maha Awjan Alreshidi; El-Sayed Salama (Process Safety and Environmental Protection, 2025)

Impact of red flour beetle Tribolium castaneum (Herbst) infestation in wheat flour on benzoquinone levels and biscuit quality - Ebtesam Farah Badran; Eizz Elden A. Elshazly; Tarek Gamal Abedelmaksoud; Gehad M. Khattab; Sayeda Sayed Ahmed (Journal of Stored Products Research, 2025)

Relationship Between Grain Yield Response Index and Wheat Genotypes Adapted to Nitrogen–Deficient Environments - Yassmin T. M. Emam; Afafa M. Tolba; Yasser A. El-Gabry; Ibrahim M. El– Metwally; Hani Saber Saudy; Amany N. Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Plant breeders of self-pollinated crops such as wheat often obtain huge number germplasms via hybridization programs. However, screening these germplasms to select the best ones, especially in terms of nitrogen (N) use efficiency, is not an easy task. Thus, the current study was designed to determine the significance of grain yield response index (GYRI) as a promising parameter versus the traditional agronomic traits to characterize the most efficient and responsive wheat genotypes to applied N. The study involved twenty bread wheat genotypes (six commercial varieties namely Sakha 94, Sakha 95, Giza 171, Gemmiza 12, Masr 1, Masr 2 and 14 new lines, numbered from 1 to 14). Over two seasons, the performances of these genotypes were monitored under three N levels: optimum N (192 kg N ha –1 , farmer practice), moderate deficit N (144 kg N ha –1 +biofertilizer) and high deficit N (96 kg N ha –1 +biofertilizer). The experiment was designed in split-plot and replicated thrice. Line 11 under optimum N or high deficit N and Line 4 under moderate deficit N in the first season as well as Line 14 under high deficit N in the second season had the earliest heading time. Under normal N application (192 kg N ha –1 ), Masr 1 in the first season and Gemmiza 12 in the second season had the widest flag leaf. Under moderate deficit N, Line 6 in the first season and Line 14 in the second one surpassed all other genotypes. Application of 144 kg N ha –1 +biofertilizer×Line 3 in the second season outperformed all other genotypes grown under the other N treatments. Line 9, Line 10, Line 13, Sakha 95 and Gemmiza 12 (under moderate deficit N) as well as Line 7, Line 8, Line 9, Line 13, Line 14, Gemmiza 12 and Masr 1 (under high deficit N) recorded the greatest values of grain yield in the first season. While, Sakha 95 and Line 9 were the marked genotypes for producing the maximum grain yield under moderate deficit N and high deficit N, respectively, in the second season. GYRI estimation exhibited that Line 11 and Sakha 95 in the first season and Sakha 95 and Masr 2 in the second one were the efficient and responsive genotypes for N applications. Obviously, GYRI as a breeding parameter can contribute greatly to resolving the conflict between crop traits in terms of distinguishing N-deficiency tolerant varieties. Herein, GYRI detected that Line 11, Sakha 95 and Masr 2 are considered promising germplasms to develop and improve wheat to tolerate low N supply. Further, the increased grain yield of some tested genotypes (i.e. Line 5, Line 6, Line 8, Line 9, Line 13, Line 14, Giza 171, Masr 1, Gemmiza 12) under deficit N than optimal N is an observation worthy of in-depth future investigation.

Effects of Gabapentin, Valsartan, and Codeine on hemato-biochemical and histological biomarkers of male catfish (Clarias gariepinus) - Abdelaziz A. A. El-Sayed; Walaa M. Abdel-Samei; Hamdy A. M. Soliman; Mervat N. Hana; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2025)

Chitosan-Nanoparticles Mitigate Cadmium Chloride Hepatorenal Toxicity in BALB/C Mice Via Amendment of Nrf2/HO-1 and NF-κB/iNOS Signaling Pathways - Asmaa F. A. Dawood; Salwa A. Fouad; Hanan M. Alharbi; Mohamed Abd El-Aal; Mohammed I. Elkhateeb; Zain El Abdeen Ali; Nermeen N. Welson; Leila H. Sayed (Biological Trace Element Research, 2025)

Benthic Ostracods as Indicators of Nearshore Pollution: An Example from Hurghada Bay, Red Sea Coast, Egypt - Ramadan M. El-Kahawy; Petra Heinz; Mostafa M. Sayed; Ammar Mannaa; Rabea A. Haredy; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
Twenty-nine sediment samples were collected from Hurghada Bay, a highly impacted coastal area along the Northern Red Sea of Egypt, to evaluate environmental quality and human-induced effects on benthic ostracods. As potential bioindicators, benthic ostracods are highly responsive to environmental disturbances, with pollution leading to reduced abundance, lower diversity, and increased opportunistic taxa. To investigate the link between ostracod assemblages and sediment contamination, we measured the concentrations of eight heavy metals (Cu, Cd, Zn, Pb, As, Cr, Ni, and Mn) using inductively coupled plasma–atomic emission spectrometry (ICP-AES). Multivariate statistical analyses identified three distinct ostracod assemblages distributed across three station groups with varying pollution levels. Group I, associated with offshore stations, exhibited low to moderate heavy metal (HM) concentrations and high ostracod abundance and was dominated by Moosella striata, Hiltermannicythere rubrimaris, Ruggieria danielopoli, Neonesidea schulzi, and Paranesidea fracticorallcola, where the water depth and sand content are the main controlling factors. In contrast, Group II, corresponding to stations with the highest HMs and total organic matter (TOM), was dominated by pollution-tolerant species Jugosocythereis borchersi, Cyprideis torosa, Alocopocythere reticulata, and, to a lesser extent, Ghardaglaia triebeli, with reduced ostracod density and diversity. Group III, characterized by stations influenced by the mud-controlling factor, had the lowest HMs and was dominated by pollution-sensitive species Xestoleberis rhomboidei, Paranesidea fortificata, and Loxocorniculum ghardaquensis. These findings highlight the ecological risks posed by HM pollution and emphasize the urgent need for pollution mitigation strategies and continued monitoring to preserve the Red Sea’s benthic biodiversity.

Harnessing the Microbiome: CRISPR-Based Gene Editing and Antimicrobial Peptides in Combating Antibiotic Resistance and Cancer - Radwa A. Amen; Yaser M. Hassan; Rawan A. Essmat; Rana H. Ahmed; Marwan M. Azab; Nadia R. Shehata; Mariam M. Elgazzar; Wael M. El-Sayed (Probiotics and Antimicrobial Proteins, 2025)
The growing crisis of antibiotic resistance and the increasing incidence of cancer have prompted the exploration of innovative approaches, such as gene editing and antimicrobial peptides (AMPs). The human microbiome is integral to various aspects of health, disease, and therapeutic development, influencing metabolic pathways, immune function, and pathogen resistance. Recent advances in gene editing technologies, particularly CRISPR (clustered regularly interspaced short palindromic repeats), have opened new avenues for leveraging the microbiome to address complex medical challenges, including combating multidrug-resistant pathogens and cancer. The microbiome plays a crucial role in combating antibiotic resistance by modulating microbial communities, influencing pathogen survival and susceptibility to treatments. This review explores the microbiome’s dynamic role in metabolic regulation, its contribution to cancer management, and how AMPs help maintain homeostasis and exhibit emerging anticancer properties, supported by both preclinical findings and clinical evidence. Additionally, CRISPR-based microbiome engineering offers potential to enhance host-microbiome interactions, optimizing therapeutic outcomes. The integration of microbiome metagenomics and proteomics has led to the discovery of novel AMPs with targeted anticancer effects. Innovative strategies, such as engineered probiotics and CRISPR-based microbiome engineering, present exciting prospects for next-generation therapies. Despite these advances, the translation of microbiome-based therapies into clinical settings remains challenging due to ethical, regulatory, and ecological hurdles. This review underscores the transformative potential of microbiome-based interventions, emphasizing the role of personalized medicine in maximizing therapeutic efficacy. Furthermore, we also address critical research gaps, limitations, and future directions, including optimizing AMP stability, delivery, and bioavailability, as well as overcoming the regulatory and ethical challenges in clinical translation.

MicroRNAs in HIV infection: dual regulators of viral replication and host immunity - Reda M. Mansour; Gharieb S. El-Sayyad; Nehal I. Rizk; Sherif S. Abdel Mageed; Mohamed Salah Basiouny; Salma A. El-Sayed; Salma Zaki Fayez; Moustafa Mahmoud Abdelaziz; Khaled Abuelhaded; Haidy Adel Fahmy; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Impacts of PVC microplastic ingestion on Biomphalaria alexandrina: behavioral, physiological, and histological responses - Amina M. Ibrahim; Ahmed A. A. Hussein; Menna H. E. Morsy; El-Sayed Baz (Hydrobiologia, 2025)
Microplastic pollution has emerged to be a crucial environmental concern. Despite the growing body of research on microplastic ingestion in oceans and marine organisms, there is a knowledge gap concerning the effects of microplastic exposure on freshwater ecosystems, which support diverse communities of plants, animals, and microorganisms. The freshwater snail Biomphalaria alexandrina is a valuable model for dissecting the ecological impact of many pollutants in aquatic environments. This study aimed to investigate the impacts of ingesting microplastic particles on B. alexandrina , particularly focusing on polyvinyl chloride (PVC), widely used in plastic applications, piping, electrical, and vehicle equipment, which results in their frequent presence in ecosystems. A combination of behavioral, physiological, biochemical, and histological assessments revealed profound effects of microplastic ingestion by these mollusks. These effects include the accumulation of PVC particles in their intestines, a reduction in feeding behavior, decreases in survival and growth rates, disruptions in biochemical parameters, induction of oxidative stress, and histological damage to their digestive glands. Additionally, our data suggest that the adverse impacts are concentration-dependent, with higher PVC concentrations causing more severe harm. Our findings advance our understanding of the potential consequences of microplastic pollution in freshwater habitats and inform targeted mitigation strategies.

Physical purification of Egyptian bentonite clay as a sustainable binder of El-Dekheila-iron-oxide-waste - Ahmed A. Khalifa; El-Sayed R. E. Hassan; A. M. Elbendari; Rasha Amin; M. A. Abdel-Khalek (Euro-Mediterranean Journal for Environmental Integration, 2025)

Quaternary ammonium compounds in medicinal herbs and health risk assessment - Yasmin S. Nasr; Osama El-Sayed Hussein; Hassan A. El-Gammal; Mostafa M. H. Khalil (Food Additives & Contaminants Part B-Surveillance, 2025)

Protective effect of empagliflozin against paracetamol-induced acute kidney injury through modulation of AMPK/SIRT1/PGC-1α pathway in experimental mice - Esraa M. Mosalam; Hind S. AboShabaan; Marwa M. Mahfouz; Amany Said Sallam; Enas Elhosary; Albatoul Allam; Ebtehal M. Metwally; Moataz A. Shaldam; Mai El-Sayed Ghoneim (Toxicology and Applied Pharmacology, 2025)

Synthesis and antimicrobial evaluation of a new hybrid bis-cyanoacrylamide-based-piperazine containing sulphamethoxazole moiety against rheumatoid arthritis-associated pathogens - Mona M. Soliman; Ahmed H. M. Elwahy; Ahmed M. Sayed; Mahmoud Ibrahim; Mohamed A. Dawoud; Shahd Hisham Mohamed Ali; Menna Tallah S. Nady; Nada A. Hassan; Wessam Saad; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Piperazine-based compounds have garnered significant attention due to their notable biological and pharmacological activities, making them essential in fine chemical and pharmaceutical applications. In this study, we managed to synthesize a novel hybrid bis-cyanoacrylamide bearing the piperazine core via phenoxymethyl linker and incorporating sulphamethoxazole moiety. The novel compound was fully characterized using different spectral data including 1H-NMR, 13 C-NMR, and FTIR spectroscopy. Piperazine-based compounds were screened for in silico studies to understand the antimicrobial activity against infections that may contribute to rheumatoid arthritis symptoms. The tested piperazine compound was also evaluated for its antimicrobial activity against Aspergillus niger , Candida albicans , Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 29213, Pseudomonas aeuroginosa ATCC 27853, Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603. S. aureus showed the highest inhibition, with a zone diameter of 16.0 ± 1.0 mm at a concentration of 0.8 mg/ml. The minimal inhibitory concentration (MIC) for all bacterial species ranged from 5 to 40 mg/ml. In contrast, fungal species were the most resistant to the tested compound. Molecular docking studies were conducted to elucidate the interaction mechanisms, binding energies, and hydrogen bonding interactions within protein–ligand complexes. Molecular docking studies were performed against five bacterial proteins and two fungal proteins, including DNA gyrase subunit B (UniProt ID: Q839Z1), protein RecA of (UniProt ID: P0A7G6), cyclic AMP-AMP-AMP synthase (UniProt ID: P0DTF7), UDP-N-acetylglucosamine 1-carboxyvinyl transferase (UniProt ID: A0A1S5RKE3), and clumping factor A (UniProt ID: Q53653). The tested compound achieved the highest binding score of ∆G = − 10.9 kcal/mol at the cyclic AMP synthase active site (UniProt ID: P0DTF7), forming 26 interactions. The results demonstrated that the synthesized piperazine compound exhibits promising antibacterial and antifungal activities, highlighting its potential as a candidate for antimicrobial development.

Remote sensing, petrogenesis and tectono-magmatic evolution of the Wadi Queh-Wadi Abu Shigeili area: a window into the transitional history of the central Egyptian-Nubian Shield from pre-plate collision to post-collision magmatism - Osama K. Dessouky; El-Sayed H. El-Sawey; Yasser S. Badr; Sobhi Nasir; Gehad M. Saleh; Ahmed M. Dardier; Kamal A. Ali; Abdel-Rahman Fowler; Saleh E. Ammar; Ahmed M. Ismail; Mahmoud M. Hassan (International Journal of Earth Sciences, 2025)

Whole genome sequencing identifies monogenic disease in 56.1% of families with early-onset steroid-resistant nephrotic syndrome - Neveen A. Soliman; Mohamed A. Elmonem; Ahmed F. El-Sayed; Eman Ramadan; Ahmed M. Badr; Fatma M. Atia; Rasha Helmy; May O. Amer; Ahmed Abd El-Raouf; Fadya M. El-Garhy; Omnia M. Abdel-Haseb; Tokka M. Hassan; et al. (Human Genetics, 2025)
Genetic causes of steroid-resistant-nephrotic-syndrome (SRNS) represent a rapidly growing number of monogenic diseases. The reported diagnostic yield of various studies applying genetic panels and exome-sequencing to diagnose SRNS is usually < 30%. We performed genome-sequencing in a cohort of Egyptian SRNS patients. We recruited 47 SRNS patients belonging to 41 unrelated families [28 males/19 females; median (range): 6 (0.5–22 years)]. We established a pipeline for genome sequencing, bioinformatics analysis, variant curation and protein modeling at the Egypt Center for Research and Regenerative Medicine (ECRRM). Disease-causing variants were detected in 27/47 patients (57.4%) belonging to 23/41 families (56.1%), including nine novel variants in NPHS1, NPHS2, COL4A3, MYO1E, NUP93, PLCE1, PODXL, SMARCAL1 and WT1 . Novel variants were confirmed by Sanger sequencing and were segregated in families of affected patients. NPHS2 was the most common causative gene in 8/23 (34.8%) of confirmed families, followed by NPHS1 , WT1 , and SMARCAL1 in 2/23 families (8.7%) each. All detected missense variants were evaluated through protein modeling and were predicted deleterious. Our study expanded the spectrum of SRNS disease-causing variants and revealed a monogenic cause in 56.1% of investigated families. In our cohort, no deep intronic or regulatory variants were detected by genome-sequencing. Pursuing genetic diagnosis in SRNS patients is crucial to inform clinical decision making, genetic counseling, transplantation strategy and prenatal diagnosis thus improving clinical outcome of affected patients.

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Targeting TLR4/NF-κB signaling, oxidative stress, and apoptosis by farnesol mitigates cadmium-induced testicular toxicity in rats - Emad H.M. Hassanein; Mohammed F. Alotaibi; Reem S. Alruhaimi; Mostafa Sabry; Ghadir A. Sayed; Ahmed M. Atwa; Ayman M. Mahmoud (Tissue and Cell, 2025)

Realistic and effective degradation of petroleum related contaminants in seawater using ecofriendly NiO and ZnO nanocomposites with ca-MCM-41: Assessment and remediation - Mashael D. Alqahtani; Alshaima Sayed; May N. Bin Jumah; Nahaa M. Alotaibi; Hassan A. Rudayni; Ahmed A. Allam; Mostafa R. Abukhadra (Journal of Water Process Engineering, 2025)

Investigating the effects of granite, marble, granodiorite, and ceramic waste powders on the physical, mechanical, and radiation shielding performance of sustainable concrete - Alaa A. Mahmoud; Alaa A. El-Sayed; Ayman M. Aboraya; Islam N. Fathy; Mohamed A. Abouelnour; Bassam A. Tayeh; Islam M. Nabil (Annals of Nuclear Energy, 2025)

The role of histological stains in aquaculture and fisheries development technology - El-Sayed Hemdan Eissa; Alkhateib Y. Gaafar; Roshmon Thomas Mathew; Eman A. Al-Shahari; Ekemini Moses Okon; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2025)

Zinc-based metal–organic frameworks for sustainable water desalination and anti-scaling solutions - Mennat Allah M. Ali; Mona El-Sayed; Omnia A. A. El-Shamy; Ghada E. Khedr; Magdy W. Sabaa; Riham R. Mohamed; Mahmoud F. Mubarak (Environmental Science and Pollution Research, 2025)

Assessing Pan-Canada wildfire susceptibility by integrating satellite data with novel hybrid deep learning and black widow optimizer algorithms - Khabat Khosravi; Ashkan Mosallanejad; Sayed M. Bateni; Dongkyun Kim; Changhyun Jun; Ali Reza Shahvaran; Aitazaz A. Farooque; Massoud Karbasi; Mumtaz Ali (Science of The Total Environment, 2025)

Chitosan-coated liposomes of pomegranate-peel phenolic extract: Maximizing the bioaccessibility and antimicrobial activity in probiotic goat yoghurt - Malikakhon Kurbonova; Marwa M. El-Said; Samah M.S. EL-Shafei; Victoria llina; Hoda S. El-Sayed; Wael M. Elmessery; Mahmood A. Hashim; Tamer M. El-Messery (Journal of Stored Products Research, 2025)

Assessing seawater intrusion impact on groundwater quality in El-Omayed aquifers, Mediterranean coast, Egypt using hydrogeochemical and chemometric analyses - Mohammed I.A. Ibrahim; Mohamed A. El-Sawy; Ahmed R. Elgendy; Hossam M. El-Sayed; Laila A. Mohamed; Mohamed A. Aly-Eldeen (Groundwater for Sustainable Development, 2025)

Structural and Energetic Insights into the Binding of L- and D-Arginine Analogs with Neuropilin-1 (NRP1): Molecular Docking, Molecular Dynamics and DFT Calculations - Mahmoud A. A. Ibrahim; Dina E. M. Mohamed; Khlood A. A. Abdeljawaad; Alaa H. M. Abdelrahman; Shaban R. M. Sayed; Mohamed A. El-Tayeb; Peter A. Sidhom; Paul W. Paré (Cell Biochemistry and Biophysics, 2025)

Decorin alleviates non-alcoholic fatty liver disease in rats with polycystic ovary syndrome - Hany A. Elkattawy; Amira Ebrahim Alsemeh; Lashin Saad Ali; Mona Mostafa Ahmed; Asmaa Monir Eltaweel; Farha M. Shaikh; Ahmed Behiry; Ahmed El-Sayed Hassan; Deema Kamal Sabir; Dalia Mahmoud Abdelmonem Elsherbini; Sahar K. Ali; Madaniah Omar Zakari; et al. (Tissue and Cell, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Preferential host plants and nesting sites for foam building by the spittlebug, Poophilus costalis Walker (Hemiptera: Aphrophoridae) - Kitherian Sahayaraj; A. Antony Gracy Princess; Wafa Abdullah Hamad Alkherb; Mohammed Ali Alshehri; Lamya Ahmed Alkeridis; Loko Yêyinou Laura Estelle; M. Srinivasan; Shanmugavel Sundar; Ganeshan Petchidurai; Samy Sayed (Phytoparasitica, 2025)

Utilization of thermally treated sludge for the removal of hexavalent chromium from drainage wastewater: a laboratory and field study - T. S. Metwaly; S. I. Ali; M. H. Moustafa; H. M. Shata; S. E. El-Mosalamy; G. O. El-Sayed; A. E. Aboubaraka; A. S. Abdel-Fatah; H. G. El-Shorbagy (International Journal of Environmental Science and Technology, 2025)

Efficacy of Aster chinensis aerial parts metabolites in BALB/c mice model of Imiquimod-induced psoriasis skin inflammation - Mai S. Hendawy; Mona M. Hashem; Ahmed A. Zaki; Mostafa A. Rabie; Nesrine S. El Sayed; Riham Salah El Dine; Ali M. El-Halawany (Inflammopharmacology, 2025)
Using a bioassay-guided fractionation approach, the most potent anti-psoriatic components of Aster squamatus herb, Aster chinensis stalks, and Aster chinensis flowers, cultivated in Egypt, were identified and evaluated against Imiquimod (IMQ)-induced psoriasis in female BALB/c mice and compared to standard drug, mometasone. The topical application of A. chinensis stalk methanolic extract exhibited the strongest anti-psoriatic effects against IMQ-induced psoriasis model, as evidenced by improvements in psoriasis area severity index (PASI) score, histopathological analysis, and spleen index. Further fractionation of A. chinensis stalk methanolic extract using petroleum ether, methylene chloride, ethyl acetate, and n -butanol revealed that the methylene chloride fraction (MCF) was the most potent. Indeed, MCF significantly reduced the PASI score, alleviated histopathological changes, and restored spleen index. Mechanistically, MCF exerted its anti-psoriatic effects by suppressing inflammation, evidenced by decreased TLR-4 gene expression and lower levels of HMGB1 and NFκBp65 protein contents. Additionally, MCF reduced serum levels of pro-inflammatory cytokines interleukin (IL)-1β, IL-6, IL-23, and IL-17 while mitigating oxidative stress through increased superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) content. Notably, the efficacy of MCF was comparable to that of mometasone, with no significant differences observed. In parallel, the chemical profile of the MCF was analyzed using UHPLC-MS/MS techniques in negative and positive ionization full scan modes. MCF of A. chinensis stalk could be used a potential therapeutic agent for psoriasis.

Zinc Oxide Nanoparticles Induced Testicular Toxicity Through Inflammation and Reducing Testosterone and Cell Viability in Adult Male Rats - Dina H. Ahmed; Nadia M. El-Beih; Enas A. El-Hussieny; Wael M. El-Sayed (Biological Trace Element Research, 2025)
Zinc oxide nanoparticles (ZnO NPs) have wide applications in daily life. Therefore, there is growing interest in the potential harmful impacts of these particles on human health. The present study was conducted to investigate the potential toxic effects of ZnO NPs (40 and 70 nm) compared to ZnO on the testes of rats. ZnO NPs were synthesized and characterized by transmission electron microscopy (TEM) and X-ray diffraction (XRD). Adult male rats were randomly divided into four groups ( n = 8): Group I (control), Group II (ZnO) received daily oral administration of ZnO (50 mg/kg), and Groups III and IV received daily oral administration of ZnO NPs of 40 nm or 70 nm at 50 mg/kg, respectively. All treatments continued for 50 consecutive days. ZnO and ZnO NPs reduced body and testis weights, sperm count and motility, serum luteinizing hormone (LH) and testosterone levels, testicular cytochrome p450 17A1 (CYP17A1) and cytochrome p450 1B1 (CYP1B1) concentrations, and the expression of p53 and cdk1 . These treatments elevated testicular myeloperoxidase and serum acid phosphatase activities as well as sperm abnormalities. ZnO NPs reduced LH levels, which decreased CYP17A1 and CYP1B1, resulting in reduced synthesis of testosterone. ZnO NPs enhanced testicular inflammation and reduced cell viability. All these effects were manifested as reduced sperm motility and increased sperm deformities. Compared to macromolecules, nanoparticles exhibited significantly higher toxicity. The larger diameter ZnO NPs had more profound toxicity than the smaller-sized particles.

Comparative Neuroprotective Potential of Nanoformulated and Free Resveratrol Against Cuprizone-Induced Demyelination in Rats - Sara A. M. El-Sayed; Ghadha Ibrahim Fouad; Maha Z. Rizk; Hanan H. Beherei; Mostafa Mabrouk (Molecular Neurobiology, 2025)
Demyelination is a frequent yet crippling neurological disease associated with multiple sclerosis (MS). The cuprizone (CZ) model, which causes demyelination through oxidative stress and neuroinflammation, is a popular tool used by researchers to examine this process. The polyphenol resveratrol (RESV) has become a promising neuroprotective agent in seeking for efficient therapies. In a rat model given CZ, we created and examined iron oxide nanoparticles (IONPs) loaded with RESV (IONP-RESV) to see how effective they were as a therapeutic agent against free RESV. According to molecular mechanisms, exposure to CZ resulted in a marked downregulation of myelin proteolipid protein (PLP) expression and an overexpression of the inflammatory markers tumor necrosis factor-α (TNF-α) and S100β, which are indicators of demyelination and neuroinflammation. It is remarkable that these CZ-induced alterations could be reversed by therapy with either RESV or IONP-RESV. Interestingly, IONP-RESV showed even stronger anti-inflammatory activity, as shown by a more noticeable downregulation of TNF-α and S100β expression. These results were confirmed by histopathological examination of the cerebral cortices. Our findings support the better neuroprotective benefits of RESV-loaded IONPs over free RESV in reducing demyelination and neuroinflammation brought on by CZ. Owing to their pro-remyelinating, anti-inflammatory, and antioxidant properties, RESV-loaded IONPs show promise as a neurotherapeutic intervention in the future for neurological diseases such as multiple sclerosis. Graphical Abstract

Physiological and Molecular Responses of Red Amaranth (Amaranthus cruentus L.) and Green Amaranth (Amaranthus hypochondriacus L.) to Salt Stress - Tartil M. Emam; Abd Elaziz M. Hosni; Ahmed Ismail; Ramy G. El-Kinany; Mohammed Hewidy; Hani Saber Saudy; Mohamed M. A. Omar; Mariam T. S. Ibrahim; Shunzhao Sui; Salwa M. El-Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Salinization, as a serious climate change phenomenon, continues to cause critical issues for soils and crops. Abundance of genetic diversity of plants could contribute in solving the impacts of salinity. However, the relations between physiological and molecular traits of plant species need deep investigation and interpretation. Pot experiments were conducted in the greenhouse to investigate the difference in behavior between two amaranth species when they were beforehand subjected to salinity-stress conditions, specifically on some specific physiological and molecular characteristics. After 45 days from transplanting, salt stress was induced using a 150 mM sodium chloride solution. Treatments were arranged in randomized complete block design using three replications. After 0, 2, 6, 10, and 24 h, samples were collected to evaluate physiological data as well as diversity of gene expression. The samples were immediately frozen in liquid nitrogen and stored in -80⁰ C ultralow temperature refrigerators. Findings revealed that the red amaranth species ( Amaranthus cruentus ) was more tolerant to saline stress than the green amaranth species ( Amaranthus hypochondriacus ). Result data revealed that malondialdehyde (MDA) content in the red amaranth increased after 2 h then decreased (after 6 and 10 h) before rising again after 24 h. In the green amaranth, MDA content initially decreased after 2 h before increasing and later decreasing in a zigzag pattern ending in an increase after 24 h. There was an initial steep rise in proline content of green amaranth after 2 h which continued to still rise moderately till 24 h. In the red amaranth the initial rise in proline continued after 2, 6 and 10 h before it stopped. Results also showed that red amaranth gave higher value of superoxide dismutase (SOD) activity as compared with green amaranth in all tested salinity exposure times. The investigation on the expression of four genes assessed through quantitative PCR indicated the efficiency of red amaranth in increasing the expression of SOS1, HKT1, NHX1, and DGR2 genes, which encode adaptation-related proteins under salinity stress. In summary, the current work demonstrated that red amaranth could be an efficient genetic resource in improving salt-tolerant genotypes belonging to Amaranthus genus.

Herbal remedies for oral and dental health: a comprehensive review of their multifaceted mechanisms including antimicrobial, anti-inflammatory, and antioxidant pathways - Mohamed A. Anwar; Ghadir A. Sayed; Dina M. Hal; Mohamed S. Abd El Hafeez; Abdel-Aziz S. Shatat; Aya Salman; Nehal M. Eisa; Asmaa Ramadan; Riham A. El-Shiekh; Shymaa Hatem; Shaza H. Aly (Inflammopharmacology, 2025)
Across diverse cultures, herbal remedies have been used to alleviate oral discomfort and maintain dental hygiene. This review presents studies on herbal remedies with remarkable antimicrobial, anti-inflammatory, antioxidant, anticancer, anticaries, analgesic, and healing properties. The manuscripts demonstrate the depth of scientific inquiry into herbal remedies used for the management of various oral and dental health conditions. These include gingivitis, oral ulcers, mucositis, periodontitis, oral pathogens, carcinoma, xerostomia, and dental caries. Researchers have investigated the phytochemical and pharmacological properties of plant-derived compounds and their extracts evaluated their interactions with oral pathogens and inflammatory processes. The convergence of traditional knowledge and rigorous scientific investigation offers a compelling narrative, fostering a deeper understanding of herbal remedies as viable alternatives to conventional dental interventions. This work has the potential to provide patients with access to gentle, yet effective solutions, and simultaneously offer dental health professionals the opportunity to enrich their knowledge, and ability to provide personalized, holistic care. This review highlights the symbiotic relationship between herbal medicine and scientific understanding, emphasizing the importance of disseminating this knowledge to benefit both practitioners and patients, enabling evidence-based decision-making in dental care. The exploration of herbal remedies offers a promising alternative, potentially mitigating some of these side effects while promoting oral health in a more natural and holistic manner.

Purification and Immobilization of Burkholderia gladioli Cholesterol Oxidase on Calcium Alginate, with Robust Catalytic Stability for Cholesterol Oxidation In Vitro - Ashraf S. A. El-Sayed; Ahmed A. Shindia; Walaa M. El-Badry; Ahmed A. Mostafa; Abdullah A.Al-Ghanayem; Amgad M. Rady (Current Microbiology, 2025)

Hydrocotyle umbellata L.; a natural source of bioactives to mitigate diabetes mellitus and its complications - Sherif A. Hamdy; Mona M. Hashem; Hala M. El Hefnawy; Shadia M. Azzam; El-Sayed A. Aboutabl (Natural Product Research, 2025)

Quantification of heavy metal exposure in a British population cohort links total mercury levels in plasma with skin tissue-specific changes in mitochondrial-related gene expression - Marcel van de Streek; Aminah Tasnim Ali; Julia S. El-Sayed Moustafa; Craig A. Glastonbury; Tim D. Spector; Ana M. Valdes; James F. Staff; Jackie Morton; Alan Hodgkinson; Jordana T. Bell; Kerrin S. Small (Science of The Total Environment, 2025)

Renoprotective effect of berberine in cisplatin-induced acute kidney injury: Role of Klotho and the AMPK/mtor/ULK1/Beclin-1 pathway - Tasneem M. Salah; Mostafa A. Rabie; Nesrine S. El Sayed (Food and Chemical Toxicology, 2025)

Differential effects of liraglutide naltrexone/bupropion, and caloric restriction on metabolic parameters and beta-cell regeneration in type 2 diabetic rat model: role of beta arrestin 1 - Dina H. Merzeban; Amani M. El Amin Ali; Reem O. Hammad; Mohamed H. Elmahdi; Marwa A. Sofi; Rania H. Mahmoud; Sayed M. Metwally; Ahmed M. El Ebiary (Journal of Molecular Histology, 2025)

Berberine-loaded iron oxide nanoparticles alleviate cuprizone-induced astrocytic reactivity in a rat model of multiple sclerosis - Ghadha Ibrahim Fouad; Mostafa Mabrouk; Sara A. M. El-Sayed; Mohamed F. Abdelhameed; Maha Z. Rizk; Hanan H. Beherei (BioMetals, 2025)
Berberine (BBN) is a naturally occurring alkaloid as a secondary metabolite in many plants and exhibits several benefits including neuroprotective activities. However, data on the neuromodulating potential of nanoformulated BBN are still lacking. In the present study, BBN loaded within iron oxide nanoparticles (BBN-IONP) were prepared and characterized by transmission electron microscopy FTIR, X-ray photoelectron spectroscopy particle-size distribution, zeta potential, and HPLC. The remyelinating neuroprotective potential of BBN-IONP relative to free BBN was evaluated against cuprizone (CPZ)-induced neurotoxicity (rats administered 0.2% CPZ powder (w/w) for five weeks). CPZ rats were treated with either free BBN or IONP-BBN (50 mg/kg/day, orally) for 14 days. Cognitive function was estimated using Y-maze. Biochemically, total antioxidant capacity lipid peroxides and reduced glutathione in the brain tissue, as well as, serum interferon-gamma levels were estimated. Moreover, the genetic expression contents of myelin basic protein Matrix metallopeptidase-9 Tumor necrosis factor-α (TNF-α), and S100β were measured. The histopathological patterns and immunohistochemical assessment of Glial Fibrillary Acidic Protein in both cerebral cortex and hippocampus CA1 regions were investigated. CPZ-rats treated with either free BBN or IONP-BBN demonstrated memory restoring, anti-oxidative, anti-inflammatory, anti-astrocytic, and remyelinating activities. Comparing free BBN with IONP-BBN revealed that the latter altered the neuromodulating activities of BBN, showing superior neuroprotective activities of IONP-BBN relative to BBN. In conclusion, both forms of BBN possess neuroprotective potential. However, the use of IONPs for brain delivery and the safety of these nano-based forms need further investigation.

Identification of Components of the Sex Pheromone of the kōwhai Moth, Uresiphita Polygonalis Maorialis, a New Zealand Native Crambid - Ashraf M. El-Sayed; A. R. Gibb (Journal of Chemical Ecology, 2025)
The identification of sex pheromones in native New Zealand moths has been limited, largely due to their minimal pest impact on agricultural ecosystems. The kōwhai moth, Uresiphita polygonalis maorialis , a native crambid, is known for its herbivory on Sophora spp. and Lupinus arboreus leaves. Understanding the chemical ecology of this species is essential for studying its behavior, population dynamics, and ecological interactions. In this study, the female sex pheromone of U. polygonalis maorialis was analyzed using coupled gas chromatography-electroantennogram detection (GC-EAD). This approach identified four antennally active compounds in the female gland extracts. Subsequent gas chromatography-mass spectrometry (GC-MS) and chemical derivatization revealed these compounds to be tetradecyl acetate (14:Ac), (E)-11-tetradecenyl acetate (E11-14:Ac), (Z)-11-tetradecenyl acetate (Z11-14:Ac), and (Z)-11-hexadecenyl acetate (Z11-16:Ac). Field trapping experiments evaluated various combinations of these four EAD-active compounds and (E)-11-hexadecenyl acetate (E11-16:Ac). Results indicated that traps baited with blends containing E11-14:Ac, Z11-14:Ac, and Z11-16:Ac captured significantly more males compared to unbaited delta traps. A blend ratio of 144:84:72 µg (E11-14:Ac: Z11-14:Ac: Z11-16:Ac) proved the most effective, capturing the highest number of males. Male captures were recorded from late November to late February, peaking in late December, suggesting a univoltine population in Canterbury. Among the three tested doses, the 300 µg and 1000 µg doses of the three-component blend were the most effective. The identification of the sex pheromone components of U. polygonalis maorialis provides a valuable tool for monitoring this species, contributing to a deeper understanding of its population densities and distribution within its native range. It also offers insights into the evolutionary development of pheromone communication within the genus, shedding light on species divergence and adaptation.

Enhanced simultaneous voltammetric detection of lead, copper, and mercury using a MIL-101(Cr)-(COOH)2@MWCNTs modified glassy carbon electrode - Osama A.S. Rafea; Ali M. Abdel-Aziz; Mostafa A. Sayed; Reda M. Abdelhameed; Ibrahim H.A. Badr (Analytica Chimica Acta, 2025)

Petrological and geochemical studies of highly fractionated I-type granites at Abu Marwa–Abu Harba area, Northern Eastern Desert, Egypt - Shimaa A. Nasser; Mohamed M. El-Sayed; Hassen I. El Sandouly (Arabian Journal of Geosciences, 2025)

Correction to: Influence of astaxanthin‑enriched Haematococcus pluvialis microalgae on the growth efficacy, immune response, antioxidant capacity, proinflammatory cytokines, and tissue histomorphology of hybrid red tilapia - Elsayed A. A. Eldessouki; Gehad E. Elshopakey; Samia Elbahnaswy; Medhat S. Shakweer; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Amira Mili; Yasmin M. Abd El‑Aziz; Sameh A. Abdelnour; El‑Sayed Hemdan Eissa (Aquaculture International, 2025)

Salinity-dependent effects of integrated biofloc technology on reproductive performance, biological responses, and offspring quality in red tilapia aquaculture - Ghada R. Sallam; Mohammed F. El Basuini; Amal F. Fahmy; Mohamed A. Al-Absawey; Yusuf Jibril Habib; Rahma Ahmed Mustafa; Walied M. Fayed; Abdel-Fattah M. El-Sayed; Akram Ismael Shehata (Aquaculture International, 2025)
The study aims to evaluate the reproductive performance, serum biochemical indices, growth, antioxidant capacity, and immune response of Florida Red Tilapia ( Oreochromis sp.) progeny reared at different salinity levels within biofloc technology (BFT) systems, focusing on egg production, fertilization rates, tolerance to oxidative stress, and offspring performance. Broodstock reared in biofloc systems (BF) were compared to those in clear water (Without biofloc, WBF) across three salinity levels (18, 28, and 36‰) over a 7-month period. The study also assessed the tolerance of fry reared in biofloc systems to direct transfer to high salinity (36‰) without prior acclimatization. A total of 216 females (initial body weight: 182 ± 1.8 g) and 72 males (initial body weight: 201 ± 0.88 g) were randomly assigned to 18 concrete tanks (2 × 6 × 1 m) to investigate the effects of BFT on spawning performance and larval survival under high-salinity conditions. The findings indicated that appropriate salinity (18‰) in BFT systems positively affected reproductive efficiency, enhanced immunological parameters, and improved growth performance, but elevated salinity levels (36‰) led to reduced reproductive success and hindered growth performance. Florida red tilapia thrive in water quality conditions that are within acceptable limits. High salinity environments led to increased dissolved oxygen but reduced pH, especially in BFT ponds. BFT improved reproductive performance, reduced spawning time, and increased egg production. It also improved hatchability, larval quality, and yolk sac absorption. The BFT broodstock showed higher levels of key proteins (total protein, albumin, and globulin) and improved immune parameters, which helped counteract the negative effects of elevated salinity and enhanced their overall health and stress tolerance. In high-salinity environments, offspring in BFT systems showed higher survival rates and growth rates. In conclusion, BFT improves the reproductive performance, growth, and immune response of Florida red tilapia under high salinity. It enhances egg production, hatchability, and larval survival, while also improving water quality and immune function, making it a sustainable solution for tilapia aquaculture in saline environments.

4-octyl itaconate improves water quality, growth, immunity, blood parameters, and disease resistance of Nile tilapia (Oreochromis niloticus) infected with Aeromonas hydrophila - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Rashid Saleh Alngada; Raed Abdul Whed; Nouh Abdulaziz Aljaafari; El-Sayed Hemdan Eissa; Abdelazeem M. Algammal; Mohammad Bodrul Munir; Moaheda E. H. Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Colchicine: A Dual Therapeutic Target for Trichinellosis - Enas Fakhry Abdel Hamed; Afaf A. Taha; Shereen M. Abdel Ghany; Al-Sayed R. Al-Attar; Eman M. Fawzy (Acta Parasitologica, 2025)
Purpose Trichinellosis affects around 11 million people globally. Treatments for this medical condition are limited by adverse effects and resistance, emphasising the importance of effective and safe therapies. Consequentially, we sought to study colchicine’s synergistic effects with atorvastatin or acetazolamide in the treatment of Trichinella spiralis ( T. spiralis) -infected mice. Methods Seventy mice were evenly divided into two groups (a and b) of 35 each. During the intestinal phase, group (a) began therapy on the second day post-infection (dpi) and lasted four days. Group (b) had treatment for four weeks during the muscle phase, beginning on the 12th dpi. While the other five infected groups received atorvastatin, colchicine, acetazolamide, a combination of acetazolamide and colchicine, or none, one group of infected mice received no treatment at all as a negative control. The efficacy was assessed by parasite count, histopathology and scanning electron microscopy. Results Our data revealed that the combination treatment lowered T. spiralis adult worm and larvae counts in infected animals. Moreover, it restored the normal intestinal and muscular architecture, reduced edema, and alleviated inflammation, as demonstrated by reduced inflammatory infiltrate. Scanning electron microscopic examination of adults and larvae verified our findings. Conclusion Adjuvant treatment with colchicine as an antifibrotic can help treat muscle trichinellosis by reducing the production of fibrous tissue. This might help to enhance treatment results by enabling the admission of larvicidal medications and, as a result, reducing the number of larvae in the muscle, which together form the basis of pathology and can be debilitating for the patient.

Biosorbent silver nanoparticles decorated coffee-ground waste composite for cleaning water and antimicrobial applications - Azza A. Al-Ghamdi; Sherif M. Ibrahim; Xingmei Lu; Jiayu Xin; Ibrahim El-Tantawy El-Sayed; Ahmed A. Galhoum; Swelm. Wageh (Environmental Science and Pollution Research, 2025)

In vivo antischistosomal activity profiling and efficacy of niosomal Spirulina platensis and praziquantel combined remedy against murine Schistosoma mansoni infection - Heba Abdel-Tawab; Shrouk E. Al-Sayed; Fatma I. Abo El-Ela; Amina M. Ibrahim; Olfat A. Hammam; Almahy M. El-Mallah (Veterinary Parasitology, 2025)

Correction to: 17β-Estradiol augments the neuroprotective effect of agomelatine in depressive- and anxiety-like behaviors in ovariectomized rats - Yasmine A. El-Khatib; Rabab H. Sayed; Nada A. Sallam; Hala F. Zaki; Mahmoud M. Khattab (Psychopharmacology, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

Dietary supplementation with fermented prebiotics and probiotics can increase growth, immunity, and histological alterations in Pacific whiteleg shrimp (Litopenaeus vannamei) challenged with Vibrio parahaemolyticus - El-Sayed Hemdan Eissa; Heba A. Dowidar; Nawal Al-Hoshani; Narjes Baazaoui; Naheda M. Alshammari; Safia M. A. Bahshwan; Zulhisyam Abdul Kari; Saadiah Ibrahim; Mohammad Bodrul Munir; Ammar AL-Farga; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2025)

UV-A-induced oxidative stress and immunotoxicity in African catfish (Clarias gariepinus): the bioremediation potential of Spirulina platensis for aquaculture - Mohamed Hamed; Carlos E. Monteiro; Rashad E. M. Said; Mostafa A. Abdel-Maksoud; Taghreed N. Almanaa; Mervat Naguib; Hanem S. Abdel-Tawab; Alaa Osman; Jae-Seong Lee; Alaa El-Din H. Sayed (Aquaculture International, 2025)

Impacts of climate change and black sand on Red Sea, Egypt. A comprehensive review - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Mohamed Abd El-Aal; Sobhi M. Ghoneim; Mohsen Y. Omer; Hamdy A.M. Soliman; Eman Saad; Zeinab Bakr; Jae-Seong Lee; Alaa El-Din H. Sayed (Regional Studies in Marine Science, 2024)

Patterns distribution, concentrations and sources of radioactive elements from black sand in the Red Sea coast, Egypt - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Sobhi M. Ghoneim; Eman Saad; Mohamed Abd El-Aal; Alaa El-Din H. Sayed (Journal of Hazardous Materials, 2024)

Synthesis, cytotoxicity, anti-inflammatory, anti-metastatic and anti-oxidant activities of novel chalcones incorporating 2-phenoxy-N-arylacetamide and thiophene moieties: induction of apoptosis in MCF7 and HEP2 cells - Nada S. Ibrahim; Hager Ahmed Sayed; Marwa Sharaky; Hadeer M. Diab; Ahmed H. M. Elwahy; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Eight Novel chalcones were synthesized and their structures were confirmed by different spectral tools. All the prepared compounds were subjected to SRB cytotoxic screening against several cancer cell lines. Compound 5c exerted the most promising effect against MCF7 and HEP2 cells with IC 50 values of 9.5 and 12 µg/mL, respectively. Real-time PCR demonstrated the inhibitory effect of compound 5c on the expression level of Antigen kiel 67 (KI-67), Survivin, Interleukin-1beta ( IL-1B ) , Interleukin-6 ( IL-6 ), Cyclooxygenase-2 (COX-2 ) and Protein kinase B (AKT1) genes. Flow-cytometric analysis of the cell cycle indicated that compound 5c stopped the cell cycle at the G0/G1 and G2/M phases in MCF7 and HEP2 treated cells, respectively. ELISA assay showed that Caspase 8, Caspase 9, P53, BAX, and Glutathione (GSH) were extremely activated and Matrix metalloproteinase 2 (MMP2), Matrix metalloproteinase 9 (MMP9), BCL2, Malondialdehyde (MDA), and IL-6 were deactivated in 5c treated MCF7 and HEP2 cells. Wound healing revealed that chalcone 5c reduced the ability to close the scrape wound and decreased the number of migrating MCF7 and HEP2 cells compared to the untreated cells after 48 h. Theoretical molecular modeling against P53 cancer mutant Y220C and Bcl2 showed binding energies of -22.8 and -24.2 Kcal/mole, respectively, which confirmed our ELISA results.

Retraction Note: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s Disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2024)

Compilation of secondary metabolites produced by fungal strains identified as Aspergillus flavus var. oryzae (formerly Aspergillus oryzae), with a review of biotechnological applications, and computational studies of their anti-COVID-19 activity - Sabrin R. M. Ibrahim; Flavia Pinzari; Shaimaa G. A. Mohamed; Hazem G. A. Hussein; Abdulrahim A. Alzain; Mohammed A. Almogaddam; Ahmed H. E. Hassan; Selwan M. El-Sayed; Nada A. S. O. AlGhamdi; Gamal A. Mohamed (Mycological Progress, 2024)

Soil–plant Integrative Supplementation with Humic Acid and Antioxidants Improves Growth, Fruit Quality, and Antioxidant Capacity of Cd-stressed Solanum Melongena - Ali A. S. Sayed; Zahra Seoudi; Ashraf Sh. Osman; Wael M. Semida; Mostafa M. Rady; Amr Elkelish; Amr E. M. Mahmoud (Journal of Soil Science and Plant Nutrition, 2024)

Biosynthesis of Silver, Copper, and Their Bi-metallic Combination of Nanocomposites by Staphylococcus aureus: Their Antimicrobial, Anticancer Activity, and Cytotoxicity Effect - Mohsen A. Sayed; Tahany M. A. Abd El-Rahman; H. K. Abdelsalam; Sayed M. S. Abo El-Souad; Rawan Muhammad Shady; Radwa Abdallnasser Amen; Mostafa Ahmed Zaki; Martina Mohsen; Sara Desouky; Samar Saeed; Seif Omar; Asmaa A. H. El-Bassuony (Indian Journal of Microbiology, 2024)
The present study outlines an easy, cheap, and environmentally friendly way to make Staphylococcus aureus -mediated bimetallic silver-copper nanocomposites (Ag/Cu) that can fight cancer and germs. The gram-positive S. aureus synthesized Ag, Cu, and their bi-metallic nanocomposites extracellularly. We aimed to prepare the bimetallic nanocomposite in two different ways, and we compared them in terms of characterization and biological applications. The first one is a bimetallic nanocomposite (Ag/Cu b ) that was made by mixing Ag and Cu metal ions in equal amounts (50:50). Then, the whole mixture was reduced. The second is the after-reduction bimetallic nanocomposite (Ag/Cu a ), in which each metal ion was reduced separately, and then the nanocomposites were mixed (50:50%) during biological applications. Nanocomposites were characterized using UV–visible spectrophotometry, Fourier-transform infrared spectroscopy, dynamic light scattering, and transmission electron microscopy. The results demonstrated that surface plasmon bands were at 320 nm for Ag NPs and 525 nm for Cu NPs, and a shift from these peaks was observed at 290 nm in the Ag/Cu b bimetallic nanocomposite. The synthesized nanocomposites were confirmed to be in the nanoscale with 20, 40, and 80 nm spherical crystals, respectively. Nanocomposites were assayed for their antimicrobial activity against the gram-negative Pseudomonas aeruginosa , the acid-fast Mycobacterium smegmatis , the gram-positive Bacillus cereus, and S. aureus, in addition to three fungal species, which were Aspergillus flavus , A. fumigatus, and Candida albicans . The minimum inhibitory concentration and minimum bactericidal concentration were determined. The Ag/Cua/Cuaetallic nanocomposite was the most potent antimicrobial compound. The anticancer activity of the tested compounds was assayed against the hepatocellular carcinoma cell line (HepG-2). Low cytotoxic activity was recorded in most assayed nanocomposites against the baby hamster kidney cell line (BHK).

Integrated biofloc technology in red tilapia aquaculture: Salinity-dependent effects on water quality, parental stock physiology, reproduction, and immune responses - Ghada R. Sallam; Akram Ismael Shehata; Mohammed F. El Basuini; Yusuf Jibril Habib; Shimaa Henish; Afaf N. Abdel Rahman; Youssef M. Hassan; Walied M. Fayed; Abdel-Fattah M. El-Sayed; Hadir A. Aly (Aquaculture International, 2024)
The study examines the impact of integrated biofloc technology (BFT), different salinity levels, and their combined effects over 90 days on various physiological parameters. The investigation includes growth performance and feed utilization, water quality, the chemical composition of biofloc and fish, digestive enzymes, reproductive performance, stress and biochemical indicators, and antioxidant-immune responses in red tilapia ( Oreochromis spp .) broodstock. The fish were initially weighed (males: n = 270; 104 ± 0.96 g; females: n = 270; 93.2 ± 0.66 g) and subsequently divided into 12 treatment groups (6 for males and 6 for females) spread across 36 separate tanks (3 tanks per treatment; 45 fish per treatment; 15 fish/tank). The treatments involved three salinity levels (18, 28, and 36 ppt) in both clear water (CW) and BFT systems. The outcomes demonstrated that fish in the 36 ppt salinity with BFT treatment demonstrated significant improvements ( P P P

Strengthening growth, digestion, body composition, haemato-biochemical indices, gene expression, and resistance to Fusarium oxysporum infection and histological structure in Oreochromis niloticus by using fructooligosaccharides and β-1,3 glucan mixture - Yasmin M. Abd El-Aziz; Fatima A. Jaber; Nada Mahmoud Nass; Ohaad F. Awlya; Wafaa F. Abusudah; Alaa H. Qadhi; Alya Redhwan; El-Sayed Hemdan Eissa; Hagar Sedeek Dighiesh (Aquaculture International, 2024)
Prebiotics are fibers that promote beneficial gut bacteria and play a pivotal role in enhancing host health. This study delves into the impact of various levels of prebiotics, specifically fructooligosaccharides and β-1,3 glucan (Fβ), on the growth performance, biochemical, hematological parameters, gene expression, histological variations in the internal organs, and disease resistance to Fusarium oxysporum in tilapia ( Oreochromis niloticus ). Two hundred forty Nile tilapia, initially weighing 34.0 ± 0.1 g, were distributed into four groups and given a commercial diet with varying Fβ treatments: control (0 g/kg) (C), T1 (0.5 g/kg), T2 (1.0 g/kg), and T3 (1.5 g/kg) for 70 days. The study revealed significant improvement of the biochemical, hematological, and digestive enzyme activities, as well as histological changes in hepatopancreatic, intestine, and spleen sections with the use of Fβ. Moreover, the expression of innate humoral genes significantly increased ( P F. oxysporum exhibited lower mortality rates in the three treatments supplemented with additive prebiotics ( P

Influence of astaxanthin-enriched Haematococcus pluvialis microalgae on the growth efficacy, immune response, antioxidant capacity, proinflammatory cytokines, and tissue histomorphology of hybrid red tilapia - Elsayed A. A. Eldessouki; Gehad E. Elshopakey; Samia Elbahnaswy; Medhat S. Shakweer; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Amira Mili; Yasmin M. Abd El-Aziz; Sameh A. Abdelnour; El-Sayed Hemdan Eissa (Aquaculture International, 2024)

Dietary multi-strains Bacillus spp. enhanced growth performance, blood metabolites, digestive tissues histology, gene expression of Oreochromis niloticus, and resistance to Aspergillus flavus infection - Hagar Sedeek Dighiesh; Nouf A. Alharbi; Ohaad F. Awlya; Walaa E. Alhassani; Shahira A. Hassoubah; Najah M. Albaqami; Nesreen Aljahdali; Yasmin M. Abd El-Aziz; El-Sayed Hemdan Eissa; Mohammad Bodrul Munir; Salah El-Sayed Sakr (Aquaculture International, 2024)
The present study tested the symbiotic effects of dietary multi-strain Bacillus probiotics (MSB) ( Bacillus licheniformis , B. pumilus , and B. subtilis ) in Nile tilapia ( Oreochromis niloticus ) exposed to Aspergillus flavus infection. Furthermore, this study investigated water quality, growth performance, blood metabolites, histological morphology, immune regulatory genes, and resistance to A. flavus infection. For 70 days, fish ( n = 240) were divided into four groups in triplicate: T0 (control group; MSB0), T1 (1 g/kg, MSB1), T2 (2 g/kg, MSB2), and T3 (3 g/kg, MSB3). The immune response was then assessed by challenging all fish groups with the A. flavus pathogen. The results showed that the rearing water quality, fish growth, and blood parameters, as well as total proteins, albumin, globulins, and amylase activity were significantly ( P P GH ), insulin-like growth factor-1 ( IGF-1 ), insulin-like growth factor receptor-1 ( IGF-1R ), and interleukin-8 ( IL-8 ) were increased in a dose-dependent manner due to MSB dietary inclusion ( P IL-1β ) gene was significantly decreased in MSB groups compared to untreated group ( P Bacillus spp. probiotics exhibited significant modulations in all computed parameters. MSB supplementation improved the pathogenic tolerance of tilapia after change with A. flavus . The integration of growth performance, biochemical, and transcriptomic results confirms that the dietary intervention of multi-strain Bacillus spp. is symbiotic and enhances the benefits for the maintenance of O. niloticus’ health, growth, and digestion. This is achieved by supporting growth genes, reducing inflammatory genes, and enhancing immune-antioxidant resistance to combat A. flavus infection.

In-water Bacillus species probiotic improved water quality, growth, hemato-biochemical profile, immune regulatory genes and resistance of Nile tilapia to Aspergillus flavus infection - El-Sayed Hemdan Eissa; Ekemini Moses Okon; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Heba A. Dowidar; Samia Elbahnaswy; Omaima H. Ezzo; Mohammad Bodrul Munir; Ahmed Jalal Khan Chowdhury; Nadia A. Abd Elghany; Heba H. Mahboub; Moaheda E. H. Eissa; et al. (Aquaculture International, 2024)

Retraction Note: The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2024)

Retraction Note: Cytotoxic effect of chlorpyrifos is associated with activation of Nrf-2/HO-1 system and inflammatory response in tongue of male Wistar rats - Norhan M. El-Sayed; Amal A. M. Ahmed; Manar A. A. Selim (Environmental Science and Pollution Research, 2024)

Challenging the negative perceptions of key stakeholders towards aquaculture sector in Egypt: Evidence-based solutions - Mahmoud M. Abdel-Hady; Thanaa El-Noby; Ahmed M. Nasr-Allah; Seham A. Hashem; Zeinab M. Abdel-Khalek; Shaimaa M. Haggag; Abdel-Fattah M. El-Sayed (Marine Policy, 2024)

Impact of different gastric acid suppressants on chronic unpredictable mild stress-induced cognitive impairment in rats: A possible involvement of gut dysbiosis - Reem M. Eladawy; Lamiaa A. Ahmed; Maha B. Salem; Olfat A. Hammam; Ahmed F. Mohamed; Hesham A. Salem; Rehab M. El-Sayed (Toxicology and Applied Pharmacology, 2024)

6-Paradol exhibits antimicrobial, anti-quorum sensing and anti-virulence capacities on gram-negative bacteria: In vitro and in vivo studies - Hassan M. Okairy; Abdulrahman E. Koshak; Mahmoud A. Elfaky; Hossam M. Abdallah; Gamal A. Mohamed; Sabrin R.M. Ibrahim; Abdulrahim A. Alzain; El-Sayed Khafagy; Azza A.H. Rajab; Wael A.H. Hegazy (South African Journal of Botany, 2024)

Enhancing the nutritional values of egg yolks of laying hens by different dietary sources of omega-3 fatty acids, vitamin e and trace elements - Youssef Attia; Ahmed A.Al Sagan; El-Sayed O.S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Alabdullatif; Rashed A. Alhotan; Mohammed M. Qaid; Vincenzo Tufarelli; Gianluca Pugliese; Khaild A. Asiry; Sameer A. Nagadi; et al. (Livestock Science, 2024)

GIS-Based Flash Flood Hazard Evaluation in Helwan-Atfih Area, Egypt - Safinaz A. A. Mahmoud; Sayed Mosaad; I. Z. El-Shamy; Maysa M. N. Taha (Journal of the Indian Society of Remote Sensing, 2024)

Spectrofluorimetric Protocol for Estimation of Commonly Used Antispasmodic Drotaverine. Fluorescence Quenching Study - Sayed M. Derayea; Nihad A. Mahmoud; Deena A. M. Noureldeen; Tamer Z. Attia (Journal of Fluorescence, 2024)
A fast, simple, accurate, precise, and cheap fluorimetric protocol has been proposed for analysis of a phosphodiesterase-IV inhibitor, namely drotaverine hydrochloride. Fluorimetric protocol is based on estimating the decrease in the eosin Y fluorescence intensity by quantitative addition of drotaverine at pH 3.1 (acetate buffer). An ion pair complex is formed, which leads to quenching in the fluorescence intensity of the dye without need of prior extraction at 534 nm (λ ex . 339 nm). Different reaction perimeters which influence the production of complex (ion pair between drotaverine and eosin) were deeply investigated and optimized. The developed fluorimetric protocol is capable for quantitative estimation of drotaverine in linear range of 0.4 to 2.5 µg mL −1 . After method validation in respect to ICH guidelines, it was applied to determine drotaverine in its commercial preparation. By comparing with other reported method, the developed and validated fluorimetric protocol is capable for estimation of drotaverine in commercial preparation with good accuracy and excellent precision.

Molecular and Clinical Characterization of a Cohort of Autosomal Recessive Sensorineural Hearing Loss in Egyptian Patients - Mohammed M. Sayed-Ahmed; Hala T. El-Bassyouni; Hanan H. Afifi; Mona L. Essawi; Mohamed B. Taher; Mohamed I. Gadelhak; Rehab A. Zaytoun; Ahmed A. Abdelmonem; Nagham M. Elbagoury (Journal of Molecular Neuroscience, 2024)
Hearing loss (HL) is one of the most common health problems worldwide. Autosomal recessive non-syndromic sensorineural hearing loss (ARNSHL) represents a large portion of congenital hereditary HL. Our study was conducted on 13 patients from 13 unrelated families. The majority of patients presented with congenital severe to profound bilateral sensorineural HL. All patients were subjected to detailed family history and three-generation pedigree analysis to exclude any environmental cause and to ensure an autosomal recessive mode of inheritance. Molecular analysis was performed using the whole exome sequencing (WES) technique for the recruited patients. Three variants in the MYO7A and OTOF genes were reported for the first time in patients with ARNSHL (one nonsense, one frameshift, and one splice variant). Ten previously reported variants were detected in seven genes ( GJB2 , MYO15A , BSND , OTOF , CDH23 , SLC26A4 , and TMIE ). They varied between missense, nonsense, frameshift, and splice variants. This study expands the molecular spectrum of two types of autosomal recessive deafness (types 2 and 9).

Effects of alfa lipoic acid and coenzyme Q10 treatment on AFB1-induced oxidative, inflammatory, and DNA damages in rats - Ghadeer M. Albadrani; Ahmed E. Altyar; Osama A. Kensara; Mohie A.M. Haridy; Mohamed Sayed Zaazouee; Alaa Ahmed Elshanbary; Amany A. Sayed; Mohamed M. Abdel-Daim (Toxicon, 2024)

Therapeutic effects of a new bithiophene against aluminum -induced Alzheimer’s disease in a rat model: Pathological and ultrastructural approach - Kholoud AbdEl-Raouf; Monir A. El-Ganzuri; Wael M. El-Sayed (Tissue and Cell, 2024)

Farnesol attenuates cadmium-induced kidney injury by mitigating oxidative stress, inflammation and necroptosis and upregulating cytoglobin and PPARγ in rats - Reem S. Alruhaimi; Emad H.M. Hassanein; Ahmad F. Ahmeda; Ahmed M. Atwa; Sulaiman M. Alnasser; Ghadir A. Sayed; Meshal Alotaibi; Mohammed A. Alzoghaibi; Ayman M. Mahmoud (Tissue and Cell, 2024)

Multiproxy faunal analysis of the middle – upper Eocene deposits in the Fayum area, Egypt: Insights into sequence stratigraphy, trophic conditions, and oxygenation - Abdel Galil A. Hewaidy; Youssef S. Bazeen; Ahmed Samir; El Sayed M. Moneer; Arafa F. El-Balkiemy; Haitham M. Ayyad (Journal of African Earth Sciences, 2024)

Metabolomic profiling of barley extracts obtained via different solvents and evaluation of their anti-inflammatory efficacy - Omneya Eid; Mohamed A. Salem; Osama G. Mohamed; Shahira Ezzat; Ashootosh Tripathi; Menna A. Ewida; Abeer El Sayed; Essam Abdel-Sattar; Wafaa M. Elkady (Food Bioscience, 2024)

Zinc oxide-Ulva lactuca nanocomposite is a robust dietary immunostimulant in the red swamp crayfish (Procambarus clarkii) - Hadeel M. Omar; Sally M. Salaah; Abd El-Halim A. Saad; Ahmed M. Azzam; Magdy T. Khalil; Wael M. El-Sayed (Fish & Shellfish Immunology, 2024)

Towards the preparation of sustainable superplasticizers for geopolymeric pastes via radiation-induced grafting of sulfonic group-bearing monomers onto corn starch - Noha M. Deghiedy; Safaa M.A. El-Gamal; Mohamed Ramadan; Alaa Mohsen; Mahmoud M. Hazem; Mostafa A. Sayed; Fatma M. Helmy; Mona M. Wetwet; Ahmed E. Swilem (Carbohydrate Polymers, 2024)

Metabolomics analysis of Citrus medica var. sarcodactylis (Siebold ex Hoola van Nooten) Swingle and Limonia acidissima Linn. fruits and leaves in perspective to their antimicrobial potential - Abeer M. El Sayed; Eman A. W. El-Abd; Fatma A. Hashim; Mohamed A. Farid; Hoda M. A. H. Shata; Seham S. El Hawary (Natural Product Research, 2024)

The Egyptian Nile estuarine habitats: a review - Khaled M. Abdelsalam; Hermine R. Z. Tadros; Abeer A. Moneer; Mona Kh. Khalil; Samia K. Hamdona; Laila Shakweer; Madelyn N. Moawad; Abeer A. M. El-Sayed; Ghada F. El-Said; Mona M. Ismail; Aida H. Shobier; Shimaa Hosny; et al. (Aquatic Sciences, 2024)
Estuaries are nutrient-rich environments characterized by a gradient in salinity due to the mixing of freshwater and seawater. These bodies of water play vital functions in nature and provide a wide variety of essential ecosystem services. In general, many natural and/or man-made activities have strongly stressed the Egyptian Nile estuarine habitats, as has the water shortage that was expected after the construction of the Grand Ethiopian Renaissance Dam. In recent decades, the Nile Delta has been considered to be one of the most important productive oil-producing petroleum regions due to onshore and offshore gas discoveries alongside gasoline and base oil generation. Up-to-date systematic reviews of the Egyptian estuarine habitats (Rosetta and Damietta) are missing, and the review reported here was undertaken to fill this gap. In this review, we consider the physical, chemical, geological, pollution, and biological parameters of Egyptian Nile estuaries. In this context, our aim is to contribute to a broader understanding of the Egyptian estuarine habitat; moreover, we provide potential warning signals that may aid in estuarine environmental protection. We found that most of the previous studies had focused on the two branches of the Nile or on the marine waters adjacent to these branches, and that only a few studies focused on the estuarine habitats themselves. In most of these previous studies, the salinity gradient of water was reported to be a significant factor in the distribution of the different measured parameters while, in contrast, more recent investigations confirm the importance of potential effluent sources in affecting the distribution of these parameters. We highly recommend that the data reported here be updated in future studies on different environmental aspects.

Curcumin’s effects on growth indices, histological scores, blood metabolites, redox state, immunity, and antioxidant-related genes of red tilapia (Oreochromis sp.) - El-Sayed Hemdan Eissa; Ohaad F. Awlya; Wafaa F. Abusudah; Alaa H. Qadhi; Yasmin M. Abd El-Aziz; Prasob-orn Rinthong; Sameh A. Abdelnour; Mohammad Bodrul Munir; Moaheda E. H. Eissa; Salah El-Sayed Sakr (Aquaculture International, 2024)
Curcumin, a polyphenol, targets multiple signaling molecules and shows activity at the cellular level, supporting its various health benefits. Thereafter, the present study examines the effects of different doses of dietary curcumin on growth indices, feed efficiency, serum metabolites, redox (oxidation) status, immunity, histological assessment, and antioxidant-related genes in red tilapia ( Oreochromis sp, Oreochromis aureus x O. mossambicus ). A total of 1200 red tilapia with an average weight of 19.1±0.03 g were distributed in 12 cement ponds (3×3.5×1m). Each treatment was assigned three pounds ( n =100 replicates). For 60 days, fish were fed baseline diets containing 0, 0.4, 0.6, and 0.8 g of curcumin/kg of diet. The treated fish showed increased body weight and SGR (specific growth rate) compared to the T0 group ( P P P >0.05). The curcumin-treated fish groups improved tissue structure in hepatocytes, pancreatic lumens, hepatic blood sinusoids, and intestine tissue layers, particularly the mucosal layer. The T0.8 group had reduced liver enzymes (AST and ALT) and greater total protein and albumin levels ( P P P P P Oreochromis sp.) diets may improve the fish’s growth, health, tissue composition, and antioxidant response.

Impact of a varied combinatorial mixture of β-1, 3 glucan and fructooligosaccharides on growth performance, metabolism, intestinal morphometry, expression of antioxidant-related genes, immunity, and protection against Vibrio alginolyticus in Red tilapia (Oreochromis niloticus x O. mossambicus) - El-Sayed Hemdan Eissa; Ragaa A. Ahmed; Yasmin M. Abd El-Aziz; Basma M. Hendam; Moaheda E. H. Eissa; Noha I. ElBanna (Aquaculture International, 2024)
Immunosaccharides such as β-glucans and fructooligosaccharide (FOS) strengthen the host’s immune responses. This study examined the influences of three levels of the β-1, 3 glucan-FOS combination on Red tilapia performance. Four diets were prepared: T 0 as a control, while T 0.5 , T 1 , and T 1.5 indicate the addition of β-1, 3 glucan-FOS mixture at 0.5%, 1%, and 1.5%, respectively. Then, 240 red Tilapia ( Oreochromis niloticus x O. mossambicus ) (weight 6.1 ± 0.07gm) were allocated into four groups, and every group was fed tested diets for 56 days. After the feeding trial, growth parameters, erythrogram profile, liver and kidney function testes, glucose, histopathological analysis, and gene expressions for antioxidants, catalase (CAT) and glutathione peroxidase ( GPX ) besides growth hormone (GH) and insulin-like growth factor 1 IGF1-related markers were assessed. Red tilapia fed T 0.5 , T 1 , and T 1.5 exhibited consistent growth, survival rate, and homeostasis compared with the control group. Different supplement concentrations displayed varying levels of responses. The hepatorenal biomarkers (alanine transaminase (ALT = SGPT) and aspartate transaminase (AST = SGOT), alkaline phosphatase (ALP = ALK), urea, and creatinine) and glucose showed a significant reduction in the supplemented groups compared with the control, especially in the T 1 and T 1.5 groups. The intestinal morphometric study revealed that fish group fed on T 1 represented the best result, whereas group T 1.5 , followed by group T 0.5, was moderately treated, compared to the control. The real-time quantitative reverse transcription PCR (qRT-PCR) analysis displayed up-regulated expression of antioxidant and growth-correlated genes in the T 1.5 groups. After 56 days, the β-1,3 glucan-FOS fed groups also exhibited an increase in survival rates compared to the control when challenged with a pathogenic Vibrio alginolyticus. Current findings suggest that inclusion of β-1,3 glucan-FOS in diets could enhance red tilapia biochemical parameters, growth, and protection against pathogenic V. alginolyticus infection.

Extension of ultrafiltered cheese shelf life using edible coatings containing supercritical rosemary, thyme and coriander extracts as antimicrobial agents - Pablo B.R.A. Alloh; Marwa M. El-Said; Hoda S. El-Sayed; Denis A. Baranenko; Tamer M. El-Messery (Food Control, 2024)

Potentiality of Melatonin for Reinforcing Salinity Tolerance in Sorghum Seedlings via Boosting Photosynthetic Pigments, Ionic and Osmotic Homeostasis and Reducing the Carbonyl/Oxidative Stress Markers - Nesma M. Helal; Hani S. Saudy; Maha M. A. Hamada; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Soumya Mukherjee; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Salwa M. El-Sayed; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress has become a major threat to worldwide crop production. Exogenous melatonin (MT) has appeared as a promising treatment against salt stress in several plant species. However, MT effect on the tolerance of sorghum plants under different saline conditions (moderate and severe) remains ambiguous. This study was carried out to explore the impact of MT (0, 50, 100 and 200 µM) as a foliar application on sorghum seedlings grown under moderate and severe saline conditions using sodium chloride, NaCl (75 and 150 µM NaCl). Salinity treatments were applied as solution in sand medium in pots. The results demonstrated that rising salinity level negatively affected plant growth, photosynthetic pigments (chlorophylls and carotenoids), leaf water status and ionic homeostasis (sodium, potassium, and calcium ions). Applied-MT specifically at 100 or 200 µM enhanced the osmotic balance, cell membrane stabilizing and leaf relative water content. These effects were associated with an obvious restriction to the level of hydrogen peroxide, lipid peroxidation (malondialdehyde content) and methylglyoxal. Moreover, antioxidant activities of peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase enzymes were modulated by MT treatments. Molecular docking modeling assessment illustrated top-ranked confirmations between MT and the target antioxidant enzymes. MT forms multiple hydrogen bonds with key amino acid residues for glycine (A: 162), tryptophan (A: 41), leucine (A: 165), tyrosine (A: 235) in the active site of ascorbate peroxidase. The alkyl interactions with leucine (A: 37), arginine (A: 38) and cysteine (A: 168) also contribute to its high affinity. Despite sorghum plant is commonly moderately tolerant to salinity stress, the results of this study confirmed its high sensitivity to a wide range of saline conditions at early growth stages. Melatonin spraying led to improvements in various morphological, physiological and biochemical mechanisms that harmonized together to confer stress resistance to salt-stressed sorghum seedlings.

Chamomile Extract Reduces Cardiac Toxicity in Female Mice with Ehrlich Solid Carcinoma - Hamed A. Abosharaf; Amira M. Farag; Abdel Allem H. Abdel Allem; Ibrahim E. T. El-Sayed; Mohamed A. Akela; Ehab Tousson; Eman H. Kandil (Cell Biochemistry and Biophysics, 2024)

Characteristics and kinetics of thermophilic actinomycetesʼ amylase production on agro-wastes and its application for ethanol fermentation - Mohamed H. El-Sayed; Abd El-Rahman F. Gomaa; Omar Mohammad Atta; Abdallah M. A. Hassane (World Journal of Microbiology and Biotechnology, 2024)

Predict the number of annual generations of Spodoptera Littoralis (Boisd.) Based on future temperature changes - A. A. El-Sayed; M. M. Nada; A. E. Amer (International Journal of Tropical Insect Science, 2024)

Influence of a mixture of oligosaccharides and β-glucan on growth performance, feed efficacy, body composition, biochemical indices, combating Streptococcus iniae infection, and gene expression of Nile tilapia (Oreochromis niloticus) - El-Sayed Hemdan Eissa; Ekemini Moses Okon; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Mohammad Bodrul Munir; Hoda A. Eissa; Sara F. Ghanem; Heba H. Mahboub; Nadia A. Abd Elghany; Hagar Sedeek Dighiesh; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2024)

From Proliferation to Protection: Immunohistochemical Profiling of Cardiomyocytes and Immune Cells in Molly Fish Hearts - Giacomo Zaccone; Doaa M. Mokhtar; Alessio Alesci; Gioele Capillo; Marco Albano; Manal T. Hussein; Marialuisa Aragona; Antonino Germanà; Eugenia R. Lauriano; Ramy K. A. Sayed (Fishes, 2024)
Unlike adult mammalian cardiomyocytes, cardiomyocytes in teleosts display high proliferative capacity throughout adulthood. This study aimed to identify the immunohistochemical profiles of cardiomyocytes and immune cells in the hearts of Molly fish by assessing the immunolabelling expression of key proteins involved in cell proliferation, differentiation, and tissue protection. The cardiac anatomy of Molly fish includes the atrium, ventricle, and bulbus arteriosus. The expression of SOX9, NF-κB, myostatin, and S100 proteins in myocardial cells indicates the proliferative features of the heart in Molly fish. The bulbus arteriosus is characterized by collagenous chambers and smooth muscle cells that express Ach and iba1. The atrium of Molly fish serves as a storage unit for rodlet cells and immune cells. Rodlet cells displayed immunoreactivity to NF-κB, iba1, Olig2, Ach, and S100 proteins, suggesting their roles in the immune response within the heart. Furthermore, telocytes (TCs) have emerged as a significant component of the atrium of Molly fish, expressing Ach, CD68, S100 protein, and iba1. These expressions indicate the involvement of TCs in multiple signaling pathways that contribute to heart architecture. This study delineates the intricate relationship between cardiomyocytes and innate immune cells in Molly fish.

Key aspects of polymeric nanofluids as a new enhanced oil recovery approach: A comprehensive review - Khalaf G. Salem; Mahmoud A. Tantawy; Ahmed A. Gawish; Adel M. Salem; Sayed Gomaa; A.N. El-hoshoudy (Fuel, 2024)

Biodegradation and antimicrobial capability-induced heavy metal resistance of the marine-derived actinomycetes Nocardia harenae JJB5 and Amycolatopsis marina JJB11 - Mohamed H. El-Sayed; Muaz M. Abdellatif; Howayada M. Mostafa; Islam A. Elsehemy; Abd El-Nasser A. Kobisi (World Journal of Microbiology and Biotechnology, 2024)

Cardioprotective role of diacerein in diabetic cardiomyopathy via modulation of inflammasome/caspase1/interleukin1β pathway in juvenile rats - Marwa M. M. Refaie; Hanaa Hassanein Mohammed; Elshymaa A. Abdel-Hakeem; Asmaa M.A. Bayoumi; Zamzam Hassan Mohamed; Sayed Shehata (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Diabetes mellitus is a common metabolic disorder affecting different body organs; one of its serious complications is diabetic cardiomyopathy (DCM). Thus, finding more cardiopreserving agents to protect the heart against such illness is a critical task. For the first time, we planned to study the suspected role of diacerein (DIA) in ameliorating DCM in juvenile rats and explore different mechanisms mediating its effect including inflammasome/caspase1/interleukin1β pathway. Four-week-aged juvenile rats were randomly divided into groups; the control group, diacerein group, diabetic group, and diabetic-treated group. Streptozotocin (45 mg/kg) single intraperitoneal (i.p.) dose was administered for induction of type 1 diabetes on the 1st day which was confirmed by detecting blood glucose level. DIA was given in a dose of 50 mg/kg/day for 6 weeks to diabetic and non-diabetic rats, then we evaluated different inflammatory, apoptotic, and oxidative stress parameters. Induction of DCM succeeded as there were significant increases in cardiac enzymes, heart weights, fasting blood glucose level (FBG), and glycosylated hemoglobin (HbA1c) associated with elevated blood pressure (BP), histopathological changes, and increased caspase 3 immunoexpression. Furthermore, there was an increase of malondialdehyde (MDA), inflammasome, caspase1, angiotensin II, nuclear factor kappa-B (NF-κB), tumor necrosis factor-α (TNFα), and interleukin 1β (IL1β). However, antioxidant parameters such as reduced glutathione (GSH) and total antioxidant capacity (TAC) significantly declined. Fortunately, DIA reversed the diabetic cardiomyopathy changes mostly due to the observed anti-inflammatory, antioxidant, and anti-apoptotic properties with regulation of blood glucose level.DIA has an ability to regulate DCM-associated biochemical and histopathological disturbances.

Synthesis and characterization of new tetrakisphosphonic acid derivatives as FPPS inhibitors and evaluation of their anti-osteoclastogenic potential for prevention of osteoporosis - A. M. A. Hassan; Marwa El-Hussieny; Naglaa F. El-Sayed; Marwa A. Fouad; Ewies F. Ewies; Manal Abdel Fattah Ezzat (Medicinal Chemistry Research, 2024)

Developing green slag/bentonite-based geopolymers modified with meso-porous tungsten oxide: Zeolitic phases, mechanical performance and gamma-radiation mitigation - M. Ramadan; S.M.A. El-Gamal; Mona M. Wetwet; Mostafa A. Sayed; M.M. Hazem; Noha M. Deghiedy; Ahmed E. Swilem; Alaa Mohsen (Applied Clay Science, 2024)

Whiteness and greenness appraisal approaches for quantitative determination of recently approved combination of indacaterol and mometasone via utilization of nuclear magnetic resonance technique - Yomna A. Salem; Selwan M. El-Sayed; Amal A. El-Masry (Sustainable Chemistry and Pharmacy, 2024)

The impact of autologous platelet-rich plasma supplement on Ossimi ram semen quality and fertility: In vivo fertility of freshly diluted and frozen-thawed spermatozoa - Maha S. Salama; Ahmed M. Shehabeldin; Mohey A. Ashour; Lamya Ahmed Alkeridis; Laila A. Al-Shuraym; Samy M. Sayed; Foad Farrag; Mustafa Shukry (Small Ruminant Research, 2024)

Taxonomy, paleoecology, and paleobiogeographical significance of the middle-late Eocene molluscs from the Garet Gehannem section in the Fayoum depression, Egypt - El Sayed M. Moneer; Abdel Galil A. Hewaidy; Haitham M. Ayyad; Ahmed Samir; Mohammed S. Antar; Arafa F. El-Balkiemy; Youssef S. Bazeen (Journal of African Earth Sciences, 2024)

Design and synthesis of indole-based elipticine analogues as topoisomerase IIβ inhibitors - Mardia T. El Sayed; Alaadin E. Sarhan; Huriyyah A. Alturaifi; Selwan M. El-Sayed; Ghada S. Hassan; Nehal A. Hamdy; Shahenda M. El-Messery; Mamdouh M. Ali (Medicinal Chemistry Research, 2024)

The chemical composition and biological activities of plant essential oils against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Nimra Altaf; Muhammad Irfan Ullah; Muhammad Arshad; Muhammad Afzal; Laila A. Al‑Shuraym; Naunain Mehmood; Zafar Hayat; Samy M. Sayed (Journal of Plant Diseases and Protection, 2024)

Combined effect of pantoprazole and mesenchymal stem cells on experimentally induced gastric ulcer: implication of oxidative stress, inflammation and apoptosis pathways - Alaa H. Sayed; Nadia S. Mahmoud; Ola A. M. Mohawed; Hanaa H. Ahmed (Inflammopharmacology, 2024)
Gastric ulcer (GU) is one of the most common diseases of the upper gastrointestinal tract that affects millions of people worldwide. This study aimed to investigate the possible alleviating effect of a combined treatment of pantoprazole (PANTO) and adipose tissue-derived mesenchymal stem cells (ADSCs) in comparison with each treatment alone on the healing process of the experimentally induced GU in rats, and to uncover the involved pathways. Rats were divided into five groups: (1) Control, (2) GU, (3) PANTO, (4) ADSCs and (5) ADSCs + PANTO. Markers of oxidative stress, inflammation and apoptosis were assessed. The current data indicated that PANTO-, ADSCs- and ADSCs + PANTO-treated groups showed significant drop ( p < 0.05 ) in serum advanced oxidation protein products (AOPPs) and advanced glycation end products (AGEPs) along with significant elevation ( p < 0.05 ) in serum TAC versus the untreated GU group. Moreover, the treated groups (PANTO, ADSCs and ADSCs + PANTO) displayed significant down-regulation ( p < 0.05 ) in gastric nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), tumor necrosis factor alpha (TNF-α), cyclooxygenase-2 (COX-2), intercellular adhesion molecule-1 (ICAM-1), matrix metallopeptidase 9 (MMP - 9) and caspase-3 along with significant up-regulation ( p < 0.05 ) in vascular endothelial growth factor (VEGF) and peroxisome proliferator-activated receptor gamma (PPARγ) genes expression compared to the untreated GU group. Immunohistochemical examination of gastric tissue for transforming growth factor β1 (TGF-β1), epidermal growth factor (EGF) and proliferating cell nuclear antigen (PCNA) showed moderate to mild and weak immune reactions, respectively in the PANTO-, ADSCs- and ADSCs + PANTO-treated rat. Histopathological investigation of gastric tissue revealed moderate to slight histopathological alterations and almost normal histological features of the epithelial cells, gastric mucosal layer, muscularis mucosa and submucosa in PANTO-, ADSCs- and ADSCs + PANTO-treated rats, respectively. Conclusively, the co-treatment with ADSCs and PANTO evidenced sententious physiological protection against GU by suppressing oxidative stress, inhibiting inflammation and reducing apoptosis with consequent acceleration of gastric tissue healing process.

Investigation on the key mix design parameters of slag-based geopolymer concrete - Nada M. Nagy; Ismail Amer; El-Sayed A. R. Nasr; Mohamed Kohail (Innovative Infrastructure Solutions, 2024)

Characterization and Cytotoxicity Assessment of Synthesized Palladium (II) Complex-Encapsulated Zinc Oxide Nanoparticles for Cancer Treatment - Ayaat M. Mosleh; Ahmed A. El-Sherif; Anwar A. El-Sayed; Heba M. Fahmy (Cell Biochemistry and Biophysics, 2024)

Dietary Pediococcus acidilactici improved the growth performance, feed utilization, gut microbiota, and disease resistance against Fusarium solani in Pacific white shrimp, Litopenaeus vannamei - Samyah D. Jastaniah; Bothaina A. Alaidaroos; Manal E. Shafi; Rabab M. Aljarari; Yasmin M. Abd El-Aziz; Mohammad Bodrul Munir; Moaheda E. H. Eissa; Ammar AL-Farga; El-Sayed Hemdan Eissa; Radwa M. Said (Aquaculture International, 2024)

Imidacloprid effects on acetylcholinesterase and nicotinic acetylcholine receptor in Apis mellifera. Experimental and molecular modeling approaches - Hussein M. Ali; Basma Abdel-Aty; Walaa El-Sayed; Faiza M. Mariy; Gamal M. Hegazy; Rehab A. Mohamed; Hala M. Zoghly (Chemosphere, 2024)

Occurrence, distribution, and composition of black sand along the Red Sea, Egypt - Mohamed Hamed; Mohamed Abd El-Aal; Mostafa A. Khaled; Sobhi M. Ghoneim; Eman Saad; Jae-Seong Lee; Alaa El-Din H. Sayed (Science of The Total Environment, 2024)

Immunomodulatory and antioxidant properties of Sarcophaga argyrostoma larval hemolymph: utilizing the Biomphalaria alexandrina snail as a model - Alya Mashaal; Asmaa A. Abo Elqasem; Lina A. Abou El-Khashab; Hend M. El-Menyawy; Basma M. Abou El-Nour; Eman M. Abdullah; Asmaa M. Abdalkareem; Rawda A. Al-gebaly; Asmaa M. El-sayed; Ghada R. Mabrok; Rawda R. Mahmoud; Dina A. Ali; et al. (Biologia, 2024)
In recent years, there has been a growing interest in exploring novel natural sources for antioxidant and anti-inflammatory agents, driven by the need for alternative therapeutic strategies with fewer side effects. This study investigates the potential of the Biomphalaria alexandrina snail as a valuable model organism to evaluate the antioxidant and anti-inflammatory properties of Sarcophaga argyrostoma larval hemolymph. The choice of B. alexandrina snails as a model is based on its ecological relevance and physiological similarities to other organisms, supporting well-established use in ecological and physiological research, as well as it provides a valuable platform for such investigations. Ultimately, this study may open avenues for the development of innovative and sustainable therapeutic interventions rooted in the rich biodiversity of the natural world. The experimental design involves the extraction of hemolymph from S. argyrostoma larvae, followed by a comprehensive analysis of its antioxidant capacity and anti-inflammatory effects using adult snails. Various biochemical assays, including total antioxidant capacity, immunomodulatory markers and histological investigation, will be employed to assess the bioactive potential of the hemolymph. The outcomes of this research can be attributed to the identification of the anti-oxidant and anti-inflammatory effects of hemolymph. This effect was observed through the reduction of oxidative stress and proinflammatory mediators, impacting the biological activities of the snails. The study is the first to shed light on the potential benefits of S. argyrostoma larval hemolymph using an animal model, showcasing its ability to mitigate oxidative and inflammatory responses within the biological context of the snails.

Hepatoprotective impact of Nigella sativa silver nanocomposite against genotoxicity, oxidative stress, and inflammation induced by thioacetamide - Fatma M. El-Demerdash; Ansam B. Al Mhanna; Raghda A. El-Sayed; Tarek M. Mohamed; Maha M. Salem (Tissue and Cell, 2024)

Citrus reticulata peel extract mitigates oxidative stress and liver injury induced by abamectin in rats - Ahmed Rahib; Mustafa M. Karhib; Hoda M. Nasr; Raghda A. El-Sayed; Mohamed M. Abdel-Daim; Ali B. Jebur; Fatma M. El-Demerdash (Tissue and Cell, 2024)

Utilizing neem wood waste as a natural dye in the development of bio-based functionalized colored jute fabric - Rony Mia; A Z M Mofasser; Mashooq Ahmad Bhat; Md Imran Howlader; Nadim Ibn Sayed; Md Abu Bakar (Sustainable Chemistry and Pharmacy, 2024)

New antiproliferative 3-substituted oxindoles inhibiting EGFR/VEGFR-2 and tubulin polymerization - Hend A. A. Ezelarab; Taha F. S. Ali; Samar H. Abbas; Ahmed M. Sayed; Eman A. M. Beshr; Heba A. Hassan (Molecular Diversity, 2024)
New 3-substituted oxindole derivatives were designed and synthesized as antiproliferative agents. The antiproliferative activity of compounds 6a–j was evaluated against 60 NCI cell lines. Among these tested compounds, compounds 6f and 6g showed remarkable antiproliferative activity, specifically against leukemia and breast cancer cell lines. Compound 6f was the most promising antiproliferative agent against MCF-7 (human breast cancer) with an IC 50 value of 14.77 µM compared to 5-fluorouracil (5FU) (IC 50 = 2.02 µM). Notably, compound 6f hampered receptor tyrosine EGFR fundamentally with an IC 50 value of 1.38 µM, compared to the reference sunitinib with an IC 50 value of 0.08 µM. Moreover, compound 6f afforded anti-tubulin polymerization activity with an IC 50 value of 7.99 µM as an outstanding observable activity compared with the reference combretastatin A4 with an IC 50 value of 2.64 µM. In silico molecular-docking results of compound 6f in the ATP-binding site of EGFR agreed with the in vitro results. Besides, the investigation of the physicochemical properties of compound 6f via the egg-boiled method clarified good lipophilicity, GIT absorption, and blood–brain barrier penetration properties.

Neuroprotective potential of Erigeron bonariensis ethanolic extract against ovariectomized/D-galactose-induced memory impairments in female rats in relation to its metabolite fingerprint as revealed using UPLC/MS - Weam W. Ibrahim; Rabab H. Sayed; Mohamed F. Abdelhameed; Enayat A. Omara; Mahmoud I. Nassar; Noha F. Abdelkader; Mohamed A. Farag; Abdelsamed I. Elshamy; Sherif M. Afifi (Inflammopharmacology, 2024)
Erigeron bonariensis is widely distributed throughout the world's tropics and subtropics. In folk medicine, E. bonariensis has historically been used to treat head and brain diseases. Alzheimer’s disease (AD) is the most widespread form of dementia initiated via disturbances in brain function. Herein, the neuroprotective effect of the chemically characterized E. bonariensis ethanolic extract is reported for the first time in an AD animal model. Chemical profiling was conducted using UPLC–ESI-MS analysis. Female rats underwent ovariectomy (OVX) followed by 42 days of D-galactose (D-Gal) administration (150 mg/kg/day, i.p) to induce AD. The OVX/D-Gal-subjected rats received either donepezil (5 mg/kg/day) or E. bonariensis at 50, 100, and 200 mg/kg/day, given 1 h prior to D-Gal. UPLC–ESI-MS analysis identified 42 chemicals, including flavonoids, phenolic acids, terpenes, and nitrogenous constituents. Several metabolites, such as isoschaftoside, casticin, velutin, pantothenic acid, xanthurenic acid, C18-sphingosine, linoleamide, and erucamide, were reported herein for the first time in Erigeron genus. Treatment with E. bonariensis extract mitigated the cognitive decline in the Morris Water Maze test and the histopathological alterations in cortical and hippocampal tissues of OVX/D-Gal-subjected rats. Moreover, E. bonariensis extract mitigated OVX/D-Gal-induced Aβ aggregation, Tau hyperphosphorylation, AChE activity, neuroinflammation (NF-κBp65, TNF-α, IL-1β), and apoptosis (Cytc, BAX). Additionally, E. bonariensis extract ameliorated AD by increasing α7-nAChRs expression, down-regulating GSK-3β and FOXO3a expression, and modulating Jak2/STAT3/NF-ĸB p65 and PI3K/AKT signaling cascades. These findings demonstrate the neuroprotective and memory-enhancing effects of E. bonariensis extract in the OVX/D-Gal rat model, highlighting its potential as a promising candidate for AD management. Graphical Abstract

Neuroprotective effect of curcumin against experimental autoimmune encephalomyelitis-induced cognitive and physical impairments in mice: an insight into the role of the AMPK/SIRT1 pathway - Mohamed A. Sadek; Mostafa A. Rabie; Nesrine S. El Sayed; Helmy M. Sayed; Esraa A. Kandil (Inflammopharmacology, 2024)
Multiple sclerosis (MS) is an incurable chronic neurodegenerative disease where autoimmunity, oxidative stress, and neuroinflammation collaboration predispose myelin sheath destruction. Interestingly, curcumin, a natural polyphenol, showed a neuroprotective effect in numerous neurodegenerative diseases, including MS. Nevertheless, the influence of curcumin against MS-induced cognitive impairment is still vague. Hence, we induced experimental autoimmune encephalomyelitis (EAE) in mice using spinal cord homogenate (SCH) and complete Freund’s adjuvant, which eventually mimic MS. This study aimed not only to evaluate curcumin efficacy against EAE-induced cognitive and motor dysfunction, but also to explore a novel mechanism of action, by which curcumin exerts its beneficial effects in MS. Curcumin (200 mg/kg/day) efficacy was evaluated by behavioral tests, histopathological examination, and biochemical tests. Concisely, curcumin amended EAE-induced cognitive and motor impairments, as demonstrated by the behavioral tests and histopathological examination of the hippocampus. Interestingly, curcumin activated the adenosine monophosphate (AMP)-activated protein kinase/silent mating type information regulation 2 homolog 1 (AMPK/SIRT1) axis, which triggered cyclic AMP response element-binding protein/brain-derived neurotrophic factor/myelin basic protein (CREB/BDNF/MBP) pathway, hindering demyelination of the corpus callosum. Furthermore, AMPK/SIRT1 activation augmented nuclear factor erythroid 2-related factor 2 (Nrf2), a powerful antioxidant, amending EAE-induced oxidative stress. Additionally, curcumin abolished EAE-induced neuroinflammation by inhibiting Janus kinase 2 /signal transducers and activators of transcription 3 (JAK2/STAT3) axis, by various pathways, including AMPK/SIRT1 activation. JAK2/STAT3 inhibition halts inflammatory cytokines synthesis. In conclusion, curcumin’s neuroprotective effect in EAE is controlled, at least in part, by AMPK/SIRT1 activation, which ultimately minimizes EAE-induced neuronal demyelination, oxidative stress, and neuroinflammation. Graphical Abstract Graphical illustration of putative molecular pathways implicated in the management of EAE by curcumin. Curcumin activates AMPK/SIRT1, which in turn activates multiple pathways that hinder neurodegeneration, oxidative stress, and neuroinflammation. Moreover, curcumin conquers the inflammatory pathway JAK2/STAT3/NF-kβ.

PI3K/AKT signaling activation by roflumilast ameliorates rotenone-induced Parkinson’s disease in rats - Heba A. Farid; Rabab H. Sayed; Marwa El-Sayed El-Shamarka; Omar M. E. Abdel-Salam; Nesrine S. El Sayed (Inflammopharmacology, 2024)
Parkinson’s disease (PD) is the second most common progressive age-related neurodegenerative disorder. Paramount evidence shed light on the role of PI3K/AKT signaling activation in the treatment of neurodegenerative disorders. PI3K/AKT signaling can be activated via cAMP-dependent pathways achieved by phosphodiesterase 4 (PDE4) inhibition. Roflumilast is a well-known PDE4 inhibitor that is currently used in the treatment of chronic obstructive pulmonary disease. Furthermore, roflumilast has been proposed as a favorable candidate for the treatment of neurological disorders. The current study aimed to unravel the neuroprotective role of roflumilast in the rotenone model of PD in rats. Ninety male rats were allocated into six groups as follows: control, rotenone (1.5 mg/kg/48 h, s.c.), L-dopa (22.5 mg/kg, p.o), and roflumilast (0.2, 0.4 or 0.8 mg/kg, p.o). All treatments were administrated for 21 days 1 h after rotenone injection. Rats treated with roflumilast showed an improvement in motor activity and coordination as well as preservation of dopaminergic neurons in the striatum. Moreover, roflumilast increased cAMP level and activated the PI3K/AKT axis via stimulation of CREB/BDNF/TrkB and SIRT1/PTP1B/IGF1 signaling cascades. Roflumilast also caused an upsurge in mTOR and Nrf2, halted GSK-3β and NF-ĸB, and suppressed FoxO1 and caspase-3. Our study revealed that roflumilast exerted neuroprotective effects in rotenone-induced neurotoxicity in rats. These neuroprotective effects were mediated via the crosstalk between CREB/BDNF/TrkB and SIRT1/PTP1B/IGF1 signaling pathways which activates PI3K/AKT trajectory. Therefore, PDE4 inhibition is likely to offer a reliable persuasive avenue in curing PD via PI3K/AKT signaling activation. Graphical Abstract

Nano-selenium impacts on growth performance, digestive enzymes, antioxidant, immune resistance and histopathological scores of Nile tilapia, Oreochromis niloticus against Aspergillus flavus infection - El-Sayed Hemdan Eissa; Walaa K. Bazina; Yasmin M. Abd El-Aziz; Nadia A. Abd Elghany; Wesam A. Tawfik; Monga I. Mossa; Ola Hasan Abd El Megeed; Nadia N. B. Abd El-Hamed; Adel F. El-Saeed; Ehab El-Haroun; Simon J. Davies; Oliver J. Hasimuna; et al. (Aquaculture International, 2024)
The present study examined the impacts of varying amounts of selenium nanoparticles (Se-NPs) as a natural antioxidant and metabolic regulator on growth performance, antioxidant capacity, digestive enzymes and immune resistance of Oreochromis niloticus challenged to Aspergillus flavus infection. For 60 days, fish were fed the experimental diet of 30% crude protein up to apparent satiation three times a day. Se-NPs were added to the control diet at different levels of 0.0 (control), 0.5 (T1), 1.0 (T2) and 1.5 (T3) mg/kg diet to fed monosex Nile tilapia fingerlings with average initial weight (4.5 ± 0.5 g). Fish were randomly distributed in 12 tanks 100 L at a density of 20 fish per tank after 2-week acclimation to represent four treatments in triplicates. The results indicated that the growth indices, feed efficiency and survival rate were significantly enhanced ( P P Aspergillus flavus , a decreasing mortality rate was observed, which clearly shows that selenium nanoparticles boosted the fish’s immune response at T2. The intestinal morphology as villus length, villus width, muscular fibres layer thickness and absorption intestinal zone after challenged with A. flavus infection were considerably enhanced ( P P

Effect of four host plants on the life history and nutritional indices of Spodoptera Littoralis - Rasha M. El-Refaie; El-Sayed H. Shaurub; Ghada E. Abd-Allah; Ahmed A. Ebeid; Zeinab S. Abouelnaga (International Journal of Tropical Insect Science, 2024)
The Egyptian cotton leafworm Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) is a pervasive and highly polyphagous insect pest. As S. littoralis has developed resistance to major classes of conventional insecticides and the use of these insecticides has caused negative impacts on the ecosystems, it is necessary to search for eco-friendly, cost-effective, and sustainable agents to control. This can be achieved by identifying the preferred host plant. The present study aimed at evaluating the impacts of four host plants– castor bean, tomato, potato, and cucumber on the various life-history traits and nutritional indices of S . littoralis . The concentrations of nitrogen, potassium, and phosphorous in the tested host plants were quantified. Newly hatched larvae were divided into four groups. Each group was fed only on one type of the four tested host plants until pre-pupal stage. Then, the life-history traits and nutritional indices were determined. Larvae fed on castor bean showed the highest adult emergence, weight of full-grown larvae, number of eggs per female, and egg-hatch percent, food consumption, relative growth rate, and food utilization efficiencies. Whereas, larvae fed on cucumber showed the lowest egg-hatch percent, food consumption, relative growth rate, and food utilization efficiencies. There was a positive correlation between nitrogen and phosphorous concentrations in the tested host plants and larval weight, with the highest concentrations in castor bean. Castor bean was the most preferred host plant.

Exploiting the role of plant growth promoting rhizobacteria in reducing heavy metal toxicity of pepper (Capsicum annuum L.) - Mohamed T. El-Saadony; El-Sayed M. Desoky; Khaled A. El-Tarabily; Synan F. AbuQamar; Ahmed M. Saad (Environmental Science and Pollution Research, 2024)

Echinacea purpurea root extract mitigates hepatotoxicity, genotoxicity, and ultrastructural changes induced by hexavalent chromium via oxidative stress suppression - Fatma M. El-Demerdash; Mustafa M. Karhib; Nora F. Ghanem; Mohamed M. Abdel-Daim; Raghda A. El-Sayed (Environmental Science and Pollution Research, 2024)
Environmental and occupational exposure to hexavalent chromium (CrVI) is mostly renowned as a possible hepatotoxic in mammals. Echinacea purpurea (L.) Moench, a phenolic-rich plant, is recurrently used for its therapeutic properties. Therefore, this investigation was done to explore whether E. purpurea (EP) root extract would have any potential health benefits against an acute dose of CrVI-induced oxidative damage and hepatotoxicity. Results revealed that GC–MS analysis of EP root extract has 26 identified components with a significant amount of total phenolic and flavonoid contents. Twenty-four Male Wistar rats were divided into four groups: control, EP (50 mg/kg BW/day for 21 days), CrVI (15 mg/kg BW as a single intraperitoneal dosage), and EP + CrVI, respectively. Rats treated with CrVI displayed a remarkable rise in oxidative stress markers (TBARS, H 2 O 2 , PCC), bilirubin, and lactate dehydrogenase activity, and a marked decrease in enzymatic and non-enzymatic antioxidants, transaminases, and alkaline phosphatase activities, and serum protein level. Also, CrVI administration induced apoptosis and inflammation in addition to histological and ultrastructural abnormalities in the liver tissue. The examined parameters were improved significantly in rats pretreated with EP and then intoxicated with CrVI. Conclusively, EP had a potent antioxidant activity and could be used in the modulation of CrVI-induced hepatotoxicity.

Molecular docking, characterization, ADME/toxicity prediction, and anti-ulcer activity of new quercetin derivatives on indomethacin-induced gastric ulcer in mice - Maha B. Salem; Abdulrahman M. Saleh; Sayed H. Seif el-Din; Safia Samir; Olfat A. Hammam; Naglaa M. El-Lakkany (Toxicology and Applied Pharmacology, 2024)

Exploring the antioxidant, anticancer and antimicrobial potential of Amaranthus viridis L. collected from Fayoum depression: Phytochemical, and biological aspects - Mai Sayed Fouad; Mosad A. Ghareeb; Ahmed A. Hamed; Esraa A. Aidy; Jioji Tabudravu; Ahmed M. Sayed; Mohamed A. Tammam; Mai Ali Mwaheb (South African Journal of Botany, 2024)

Sequence stratigraphy of the Paleocene succession in the Kharga Oasis, Western Desert, Egypt: insights from microplankton biostratigraphy and benthic foraminifer paleoenvironments - Youssef S. Bazeen; Abdel Galil A. Hewaidy; Ahmed Samir; El Sayed M. Moneer; Mohamed W. Abd El-Moghny; Haitham M. Ayyad (Palaeoworld, 2024)

New bithiophene derivative attenuated Alzheimer’s disease induced by aluminum in a rat model via antioxidant activity and restoration of neuronal and synaptic transmission - Kholoud AbdEl-Raouf; Hussein S.H. Farrag; Rashed Rashed; Mohamed A. Ismail; Monir A. El-Ganzuri; Wael M. El-Sayed (Journal of Trace Elements in Medicine and Biology, 2024)

Protozoan and helminths infestation of Nile tilapia Oreochromis niloticus and its correlation with certain water quality variables along river Nile in the area of Greater Cairo - Hanaa M.M. El-Khayat; Sara S.M. Sayed; Wafaa A. Mohammed; Al- Shaimaa M. Sadek (Environmental Pollution, 2024)

Histopathological changes and oxidative stress associated with Fascioliasis in bovines - Salma A. Shoulah; Mohamed M. S. Gaballa; Marwa Mohamdy Al-Assas; Sayed A. Saqr; Hattan S. Gattan; Abdelfattah Selim (Tropical Animal Health and Production, 2024)

Impact of Chlorella vulgaris Bioremediation and Selenium on Genotoxicity, Nephrotoxicity and Oxidative/Antioxidant Imbalance Induced by Polystyrene Nanoplastics in African Catfish (Clarias gariepinus) - Shimaa A. Abdelbaky; Zakaria M. Zaky; Doha Yahia; Mohamed H. Kotob; Mohammed A. Ali; Mohammed Aufy; Alaa El-Din H. Sayed (Fishes, 2024)
Contamination of the environment with nano- and microplastic particles exerts a threatening impact on the aquatic ecosystems and sustainable catfish aquaculture. The presence of nanoplastics has been found to have a detrimental impact on both aquatic and terrestrial ecosystems. The present study examines the effect of polystyrene nanoplastics (PS NPs) on the DNA, erythrocytes, oxidative status and renal histology of catfish, in addition to the potential protective effects of Chlorella vulgaris bioremediation and selenium to hinder this effect. Six equal groups of fish were used as follows: Group 1 served as a control group and received water free from PS NPs; Group 2 was exposed to PS NPs at a concentration of 5 mg/L; Group 3 was exposed to PS NPs (5 mg/L) + selenium (1 mg/kg diet); Group 4 was exposed to PS NPs (5 mg/L) + C. vulgaris (25 g/kg diet); Group 5 was supplemented with C. vulgaris (25 g/kg diet); and Group 6 was supplemented with selenium (1 mg/kg diet). The exposure period was 30 days. The results indicated that PS NPs induced oxidative stress by significantly elevating malondialdehyde activities and slightly reducing antioxidant biomarkers, resulting in DNA damage, increased frequency of micronuclei, erythrocyte alterations, and numerous histopathological alterations in kidney tissue. Selenium and C. vulgaris significantly ameliorated the oxidative/antioxidant status, reducing DNA damage, micronucleus frequency, erythrocyte alterations, and improving the morphology of kidney tissue. Nevertheless, further research is needed for a profound understanding of the mechanism behind the toxicity of nano-microplatics in aquatic systems.

Dietary mannan-oligosaccharides enhance hematological and biochemical parameters, reproductive physiology, and gene expression of hybrid red tilapia (Oreochromis niloticus x O. mossambicus) - El-Sayed Hemdan Eissa; Abdel-Fattah M. El-Sayed; Sara F. Ghanem; Hagar Sedeek Dighiesh; Heba E. Abd Elnabi; Basma M. Hendam; Ahmed A. Elleithy; Moaheda E.H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture, 2024)

The role of fenugreek seed extract in alleviating pancreatic toxic effects and altering glucose homeostasis induced by acetamiprid via modulation of oxidative stress, apoptosis, and autophagy - Samah A. El-Nagdy; Yara M. Elfakharany; Manal Mohammad Morsy; Marwa M. Ahmad; Samaa Salah Abd El-Fatah; Eman El-Sayed Khayal (Tissue and Cell, 2024)

Integration of sustainable chemistry frameworks with a single-pot, on-off fluorescence approach for enabling the facile quantification of mosapride; Application to pharmaceutical tablets and content uniformity - Sayed M. Derayea; Fatma F. Mohammed; Ahmed A. Hamad; Khalid M. Badr El-Din (Sustainable Chemistry and Pharmacy, 2024)

Impacts of different levels of vitamin K on the growth performance, hematological parameters, and immunological response of juvenile Nile tilapia (Oreochromis niloticus) - Ahmed F. Abdelhamid; Ahmed G. A. Gewida; Abdel-Fattah M. El-Sayed; Mohamed F. Badran (Aquaculture International, 2024)
The current investigation was carried out to determine the impacts of different levels of vitamin K (VK) on the growth performance, hematological parameters, and immunological response of all-male juveniles of Nile tilapia ( O. niloticus ). VK3 (menadione) was added in five concentrations (0.0, 2.0, 4.0, 8.0, and 12.0 mg kg –1 diet) in five isonitrogenous (30% cp), isocaloric (18.61 MJ kg –1 ) diets. The fish were fed the diets at a daily rate of 3% of their live weight, divided into 3 meals for 60 days. The results implied that supplemental VK did not provide any growth rate improvements and the efficiency of feed utilization over the control diet. Increasing dietary VK above 2 mg kg –1 feed resulted in significant retardation in fish performance and survival rates. Furthermore, supplemental VK up to 2–4 mg kg –1 increased hematological parameters, physiological functions, immune response, antioxidant capacity, and bone mineralization. Further increase in dietary VK resulted in a significant decline or level off in these parameters. Meanwhile, liver function enzymes increased progressively with dietary VK increasing. In conclusion, these findings suggest that supplemental VK maybe not be necessary for Nile tilapia growth performance, whereas about 2–4 mg kg –1 diet is required for other physiological functions. Increasing VK beyond these levels may pose adverse effects on Nile tilapia. However, further long-term studies are required to confirm these results.

Eco-friendly approach to decrease the harmful effects of untreated wastewater on growth, yield, biochemical constituents, and heavy metal contents of carrot (Daucus carota L.) - Abdulrahman Alhashimi; Ayman Abdelkareem; Mohamed A. Amin; Abdelatti I. Nowwar; Amr Fouda; Mohamed A. Ismail; Abeer E. Mustafa; Maha Alharbi; Amr Elkelish; Abdelrahman M. Sayed; Hanan A. Said (Environmental Science and Pollution Research, 2024)

Spirulina platensis ameliorates hepatic oxidative stress and DNA damage induced by aflatoxin B1 in rats - Ahmed E. Altyar; Osama A. Kensara; Ahmed E. Noreldin; Ghadeer M. Albadrani; Fatma M. El-Demerdash; Amany A. Sayed; Marina Piscopo; Zuhair M. Mohammedsaleh; Muath Q. Al-Ghadi; Nehmat Ghaboura; Mohamed M. Abdel-Daim (Toxicon, 2024)

Effect of ambient lead on progesterone and pregnancy-associated glycoprotein 1 and their relationship with abortion in Zaraibi goats: a field study - Abrar F. Mosaad; Sayed M. El-Nakhla; Ferial H. Abd El-Rasoul; Ahmed M. Shehabeldin; Atef A. Ali; Gamal M. Morsy (Tropical Animal Health and Production, 2024)
This study aimed to investigate the impact of ambient lead (Pb) exposure on progesterone (P 4 ) and pregnancy-associated glycoprotein 1 (PAG1) and their relationship with abortion in Egyptian Zaraibi goats ( C. hircus ). To achieve this, 40 female goats (does) were mated with highly fertile male goats, resulting in a total of 28 pregnant goats. Eight of them aborted, and each of the 12 pregnant goats gave birth to one kid, whereas the remaining eight gave birth to twins. The levels of PAG1, P4, and Pb in serum were estimated by enzyme-linked immunosorbent assay (ELISA), radioimmunoassay (RIA), and inductively coupled plasma mass spectrometry (ICP-MS) respectively. Statistically, the repeated measure two-way ANOVA, regression analysis, correlation coefficient, and receiver operating characteristic (ROC) curves were applied. The current data demonstrated that the levels of blood Pb in aborted goats were significantly higher than those in non-aborted goats at the early, mid, and late gestations, and this was followed by significant decreases in serum PAG1 and P 4 . Furthermore, there were substantial inverse associations between blood Pb concentration and levels of PAG1 and P 4 , with markedly negative correlation coefficients of − 0.88 and − 0.77, respectively, in aborted goats. The threshold level of Pb required to cause abortion was ≥ 32.08 μg/dl, but for PAG1 and P 4 were respectively ≤ 0.95 ng/ml and ≤ 0.48 ng/ml. Additionally, threshold levels of ≥ 12.34 ng/ml and ≥ 31.52 ng/ml for P 4 and PAG1, respectively, were needed to deliver twins. In conclusion, pollution-induced increases in Pb bioavailability resulted in dramatic decreases in P 4 and PAG1 levels, leading to abortions. PAG1 and P 4 levels are also key factors in determining whether Zaraibi goats will give birth to twins.

Mechanistic aspects of ameliorative effects of Eicosapentanoic acid ethyl ester on methotrexate-evoked testiculopathy in rats - Noha A. T. Abbas; Shaimaa S. El-Sayed; Samaa Salah Abd El-Fatah; Walaa M. Sarhan; Eman M. A. Abdelghany; Omnia Sarhan; Shireen S. Mahmoud (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Disrupted spermatogenesis and testicular injury are among the devastating outcomes of methotrexate. A major contributor to methotrexate-induced testiculopathy is oxidative damage which triggers apoptosis and altered autophagy responses. Eicosapentaenoic acid ethyl ester (EPA-E) is an antihyperlipidemic derivative of omega-3 fatty acids that exhibited affinity to peroxisome proliferator-activated receptor-γ (PPAR-γ) that possesses both antioxidant and autophagy modulating properties. This is an exploratory study aiming at assessing the effectiveness of EPA-E to alleviate testicular damage induced by methotrexate. The specific exploratory hypothesis of this experiment is: EPA-E administration for 1 week to methotrexate-treated rats reduces testicular damage compared to control rats. As a secondary outcome, we were interested in identifying the implicated mechanism that mediates the action of EPA-E. In adult male Wistar rats, testiculopathy was achieved by a single methotrexate injection (20 mg/kg, ip ). Rats received vehicle, EPA-E (0.3 g/kg/day, po ) alone or with selective PPAR-γ antagonist (bisphenol A diglycidyl ether, BADGE) at 30 mg/kg/day, ip for 1 week. EPA-E recuperated methotrexate-attenuated serum total testosterone while reduced testicular inflammation and oxidative stress, restoring superoxide dismutase (SOD) while reducing malondialdehyde (MDA) and 8–hydroxy–2′-deoxyguanosine (8-OHdG). Methotrexate-induced testicular apoptosis (caspase-3 and p53) was suppressed upon EPA-E treatment. Besides, EPA-E curbed methotrexate-induced abnormal autophagy by downregulating LC3A/B and beclin-1. Interestingly, BADGE-coadministration reversed EPA-E beneficial actions. Collectively, our findings suggest PPAR-γ role in EPA-E-mediated mitigation of methotrexate-evoked testiculopathy via suppression of oxidative stress, apoptosis, as well as abnormal autophagy. Furthermore, EPA-E could be used as a preventive therapy for some testiculopathies mediated by oxidative stress. Graphical Abstract

Echinacea purpurea extract intervention for counteracting neurochemical and behavioral changes induced by bifenthrin - Khaled G. Abdel-Wahhab; Rehab S. Sayed; Doaa G. EL-Sahra; Laila K. Hassan; Ghada M. Elqattan; Fathia A. Mannaa (Metabolic Brain Disease, 2023)
This study was conducted to elucidate the possible protective efficiency of Echinacea purpurea hydroethanolic extract (EchEE) against bifenthrin (BIF)-induced neuro-chemical and behavioral changes in rats. Total phenolics content, reducing power and radical scavenging activity of EchEE were estimated. Four groups of adult male albino rats were used (10 rats each) as follows: 1) Control healthy rats ingested with placebo, 2) Healthy rats orally received EchEE (465 mg/kg/day), 3) Rats intoxicated with BIF (7mg/kg/day) dissolved in olive oil, and 4) Rats co-treated with EchEE (465 mg/kg/day) besides to BIF (7mg/kg/day) intoxication. After 30 days, some neuro-chemical and behavioral tests were assessed. The behavioral tests revealed that rats received BIF exhibited exploratory behavior and spatial learning impairments, memory and locomotion dysfunction, and enhanced anxiety level. Biochemical findings revealed that BIF induced-oxidative stress in the cortex and hippocampus; this was appeared from the significant rise in malondialdehyde (MDA) and nitric oxide (NO) levels, coupled with decreased catalase (CAT), superoxide dismutase (SOD), paraoxonase-1 (PON-1) activities, and reduced glutathione (GSH) level in both brain areas. Also, BIF induced a significant increase caspas-3, tumor necrosis factor alpha (TNF), and interleukin-1beta (IL-1ß) in both areas; dopamine and serotonin levels, and ACh-ase activity were markedly decreased in both areas. Interestingly, treatment of rats with EchEE in combination with BIF resulted in a significant decrease in oxidative stress damage, and modulation of the apoptotic and pro-inflammatory markers. Also, EchEE markedly improved behavioral activities and neurotransmitters level that were impaired by BIF. In conclusion, the present study clearly indicated that EchEE can attenuate brain dysfunction induced by pesticides exposure through preventing the oxidative stress. This may be attributed to its high antioxidant component.

Immune Cell Profiling in the Ovarian Stroma of a Viviparous Fish during the Breeding Season: A Histological and Immunohistochemical Investigation - Ramy K. A. Sayed; Doaa M. Mokhtar; Madeha Ahmed Hashim; Ahmed S. Aly; Giacomo Zaccone; Marco Albano; Alessio Alesci; Nada Abdellah (Fishes, 2023)
The molly fish is a member of viviparous teleosts that are characterized by the fusion of the right and left ovaries during their early embryonic development. This fusion results in a singular and saccular ovary, where the germinal epithelium lines the internal lumen. The present study aimed to identify the immune cells in the ovarian stroma of Molly fish during the breeding season using histological and immunohistochemical analysis. Histological examination of the ovaries displayed oocytes at all different stages of development and degeneration. The ovocoel, a lymph-filled space, remains in the center of the ovary and branches posteriorly, creating the lumen of the gonoduct. The ovarian wall is composed of three layers: the mesothelium, tunica albuginea, and germinal epithelium. The developing ova were held together by the stroma, which consisted of vascular collagenous connective tissue clustered with immune cells. Immunohistochemical analysis revealed the presence of clusters of macrophages expressing APG5, IL-1β, TGF-β, S100, NF-κB, CD68, Iba-1, and Ach. Monocytes demonstrated positive immunoreactivity for both APG5 and IL-1β, whereas dendritic cells expressed only APG5. Furthermore, rodlet cells exhibited immunoreactivity for S100 protein, IL-1β, NF-κB, CD68, Nrf2, Ach, myostatin, SOX9, and Iba-1. In contrast, stem cells displayed immunoreactivity for Nrf2, myostatin, and SOX9. In conclusion, the ovarian stroma of Molly fish demonstrated a notable presence of immune cells, indicating their active involvement in immune reactions.

Epigenetic alterations of miR-155 and global DNA methylation as potential mediators of ochratoxin A cytotoxicity and carcinogenicity in human lung fibroblasts - Taghrid G. Kharboush; Inas A. Ahmed; Amina A. Farag; Tayseir Kharboush; Alaa El-Din H. Sayed; Amal M. Abdel-Kareim; Mohammed Al mohaini; Hend Attia; Refaat A. Eid; Mohamed Samir A. Zaki; Al-Shaimaa M. Al-Tabbakh (Environmental Science and Pollution Research, 2023)
Ochratoxin A (OTA) is a well-known mycotoxin that adversely affects different human cells. Inhalational exposure to OTA and subsequent pulmonary diseases have been previously reported, yet its potential carcinogenicity and underlying molecular mechanisms have not been fully elucidated. This study aimed to evaluate the OTA-induced cytotoxicity and the epigenetic changes underlying its potential carcinogenicity in fetal lung fibroblast (WI-38) cells. OTA cytotoxicity was assessed by MTT assay; RT-qPCR was used to determine the expression of BAX , BCL-2 , TP53 , and miR-155 , while ELISA was used for measuring 5-methyl cytosine percentage to assess global DNA methylation in OTA-treated versus control cells. WI-38 cells demonstrated sensitivity to OTA with IC50 at 22.38 μM. Though BAX and Bcl-2 were downregulated, with low BAX / BCL-2 ratio, and TP53 was upregulated, their fold changes showed decline trend with increasing OTA concentration. A significant dose-dependent miR-155 upregulation was observed, with dynamic time-related decline. Using subtoxic OTA concentrations, a significant global DNA hypermethylation with significant dose-dependent and dynamic alterations was identified. Global DNA hypermethylation and miR-155 upregulation are epigenetic mechanisms that mediate OTA toxicity on WI-38 cells. BAX downregulation, reduced BAX / BCL-2 ratio together with miR-155 upregulation indicated either the inhibition of TP53 -dependent apoptosis or a tissue specific response to OTA exposure. The aforementioned OTA-induced variations present a new molecular evidence of OTA cytotoxicity and possible carcinogenicity in lung fibroblast cells. Graphical Abstract

Eco-friendly and cost-effective adsorbent derived from blast furnace slag with black liquor waste for hazardous remediation - Ahmed H. Naggar; Abdelghaffar Dhmees; Tarek A. Seaf-Elnasr; Kwok Feng Chong; Gomaa A. M. Ali; Hazim M. Ali; Rasmih M. Kh Alshamery; Lubna H. M. AlNahwa; Al-Sayed A. Bakr (Environmental Science and Pollution Research, 2023)

Comparative study on Lake Manzala in Egypt after and before development and purifications: Ecosystem and biomarkers; biochemical, histopathological and immunohistochemical - Hanaa M.M. El-Khayat; Hanan S. Gaber; Noha S. Helal; Khaled M. Zayed; Hassan E. Flefel; Wafaa A. Mohammed; Sara S.M. Sayed (Environmental Pollution, 2023)

Myco-fabricated ZnO nanoparticles ameliorate neurotoxicity in mice model of Alzheimer’s disease via acetylcholinesterase inhibition and oxidative stress reduction - Hanan A. Abd Elmonem; Reham M. Morsi; Doaa S. Mansour; El-Sayed R. El-Sayed (BioMetals, 2023)
Alzheimer’s disease (AD) is one of the primary health problems linked to the decrease of acetylcholine in cholinergic neurons and elevation in oxidative stress. Myco-fabrication of ZnO-NPs revealed excellent biological activities, including anti-inflammatory and acetylcholinesterase inhibitory potentials. This study aims to determine if two distinct doses of myco-fabricated ZnO-NPs have a positive impact on behavioral impairment and several biochemical markers associated with inflammation and oxidative stress in mice that have been treated by aluminum chloride (AlCl 3 ) to induce AD. Sixty male mice were haphazardly separated into equally six groups. Group 1 was injected i.p. with 0.5 ml of deionized water daily during the experiment. Mice in group 2 received AlCl 3 (50 mg/kg/day i.p.). Groups 3 and 4 were treated i.p. with 5 and 10 mg/kg/day of ZnO-NPs only, respectively. Groups 5 and 6 were given i.p. 5 and 10 mg/kg/day ZnO-NPs, respectively, add to 50 mg/kg/day AlCl 3 . Results showed that the AlCl 3 caused an increase in the escape latency time and a reduction in the time spent in the target quadrant, indicating a decreased improvement in learning and memory. Moreover, acetylcholinesterase enzyme (AChE) activity and malondialdehyde (MDA), tumor necrosis factor-alpha (TNF-α), and interleukin 1β (IL-1β) levels were significantly increased, and the content of glutathione (GSH), activities of superoxide dismutase (SOD), catalase (CAT), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), as well as levels of serotonin and dopamine, were decreased in brain tissues only in AlCl 3 treated mice. However, treatment of mice with myco-fabrication of ZnO-NPs at doses of 5 or 10 mg/kg improves learning and memory function through ameliorate all the previous parameters in the AD mice group. The low dose of 5 mg/kg is more effective than a high dose of 10 mg/kg. In accordance with these findings, myco-fabricated ZnO-NPs could enhance memory and exhibit a protective influence against memory loss caused by AlCl 3 .

Quantifying microplastics pollution in the Red Sea and Gulfs of Suez and Aqaba: Insights from chemical analysis and pollution load assessment - Safaa A. Abdel Ghani; Aida H. Shobier; Abeer A.M. El-Sayed; M. A Shreadah; Soha Shabaka (Science of The Total Environment, 2023)

Withdrawal notice to “Seasonal monitoring of the River Nile in the area of Greater Cairo using a combined approach of certain chemical criteria and macroinvertebrates matrices” [Limnologica 103 (2023) 126119] - Hanaa M.M. El-Khayat; Mohamed R. Habib; Wafaa A. Mohammed; Khaled M. Zayed; Sara S.M. Sayed (Limnologica, 2023)

WITHDRAWN: Seasonal monitoring of the River Nile in the area of Greater Cairo using a combined approach of certain chemical criteria and macroinvertebrates matrices - Hanaa M.M. El-Khayat; Mohamed R. Habib; Wafaa A. Mohammed; Khaled M. Zayed; Sara S.M. Sayed (Limnologica, 2023)

A hybrid deep learning model for rainfall in the wetlands of southern Iraq - Fehaid Alqahtani; Mostafa Abotaleb; Alhumaima Ali Subhi; El-Sayed M. El-Kenawy; Abdelaziz A. Abdelhamid; Khder Alakkari; Amr Badr; H. K. Al-Mahdawi; Abdelhameed Ibrahim; Ammar Kadi (Modeling Earth Systems and Environment, 2023)

Cellophane packaging treated with nano silica is superior to polyethylene in reducing stored irradiated flour from Tribolium confusum infestation - T. S. El sayed; S. A. Rizk; R. M. Sayed (International Journal of Tropical Insect Science, 2023)
Most packaged food products are attacked and penetrated by insects. Causing reducing food quality. Since, different ways are investigated for controlling stored-product pests without application of chemical methods. So, the present study included laboratory methods to evaluate the effectiveness of two packaging materials, polyethylene and cellophane with silica nano particles to prevent or minimize the insect infestation and grain wastage resulting by the attack of wheat grain by confused flour beetle, Tribolium confusum . Studies made to determine the protecting capacity of the two packaging materials through assessing some parameters, number of adults infested poly ethelene and cellophane bags, percentage weight loss of grains, the results revealed that cellophane was the better packaging material than polyethelene, so polyethylene was the susceptible packaging material because it had maximum number of holes as a result penetrations by insects into them. Also, treatment the two types with packaging materials with different concentrations of nano silica protect the treated packaging materials from insect infestation and the protection increase with the increase of the concentration of silica nano particles

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Insecticidal activity of brown seaweed (Sargassum latifolium) extract as potential chitin synthase inhibitors: Toxicokinetic and molecular docking approaches - Fatma El-Zahraa A. Abd El-Aziz; Awatief F. Hifney; Mohamed Mohany; Salim S. Al-Rejaie; Artur Banach; Ahmed M. Sayed (South African Journal of Botany, 2023)

Novel palladium(II) and Zinc(II) Schiff base complexes: Synthesis, biophysical studies, and anticancer activity investigation - Heba M. Fahmy; Ayaat M. Mosleh; Anwar A. El-Sayed; Ahmed A. El-Sherif (Journal of Trace Elements in Medicine and Biology, 2023)

Averrhoa carambola L. fruit and stem metabolites profiling and immunostimulatory action mechanisms against cyclosporine induced toxic effects in rat model as analyzed using UHPLC/MS-MS-based chemometrics and bioassays - Nehal S. Ramadan; Nesrin M. Fayek; Magdy M. El-Sayed; Rasha S. Mohamed; Ludger A. Wessjohann; Mohamed A. Farag (Food and Chemical Toxicology, 2023)

Development of Fe3O4/polyvinylalcohol-nanocomposite hydrogel by chemical and irradiation approaches for Sb(III) sorption from acidic medium - H. M. Gayed; B. A. Masry; M. A. Sayed; Ahmed Awadallah-F (Nanotechnology for Environmental Engineering, 2023)

Heavy metals in popularly sold branded cigarettes in Bangladesh and associated health hazards from inhalation exposure - Mehedi Hasan; Md Moazzem Hossain; Shaifa Abrarin; Tapos Kormoker; Md Masum Billah; Md Khurshid Alam Bhuiyan; Md Ahedul Akbor; Sayed M A Salam; Rahat Khan; Kamrun Naher; Mohammed Abdus Salam; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2023)

Hepatic heat shock proteins, antioxidant-related genes, and immunocompetence of heat-stressed broilers in response to short periods of incubation during egg storage and thermal conditioning - Mona A. Hemida; Sayed A. Abdel-Fattah; Mahmoud Madkour; Mohamad M. Aboelenin; Sarah Y.A. Ahmed; Mohamed Shourrap (Journal of Thermal Biology, 2023)

Correction: Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. Khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2023)

Extremophilic bacterial strains as plant growth promoters and biocontrol agents against Pythium ultimum and Rhizocotnia solani - Sayed Abdelaziz; Eman E. Belal; Diana A. Al-Quwaie; Mada F. Ashkan; Fatimah S. Alqahtani; Khaled A. El-Tarabily; Taia A. Abd El-Mageed; Ashwag Shami; Maha M. Nader; Nada F. Hemeda (Journal of Plant Pathology, 2023)

Spirulina platensis extract improves the production and defenses of the common bean grown in a heavy metals-contaminated saline soil - Mostafa M. Rady; Ahmed S. Elrys; Eman Selem; Ahmed A.A. Mohsen; Safaa M.A.I. Arnaout; Ahmed H. El-Sappah; Khaled A. El-Tarabily; El-Sayed M. Desoky (Journal of Environmental Sciences, 2023)

Metabolic Analysis of Methylenetetrahydrofolate Reductase Single Nucleotide Polymorphisms (MTHFR 677C<T and MTHFR 1298A<C), Serum Folate and Vitamin B12 in Neural Tube Defects - Mohammed H. Hassan; Mohamed A. Raslan; Mena Tharwat; Hala M. Sakhr; Eslam El-Sayed El-Khateeb; Shimaa Fathy Sakr; Hesham H. Ameen; Ali R. Hamdan (Indian Journal of Clinical Biochemistry, 2023)

Bromelain mitigates liver fibrosis via targeting hepatic stellate cells in vitro and in vivo - Amany A. Sayed; Amel M. Soliman; Mohamed Marzouk; Faten F. Mohammed; Shreen Desouky (Tissue and Cell, 2023)

Umbelliferone potentiates intestinal protective effect of Lactobacillus Acidophilus against methotrexate-induced intestinal injury: Biochemical and histological study - Emad H.M. Hassanein; Fares E.M. Ali; Manal M. Sayed; Amany Refaat Mahmoud; Fatima A. Jaber; Mohamed H. Kotob; Tarek Hamdy Abd-Elhamid (Tissue and Cell, 2023)

Hematological consequences of polyethylene microplastics toxicity in male rats: Oxidative stress, genetic, and epigenetic links - Amina A. Farag; Heba S. Youssef; Rania E. Sliem; Walaa Bayoumie El Gazzar; Nashwa Nabil; Maha M. Mokhtar; Yasmin M. Marei; Nesma S. Ismail; Shaimaa E. Radwaan; Amira M. Badr; Alaa El-Din Hamid Sayed (Toxicology, 2023)

Multi-step ahead hourly forecasting of air quality indices in Australia: Application of an optimal time-varying decomposition-based ensemble deep learning algorithm - Mehdi Jamei; Mumtaz Ali; Changhyun Jun; Sayed M. Bateni; Masoud Karbasi; Aitazaz A. Farooque; Zaher Mundher Yaseen (Atmospheric Pollution Research, 2023)

Oxidative Stress and Immunopathological Alterations of Clarias gariepinus Exposed to Monocyclic Aromatic Hydrocarbons (BTX) - Alaa El-Din H. Sayed; Hamdy A. M. Soliman; Shaimaa K. Idriss; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Water, Air, & Soil Pollution, 2023)
This study’s goal was to assess the catfish’s response to exposure to monoaromatic petroleum hydrocarbons (benzene, toluene, and xylene) and its recovery after exposure using oxidative stress, histopathological, and immunological changes as biomarkers. Four groups: one as control and other three exposed to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L), respectively, for 30 days and then recovery period for 30 days. The levels of the cortisol, lipid peroxidation, and cytokines (IL-1β, IL-6) increased significantly ( p < 0.05) after exposure to benzene and xylene compared to control. Superoxide dismutase (SOD), total antioxidant capacity (TAC), and acetylcholinstease (Ach) decreased significantly ( p < 0.05) in fishes exposed to benzene only compared to control group. While glutathione-S-transferase (GST) did not show any change in different treatment groups compared to control group. The histopathological signs of liver exposed to benzene, toluene, and xylene displayed aggregation of melanomacrophages, congestion of sinusoids, vacuolar degeneration of hepatocytes, necrotic area with inflammatory cell infiltration, and thrombus of central vein. Kidney exposed to benzene, toluene, and xylene showed dilatation of Bowman’s space with atrophy of glomerular tuft, lyses of RBCs with mononuclear cell infiltration, multifocal area of hemopoietic tissue necrosis, organized thrombus with perivascular hemorrhage, focal inflammatory cellular reaction, renal tubular necrosis, and thrombus of blood vessels. Spleen exposed to benzene, toluene, and xylene showed hyperplasia of lymphoid follicles in white pulp in a mild degree. These lesions appeared to a mild degree or disappeared completely after recovery period to BTX except spleen. In conclusion, monocyclic aromatic hydrocarbons (BTX) are hazardous to fish and the toxicity level was as benzene > xylene > toluene even though after recovery period.

Synergistic effects of graphene oxide grafted with barbituric acid nanocomposite for removal of heavy metals from aqueous solution - Mostafa M. Abdel Wahab; Galal H. Sayed; Ramadan M. Ramadan; Amr H. Mady; Abdelrahman M. Rabie; Ahmed A. Farag; Nabel A. Negm; Eslam A. Mohamed (Nanotechnology for Environmental Engineering, 2023)

Assessment of nest architecture and pollination efficiency of Lasioglossum (Evylaeus) marginatum (Helictidae: Hymenoptera) - Showket A. Dar; Kounser Javeed; Laila A. Al-Shuraym; Samy Sayed; Yendrembam K. Devi; Wajid Hassan; Mohamed Morsi M. Ahmed; Naser A. Alkenani; Ivana Tlak Gajger; James John (Biologia, 2023)

Dietary Effects of Nano Curcumin on Growth Performances, Body Composition, Blood Parameters and Histopathological Alternation in Red Tilapia (Oreochromis sp.) Challenged with Aspergillus flavus - El-Sayed Hemdan Eissa; Bothaina A. Alaidaroos; Samyah D. Jastaniah; Mohammad Bodrul Munir; Manal E. Shafi; Yasmin M. Abd El-Aziz; Walaa K. Bazina; Saadiah binti Ibrahim; Moaheda E. H. Eissa; Marina Paolucci; Fatima S. Alaryani; Nadia N. B. Abd El-Hamed; et al. (Fishes, 2023)
This research examined the role of nano curcumin (NC) on growth performances, body composition, and blood parameters of red tilapia (Oreochromis sp.) challenged with Aspergillus flavus. Fish (5.0 g ± 0.30) were randomly distributed in four equal groups (20 fish per pond in triplicates) and fed various concentrations of NC fortified with 0 (Control), 40 mg/kg (NC1), 50 mg/kg (NC2), and 60 mg/kg diet (NC3) of nano curcumin. After eight weeks of the feeding trial, the fish were challenged with A. flavus for 15 days, and the cumulative mortality was recorded. Fish fed with different concentrations of NC improved significantly (p 0.05) difference between NC2 and NC3 treatments. However, NC3 exhibited higher performances. Fish feed supplemented with NC decreased the mortality rate when challenged with A. flavus. Hence, dietary supplementation of NC enhanced the growth and health status of Oreochromis sp. and protected it from A. flavus infection. This study suggests the optimum inclusion level of NC is a 50–60 mg/kg diet.

Hydrothermal assisted synthesis of hierarchical SnO2 micro flowers with CdO nanoparticles based membrane for energy storage applications - Ehsan Ullah; Muhammad Zia Ullah Shah; Syed Awais Ahmad; Muhammad Sajjad; Shaukat Khan; Fatimah M. Alzahrani; Adel E.M. Yahya; Sayed M. Eldin; Bhargav Akkinepally; A. Shah; Shenghui Guo (Chemosphere, 2023)

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials - Mohamed Sayed Zaazouee; Mahmoud Eleisawy; Amira M. Abdalalaziz; Mahmoud M. Elhady; Omar Adel Ali; Taghreed Mohamed Abdelbari; Sara Mohamed Hasan; Hossam Waleed Almadhoon; Alaa Yehia Ahmed; Alaa Shaban Fassad; Rewan Elgendy; Eman Adnan Abdel-Baset; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19. Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywords/Mesh terms. Only randomized clinical trials (RCTs) that addressed the topic were included. The Cochrane tool was used to assess the studies’ risk of bias, and the data were analyzed using the review manager (RevMan 5.4). We included nine RCTs with 1586 confirmed COVID-19 patients. Vitamin D group showed a significant reduction of intensive care unit (ICU) admission (risk ratio = 0.59, 95% confidence interval (CI) [0.41, 0.84], P = 0.003), and higher change in vitamin D level (standardized mean difference = 2.27, 95% CI [2.08, 2.47], P < 0.00001) compared to the control group. Other studied hospital and laboratory outcomes showed non-significant difference between vitamin D and the control group ( P ≥ 0.05). In conclusion, vitamin D reduced the risk of ICU admission and showed superiority in changing vitamin D level compared to the control group. However, other outcomes showed no difference between the two groups. More RCTs are needed to confirm these results.

Recent updates on thienopyrimidine derivatives as anticancer agents - Menna Tallah M. Sayed; Rasha A. Hassan; Peter A. Halim; Afaf K. El-Ansary (Medicinal Chemistry Research, 2023)
Thienopyrimidine derivatives hold a unique place between fused pyrimidine compounds. They are important and widely represented in medicinal chemistry as they are structural analogs of purines. Thienopyrimidine derivatives have various biological activities. The current review discusses different synthetic methods for the preparation of heterocyclic thienopyrimidine derivatives. It also highlights the most recent research on the anticancer effects of thienopyrimidines through the inhibition of various enzymes and pathways, which was published within the last 9 years. Graphical Abstract

Design and cytotoxic evaluation via apoptotic and antiproliferative activity for novel 11(4-aminophenylamino)neocryptolepine on hepatocellular and colorectal cancer cells - Esraa Tariq Nagy; Abdullah A. S. Ahmed; Elshaymaa I. Elmongy; Saad M. EL-Gendy; Ibrahim Elmadbouh; Ibrahim El Tantawy El Sayed; Mabrouk Attia Abd Eldaim; Ahmed A. El-Gokha (Apoptosis, 2023)

Morphometry, migration rates, and environmental hazards of barchan dunes in the Kharga Depression, Western Desert, Egypt - Mohamed Abdel Wahed; Mohamed A. Hamdan; Sayed Ramadan; Mai F. Gebril; Ahmed M. Abu Khadrah (Arabian Journal of Geosciences, 2023)
Barchan dunes of the Kharga Depression, Western Desert, Egypt, have been assessed in terms of their morphometry, grain size, and migration rate using remote sensing and GIS techniques and field and laboratory work. Thirty-seven sites were chosen along the Kharga dune belt and subdivided into northern, central, and southern sectors. At each site, several barchans were subjected to morphometric measurements (length, width, height, length of eastern and western horns, and length of windward and leeward sides). The rate and direction of 160 barchans were also measured for the period between 2002 and 2018. Grain size analysis was carried out on sand samples taken from the crest of these dunes. Statistically, significant relationships have been found between the morphometric parameters, dune migration, and grain size attributes. The analysis of the morphology of the barchan dunes, their movement, and the nature of sedimentary materials provide essential information for assessing and evaluating their environmental hazards.

In-situ construction of binder-free MnO2/MnSe heterostructure membrane for high-performance energy storage in pseudocapacitors - Qasim Abbas; Abdul Mateen; Sajid Hussain Siyal; Najam Ul Hassan; Asma A. Alothman; Mohamed Ouladsmane; Sayed M. Eldin; Mohd Zahid Ansari; Muhammad Sufyan Javed (Chemosphere, 2023)

Interactive adverse effects of low-density polyethylene microplastics on marine microalga Chaetoceros calcitrans - Hoda H. Senousy; Hanan M. Khairy; Heba S. El-Sayed; Eman R. Sallam; Mohamed A. El-Sheikh; Mostafa E. Elshobary (Chemosphere, 2023)

Oil Spill Identification based on Dual Attention UNet Model Using Synthetic Aperture Radar Images - Amira S. Mahmoud; Sayed A. Mohamed; Reda A. El-Khoriby; Hisham M. AbdelSalam; Ihab A. El-Khodary (Journal of the Indian Society of Remote Sensing, 2023)
Oil spills cause tremendous damage to marine, coastal environments, and ecosystems. Previous deep learning-based studies have addressed the task of detecting oil spills as a semantic segmentation problem. However, further improvement is still required to address the noisy nature of the Synthetic Aperture Radar (SAR) imagery problem, which limits segmentation performance. In this study, a new deep learning model based on the Dual Attention Model (DAM) is developed to automatically detect oil spills in a water body. We enhanced a conventional UNet segmentation network by integrating a dual attention model DAM to selectively highlight the relevant and discriminative global and local characteristics of oil spills in SAR imagery. DAM is composed of a Channel Attention Map and a Position Attention Map which are stacked in the decoder network of UNet. The proposed DAM-UNet is compared with four baselines, namely fully convolutional network, PSPNet, LinkNet, and traditional UNet. The proposed DAM-UNet outperforms the four baselines, as demonstrated empirically. Moreover, the EG-Oil Spill dataset includes a large set of SAR images with 3000 image pairs. The obtained overall accuracy of the proposed method increased by 3.2% and reaches 94.2% compared with that of the traditional UNet. The study opens new development ideas for integrating attention modules into other deep learning tasks, including machine translation, image-based analysis, action recognition, and speech recognition.

Seismic analysis of a full scaled self-supported tower using ambient vibration testing - Ahmed M. A. Sayed; Ahmed H. Yousef; Ghada N. Saudi; Ehab H. A. Hassan (Innovative Infrastructure Solutions, 2023)

UPLC-MS/MS and GC-MS based metabolites profiling of Moringa oleifera seed with its anti- Helicobacter pylori and anti-inflammatory activities - Abeer M. El Sayed; Farghaly A. Omar; Marwa Mostafa Abdel-Aziz Emam; Mohamed A. Farag (Natural Product Research, 2022)

Evaluation of short and long term enrichment of Artemia franciscana with mixed algae or DHA oil emulsion for improving Dicentrarchus labrax larvae aquaculture - Heba S. El-Sayed; Alaa A. El-Dahhar; Samy Y. El-Zaeem; Shimaa A. Shahin; Hanan M. Khairy; Amira S. Elwan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Phytochemical and in silico studies for potential constituents from Centaurium spicatum as candidates against the SARS-CoV-2 main protease and RNA-dependent RNA polymerase - Ahmed E. Allam; Mohamed E. Abouelela; Hamdy K. Assaf; Ahmed M. Sayed; Alaa M. Nafady; Mohamed A. El-Shanawany; Fumihide Takano; Tomihisa Ohta (Natural Product Research, 2022)

The mitigating effect of Spirulina (Arthrospira platensis) on the hemotoxicity of gibberellic acid on juvenile tilapia (Oreochromis niloticus) - Alaa El-Din H. Sayed; Mohamed Hamed; Abdelaziz A. A. El-Sayed; Bruno Nunes; Hamdy A. M. Soliman (Environmental Science and Pollution Research, 2022)
The use of plant growth regulators has led to environmental contamination of water bodies that occur adjacent to agricultural areas. Some of these chemicals are bioactive, not only to plants, but also to non-target exposed biota, namely of the aquatic compartment. Previous work demonstrated the establishment of hepato- and nephrotoxic effects in juvenile tilapia ( Oreochromis niloticus ) exposed via aquatic media to gibberellic acid (GA 3 ), which is among the most used plant growth regulators, in agricultural practices. Here, we investigated the effect of GA 3 on hematological indices, poikilocytosis, nuclear abnormalities, and genotoxic indices measured in Nile tilapia ( Oreochromis niloticus ), as well as the putative protective effects of dietary supplementation of Spirulina ( Arthrospira platensis ). Fish were evenly assorted into 5 groups: group I served as a control, and groups II–V were fed diets supplemented with Spirulina at rates of 0 g/kg, 5 g/kg, 20 g/kg, and 100 g/kg, respectively, for 2 months before being exposed to 150 mg/L GA 3 . The results revealed that GA 3 exposure decreased significantly all hematological indices ( P < 0.05), except leucocytes and mean corpuscular hemoglobin concentration (MCHC), compared to the control group ( P > 0.05). GA 3 exposure increased significantly the percentage of nuclear abnormalities, altered erythrocytes and the percentages of tail DNA, compared to the control group ( P < 0.05). Spirulina supplementation restored the hematological, poikilocytosis, nuclear abnormalities, and the percentages of tail DNA to near normal levels. The 100 g/kg SP treatment was the most effective in attaining such effect, showing concentration-dependency. The present study reinforces our findings of the toxicity of GA 3 on O. niloticus and suggests that the addition of Spirulina to fish diet can mitigate the hemotoxic effects of GA 3 .

Protective efficacy of dietary natural antioxidants on microplastic particles-induced histopathological lesions in African catfish (Clarias gariepinus) - Alaa El-Din H. Sayed; Mervat N. Hana; Mohamed Hamed; Hany M. R. Abdel-Latif; Jae-Seong Lee; Hamdy A. M. Soliman (Environmental Science and Pollution Research, 2022)
Microplastic particles (MPs) are a common environmental pollutant easily ingested by fish in aquaculture. The current study evaluated the protective efficacies of some antioxidant, e.g., lycopene, citric acid, and chlorella, against the toxic effects of MP ingestion by Clarias gariepinus using histopathological biomarkers. Five experimental groups were established, a control group receiving only a standard diet, a group exposed to 500 mg/kg MP concomitant with the standard diet, and three antioxidant groups exposed to MPs plus either lycopene (500 mg/kg), citric acid (30 g/kg), or chlorella (50 g/kg) in the standard diet. After 15 days, fish were sacrificed for histological and histochemical examinations. Histological analysis of the kidney for group 2 (fed 500 mg/kg MPs alone) revealed distributed tissue dissociation, regional glomerular hypertrophy or shrinkage, melanomacrophage accumulation, and expansion of Bowman’s space, while liver tissue exhibited dilation and rupture of the central vein wall, hemorrhage, cytoplasmic vacuolation, and cellular necrosis or apoptosis. Fish exposed to MPs also exhibited connective tissue fiber accumulation around renal blood vessels, renal tubules, the central hepatic vein, hepatic blood sinusoids, and serosal, muscle, and submucosal layers of the intestine. In addition, MP exposure reduced carbohydrate (mainly glycogen) contents in the brush borders and basement membranes of renal tubules, glomeruli, and intestinal tissues as well as in the cytoplasm of hepatocytes. These signs of renal, hepatic, and intestinal histopathology were fully or partially reversed by dietary lycopene, chlorella, or citric acid. Enhancing dietary antioxidants is an effective strategy for preventing MP toxicity in Clarias gariepinus in aquaculture.

Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2022)
The prevalence of obesity and its associated metabolic disorders, along with their healthcare costs, is rising exponentially. Irisin, an adipomyokine, may serve as a critical cross-organ messenger, linking skeletal muscle with adipose tissue and the liver to integrate the energy homeostasis under diet-induced obesity. We aimed to explore the putative role of irisin in the protection against obesity in a postmenopausal rat model by modulating energy expenditure (EE). Bilateral ovariectomy (OVX) was performed. After 3 weeks of recovery, the OVX rats were classified according to their dietary protocol into rats maintained on normal diets (ND) (OVX) or high-fat diet (HFD) groups. The HFD-fed animals were equally divided into OVX/HFD, or irisin-treated OVX/HFD groups. Sham rats, maintained on ND, were selected as the control group. We evaluated anthropometric, EE, and molecular biomarkers of browning and thermogenesis in inguinal white adipose tissue and skeletal muscle, and the activity of the proteins related to mitochondrial long chain fatty acid transport, oxidation, and glycolysis. HFD of OVX further deteriorated the disturbed glucose homeostasis, lipid profile, and the reduced irisin, thermogenic parameters in adipose tissue and skeletal muscle, and EE. Irisin treatment improved the lipid profile and insulin resistance. That was associated with reduced hepatic gluconeogenic enzyme activities and restored hepatic glycogen content. Irisin reduced ectopic lipid infiltration. Irisin augmented EE by activating non-shivering thermogenesis in muscle and adipose tissues and decreasing metabolic efficiency. Our experimental evidence suggests irisin’s use as a potential thermogenic agent, therapeutically targeting obesity in postmenopausal patients. Graphical abstract Irisin modulates the non-shivering thermogenesis in skeletal muscle and adipose tissue in postmenopausal model

Improved weighted ensemble learning for predicting the daily reference evapotranspiration under the semi-arid climate conditions - El-Sayed M. El-kenawy; Bilel Zerouali; Nadjem Bailek; Kada Bouchouich; Muhammed A. Hassan; Javier Almorox; Alban Kuriqi; Marwa Eid; Abdelhameed Ibrahim‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ (Environmental Science and Pollution Research, 2022)

Ni-alginate hydrogel beads for establishing breakthrough curves of lead ions removal from aqueous solutions - Nesreen M. Sami; A. A. Elsayed; M. M. S. Ali; Sayed S. Metwally (Environmental Science and Pollution Research, 2022)
The scientific impact of this work is the protection of the environment from hazardous pollutants using a column technique. Besides its higher stability at working pH and its time persisting, Ni-alginate has a higher ability to remove lead ions compared to the other prepared beads (Sr-alginate, Co-alginate, and Ca-alginate). Also, Ni-alginate possessed a higher removal percent, 93.3%, toward Pb 2+ than the other ions, taking the sorption order of Pb 2+ > Sr 2+ > Co 2+ > Cd 2+ > Zn 2+ . Therefore, this study focused on using Ni-alginate as a selective sorbent for lead ions. Fixed-bed column was employed for the sorption process. The results for that efficiency are presented as breakthrough curves in view of the impact of various parameters; influent flow rate (1.5, 3.0, and 5.0 mL/min), lead concentration (100, 150, and 200 mg/L), and bed depth of sorbent (3.0, 5.0, and 7.0 cm). Breakthrough modeling including Thomas and Yan models was employed. The outcomes indicated that Thomas theory is more applicable. The overall outcomes indicated that Ni-alginate is recommended for selective removal of Pb 2+ from waste solutions.

Fungicidal activities and molecular docking of the marine alga Ulva lactuca and Punica granatum peel extracts on Alternaria tomato spot disease - Elhagag A. Hassan; Awatief F. Hifney; Esmat F. Ali; Ahmed M. Sayed (Environmental Science and Pollution Research, 2022)

Evaluation of energy extraction of PV systems affected by environmental factors under real outdoor conditions - Muhammed A. Hassan; Nadjem Bailek; Kada Bouchouicha; Abdelhameed Ibrahim; Basharat Jamil; Alban Kuriqi; Samuel Chukwujindu Nwokolo; El-Sayed M. El-kenawy (Theoretical and Applied Climatology, 2022)
The global agenda to increase the renewable energy share has driven many countries and entities to harness solar energy from solar photovoltaic (PV) systems. However, the power generation of PV systems is strongly affected by climate conditions. Therefore, the main objective of this study is to analyze and predict the power generation of different PV technologies under arid desert climate conditions on an hourly basis. Two areas have been considered as case studies: Adrar in Algeria and Alice Springs in Australia. A total of nine physical models and input parameter combinations from six different power plants have been used and tested for the suitability of the proposed models for predicting the power yield of PV power plants depending on solar irradiance and other meteorological variables. Then, an ensemble learning technique is applied to improve the performance capabilities of the best-fit input combinations. The results reveal that the global irradiance, ambient air temperature, and relative humidity combination are the most related to the PV power output of all technologies under all-sky conditions and provide effective and efficient performance with the proposed ensemble learning, with an estimated accuracy of over 99%.

Neuroprotective Potential of Intranasally Delivered Sulforaphane-Loaded Iron Oxide Nanoparticles Against Cisplatin-Induced Neurotoxicity - Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Mostafa Mabrouk; Kawkab A. Ahmed; Hanan H. Beherei (Neurotoxicity Research, 2022)
Cisplatin (CIS) is a platinum-based chemotherapeutic drug that is widely used to treat cancer. However, its therapeutic efficiency is limited due to its potential to provoke neurotoxicity. Sulforaphane (SF) is a natural phytochemical that demonstrated several protective activities. Iron oxide nanoparticles (Fe 3 O 4 -NPs) could be used as drug carriers. This study aimed to explore the nanotoxic influence of SF-loaded within Fe 3 O 4 -NPs (N.SF), and to compare the neuroprotective potential of both N.SF and SF against CIS-induced neurotoxicity. N.SF or SF was administrated intranasally for 5 days before and 3 days after a single dose of CIS (12 mg/kg/week, i.p.) on the 6 th day. Neuromuscular coordination was assessed using hanging wire and tail-flick tests. Acetylcholinesterase (AChE) activities and markers of oxidative stress were measured in the brain. In addition, the brain iron (Fe) content was estimated. CIS significantly induced a significant increase in AChE activities and lipid peroxides, and a significant decrement in glutathione (GSH) and nitric oxide (NO) contents. CIS elicited impaired neuromuscular function and thermal hyperalgesia. CIS-induced brains displayed a significant reduction in Fe content. Histopathological examination of different brain regions supported the biochemical and behavioral results. Contradict, treatment of CIS-rats with either N.SF or SF significantly decreased AChE activity, mitigated oxidative stress, and ameliorated the behavioral outcome. The histopathological features supported our results. Collectively, N.SF demonstrated superior neuroprotective activities on the behavioral, biochemical, and histopathological (striatum and cerebral cortex) aspects. N.SF could be regarded as a promising “pre-clinical” neuroprotective agent. Furthermore, this study confirmed the safe toxicological profile of Fe 3 O 4 -NPs.

The provenance and history of Abu Muharak barchan sands (Kharga Depression) inferred from textural, mineralogical, and geochemical perspectives - Sayed Ramadan; Mohamed A. Hamdan; Ahmed M. Abu Khadra; Mohamed Abdel Wahed (Arabian Journal of Geosciences, 2022)
The current study deals with textural, mineralogical, and geochemical characteristics of the barchan dune sands of Abu Muharak dune belts in the Kharga Depression. Abu Muharak is the longest dune belt in the Western Desert of Egypt. Sand samples from 37 sites were texturally, petrologically, and chemically analyzed. Our goals were to interpret the provenance of the sands in terms of grain size, petrology, and geochemistry and correlate these data with the proposed source such as Nubian sandstone, Pleistocene alluvial, and Holocene lacustrine sediments as well as ancient aeolian deposits exposed at the Kharga Depression. The present study concludes that the Moghra sandstone is the main source of the Abu Muharak dune belt with local contributions from Pleistocene alluvial and dune deposits as well as weathered Nubian sandstone in the Kharga Depression.

Essential oils from the leaves and flowers of Leucophyllum frutescens (Scrophulariaceae): phytochemical analysis and inhibitory effects against elastase and collagenase in vitro - Amany A. Thabet; Iriny M. Ayoub; Fadia S. Youssef; Eman Al Sayed; Abdel Nasser B. Singab (Natural Product Research, 2022)

Evaluation of the cytotoxic, anticancer, and genotoxic activities of Acacia nilotica flowers and their effects on N-methyl-N-nitrosourea-induced genotoxicity in mice - Kawthar A. Diab; Maha A. Fahmy; Emad M. Hassan; Sayed A. El-Toumy (Molecular Biology Reports, 2022)
Purpose In this study, two main research objectives were examined: (1) the cytotoxic and anticancer activities of the aqueous methanol extract from Acacia nilotica flowers on three human cancer cells, namely lung A549, breast MCF-7, and leukemia THP-1 cells, and (2) the genotoxic effects of A. nilotica extract and its influence on DNA damage induced by N-methyl-N-nitrosourea (MNU) in mice. Methods Mice were orally treated with A. nilotica extract (200, 500, and 800 mg/kg for 4 days) with or without MNU (80 mg/kg intraperitoneally for 24 h). Results In vitro experiments showed that A549 cells were the most sensitive to A. nilotica extract among the tested cell lines. A. nilotica extract inhibited A549 cell proliferation by blocking the cell cycle at the G 2 /M phase and accumulating apoptotic cells in the sub-G 0 /G 1 phase in A549 cells. In vivo experiments showed that MNU induced positive and negative genotoxicity in bone marrow cells and spermatocytes, respectively. Negative genotoxicity was observed in A. nilotica extract-treated groups only. However, A. nilotica extract (800 mg/kg) remarkably increased comet tail formation in bone marrow cells. Unexpectedly, the absence of antigenotoxicity was observed in three cotreated groups with A . nilotica extract and MNU compared with the MNU-treated group. Astonishingly, cotreatment with MNU and A. nilotica extract at a dose above 200 mg/kg remarkably increased micronucleus and comet tail formation in bone marrow cells compared with the MNU-treated group. Conclusions A. nilotica extract possessed anticancer activity with relative genotoxic effects at high doses.

Combined Effect of Prickly Pear Waste Biochar and Azolla on Soil Fertility, Growth, and Yield of Roselle (Hibiscus sabdariffa L.) Plants - Hassan M. Al-Sayed; Ahmed M. Ali; Mahmoud A. Mohamed; Mostafa F. Ibrahim (Journal of Soil Science and Plant Nutrition, 2022)
Although the use of biochar to promote plant growth has been reported by many researchers, the combined effect of prickly pear waste biochar (BC) and Azolla (AZ) in a field experiment on the roselle plants did yet receive attention. Therefore, the study aims to evaluate the effect of biochar and Azolla extract on the growth, production, and quality of roselle plants. The experiment treatments were in a completely randomized block design with three replicates. Biochar was added at rates of 0, 10, and 20 ton ha −1 and AZ was applied at rates of 0, 3, and 6% in addition to a control treatment. Biochar added at high rate (20 ton ha −1 ) significantly increased the fresh and dry weights of sepals by 27.98 and 35.73%, respectively, compared to the control. The corresponding values were significantly increased by 11.89 and 11.85% over the control when Azolla was added at rate of 6%. The interaction effect of both BC and AZ treatments at high rate significantly increased the fresh and dry weight of sepals by 47.16 and 60.59%, respectively, compared to the control. The interaction effect of BC and AZ realized significant effect on soil properties, growth and yield, as well as pigments of roselle plants. This is a good evident means that BC and AZ applications separately or combined are considered promising materials for sustainable organic agriculture and safety food.

Mapping of soils and land-related environmental attributes in modern agriculture systems using geomatics - Mohamed A. E. AbdelRahman; Eslam Farg; Ahmed M. Saleh; Marwa Sayed; Khaled Abutaleb; Sayed M. Arafat; Mohamed M. Elsharkawy (Sustainable Water Resources Management, 2022)

Flupyradifurone induces transgenerational hormesis effects in the cowpea aphid, Aphis craccivora - Eman A. Fouad; Sherifa A. N. El-Sherif; El-Sayed M. S. Mokbel (Ecotoxicology, 2022)

Hepatotoxic and Neurotoxic Potential of Iron Oxide Nanoparticles in Wistar Rats: a Biochemical and Ultrastructural Study - Mostafa Mabrouk; Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Maha Z. Rizk; Hanan H. Beherei (Biological Trace Element Research, 2022)

Addressing Peroxisome Proliferator-Activated Receptor-gamma in 3-Nitropropionic Acid-Induced Striatal Neurotoxicity in Rats - Riham M. Mansour; Nesrine S. El Sayed; Maha A. E. Ahmed; Ayman E. El-Sahar (Molecular Neurobiology, 2022)
Telmisartan (TEL) is an angiotensin II type 1 receptor blocker and a partial activator of peroxisome proliferator-activated receptor-gamma (PPARγ), which regulates inflammatory and apoptotic pathways. Increasing evidence has demonstrated the PPARγ agonistic property of TEL in several brain disorders. This study aims to explore the neuroprotective impact of TEL in 3-nitropropionic acid (3-NP)-induced neurotoxicity in rats. The PPARγ effect of TEL was affirmed by using the PPARγ agonist pioglitazone (PIO), and the antagonist GW9662. 3-NP led to a significant reduction in body weight alongside motor and cognitive functioning. The striata of the 3-NP-treated rats showed energy-deficit, microglia-mediated inflammatory reactions, apoptotic damage as well as histopathological lesions. PIO and TEL improved motor and cognitive perturbations induced by 3-NP, as confirmed by striatal histopathological examination, energy restoration, and neuronal preservation. Both drugs improved mitochondrial biogenesis evidenced by elevated mRNA expression of PPARγ, PGC-1α, and TFAM, alongside increased striatal ATP and SDH. The mitochondrial effect of TEL was beyond PPARγ activation. As well, their anti-inflammatory effect was attributed to suppression of microglial activation, and protein expression of pS536 p65 NF-κB with marked attenuation of striatal inflammatory mediator's release. Anti-inflammatory cytokine IL-10 expression was concurrently increased. TEL effectively participated in neuronal survival as it promoted phosphorylation of Akt/GSK-3β, further increased Bcl-2 expression, and inhibited cleavage of caspase-3. Interestingly, co-treatment with GW9662 partially revoked the beneficial effects of TEL. These findings recommend that TEL improves motor and cognitive performance, while reducing neuronal inflammation and apoptosis in 3-NP-induced neurotoxicity via a PPARγ-dependent mechanism. Graphical Abstract

The diagnostic accuracy of intraoperative frozen section biopsy for diagnosis of sentinel lymph node metastasis in breast cancer patients: a meta-analysis - Alaa Ahmed Elshanbary; Alaa Abdelsameia Awad; Alaa Abdelsalam; Islam H. Ibrahim; Walid Abdel-Aziz; Youssef Bahaaeldin Darwish; Alaa Saad Isa; Boutheyna Drid; Marwa Gamal Mustafa; Radwa Hamdy Allam; Amira A. Abo Ali; Anas Zakarya Nourelden; et al. (Environmental Science and Pollution Research, 2022)
Sentinel lymph node (SLN) sampling is important for evaluating the nodal stage of breast cancer when the axillary nodes are clinically free of metastasis. The intraoperative frozen section (IFS) of SLN is used for lymph node assessment. This meta-analysis aims to provide evidence about the diagnostic accuracy and the applicability of IFS of SLN in breast cancer patients. Data were collected by searching PubMed, Cochrane, Scopus, and Web of Science electronic databases for trials matching our eligibility criteria. The statistical analysis included the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and pooled studies’ diagnostic odds ratio outcomes. The analyses were conducted using the Open Meta-analyst software. This meta-analysis pooled the results of 110 studies. The overall sensitivity of IFS for SLN metastasis was 74.7%; 95% CI [72.0, 77.2], P < 0.001. It was 31.4% 95% CI [25.2, 38.3], P < 0.001 for the micro-metastasis, and 90.2%; 95% CI [86.5, 93.0], P < 0.001 for the macro-metastasis. The overall specificity was 99.4%; 95% CI [99.2, 99.6], P < 0.001. The overall positive likelihood ratio was 121.4; 95% CI [87.9, 167.6], P < 0.001, and the overall negative likelihood ratio was 0.226; 95% CI [0.186, 0.274], P < 0.001. The overall diagnostic odds ratio of IFS for diagnosing SLN metastasis was 569.5; 95% CI [404.2, 802.4], P < 0.001. The intraoperative frozen section of SLN has good sensitivity for diagnosing breast cancer macro-metastasis. However, the sensitivity is low for micro-metastasis. The specificity is very satisfactory.

Bioprocesses optimization and anticancer activity of camptothecin from Aspergillus flavus, an endophyte of in vitro cultured Astragalus fruticosus - Ashraf S. A. El-Sayed; Rawia A. Zayed; Ashraf F. El-Baz; Wafaa M. Ismaeil (Molecular Biology Reports, 2022)

Spectrofluorimetric Approach for Quantification of Cyclizine in the Presence of its Toxic Impurities in Human Plasma; in silico Study and ADMET Calculations - Michel Y. Fares; Nada S. Abdelwahab; Ghada M. El-Sayed; Maha A. Hegazy; Maha M. Abdelrahman (Journal of Fluorescence, 2022)
Cyclizine (CYZ); an antiemetic compound; is widely misused for its euphoric or hallucinatory effects, either by oral or intravenous routes. The concomitant abuse of CYZ among addicted adolescents contributes to neuromuscular disorders that are life-threatening. Consequently, with the company of 1-Methylpiperazine (MPZ) and diphenylmethanol (DPM, Benzhydrol) as pharmacopoeia-reported CYZ impurities, a novel spectrofluorimetric assay for the detection of CYZ, has been established either in human plasma samples or in its parenteral formulation. The native fluorescence of CYZ has been investigated under various conditions. Different parameters affecting relative fluorescence intensity of CYZ including diluting solvent, surfactant, plasma protein solvent, and pH were studied and optimized. The linearity obtained between the fluorescence intensity at emission wavelength 350 nm after excitation at 244 nm and the corresponding CYZ concentrations was in the range 10–1000 ng/mL for measurement of CYZ either in pure form or in human plasma samples, with a appropriate correlation coefficient (r = 0.9999) and 3.10 ng/mL as the limit of detection and 9.41 ng/mL as the limit of quantitation. The suggested procedure was created and validated in accordance with ICH guidelines for quantification of CYZ either in its pure form or its dosage form, and FDA guidelines for the assay of CYZ in human plasma. Finally, in silico study and ADMET predictions were conducted for the studied drug impurities to estimate their pharmacokinetic behaviors. The results showed that both CYZ impurities have higher cellular permeability and maximum tolerated doses, DPM has higher BBB and CNS permeability than MPZ, while MPZ exceeds DPM in total clearance and volume of distribution. Graphic Abstract

Biochemical, molecular and cytological impacts of alpha-lipoic acid and Ginkgo biloba in ameliorating testicular dysfunctions induced by silver nanoparticles in rats - Hossam G. Tohamy; Mohamed A. Lebda; Kadry M. Sadek; Mohamed S. Elfeky; Yasser S. El-Sayed; Dalia H. Samak; Heba S. Hamed; Tarek K. Abouzed (Environmental Science and Pollution Research, 2022)

Biological and molecular characterization of fEg-Eco19, a lytic bacteriophage active against an antibiotic-resistant clinical Escherichia coli isolate - Shimaa Badawy; Zakaria A. M. Baka; Mohamed I. Abou-Dobara; Ahmed K. A. El-Sayed; Mikael Skurnik (Archives of Virology, 2022)
Characterization of bacteriophages facilitates better understanding of their biology, host specificity, genomic diversity, and adaptation to their bacterial hosts. This, in turn, is important for the exploitation of phages for therapeutic purposes, as the use of uncharacterized phages may lead to treatment failure. The present study describes the isolation and characterization of a bacteriophage effective against the important clinical pathogen Escherichia coli , which shows increasing accumulation of antibiotic resistance. Phage fEg-Eco19, which is specific for a clinical E. coli strain, was isolated from an Egyptian sewage sample. Phage fEg-Eco19 formed clear, sharp-edged, round plaques. Electron microscopy showed that the isolated phage is tailed and therefore belongs to the order Caudovirales , and morphologically, it resembles siphoviruses. The diameter of the icosahedral head of fEg-Eco19 is 68 ± 2 nm, and the non-contractile tail length and diameter are 118 ± 0.2 and 13 ± 0.6 nm, respectively. The host range of the phage was found to be narrow, as it infected only two out of 137 clinical E. coli strains tested. The phage genome is 45,805 bp in length with a GC content of 50.3% and contains 76 predicted genes. Comparison of predicted and experimental restriction digestion patterns allowed rough mapping of the physical ends of the phage genome, which was confirmed using the PhageTerm tool. Annotation of the predicted genes revealed gene products belonging to several functional groups, including regulatory proteins, DNA packaging and phage structural proteins, host lysis proteins, and proteins involved in DNA/RNA metabolism and replication.

Experimental study of thermal characteristics of ZrO2/EG nanofluid for application of heat transfer - Rohinee M. Barai; Devesh Kumar; Atul V. Wankhade; Aamir R. Sayed; Anup A. Junankar (Environmental Science and Pollution Research, 2022)

Comparative efficacy of gamma and microwave radiation in protecting peppermint from infestation by drugstore beetle (Stegobium paniceum) L. - Nilly A. H. Abdelfattah; R. M. Sayed (International Journal of Tropical Insect Science, 2022)

Correction: The use of microbial inoculants for biological control, plant growth promotion, and sustainable agriculture: A review - Ahmed S. M. Elnahal; Mohamed T. El-Saadony; Ahmed M. Saad; El-Sayed M. Desoky; Amira M. El-Tahan; Mostafa M. Rady; Synan F. AbuQamar; Khaled A. El-Tarabily (European Journal of Plant Pathology, 2022)

The use of microbial inoculants for biological control, plant growth promotion, and sustainable agriculture: A review - Ahmed S. M. Elnahal; Mohamed T. El-Saadony; Ahmed M. Saad; El-Sayed M. Desoky; Amira M. El-Tahan; Mostafa M. Rady; Synan F. AbuQamar; Khaled A. El-Tarabily (European Journal of Plant Pathology, 2022)

“Anosmia” the mysterious collateral damage of COVID-19 - Abdulrahman K. Ahmed; Reem Sayad; Islam A. Mahmoud; Aya M. Abd EL-Monem; Salma H. Badry; Islam H. Ibrahim; Mahmoud HR Hafez; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Journal of NeuroVirology, 2022)

2, 3-Dimethylsuccinic acid and fulvic acid attenuate lead-induced oxidative misbalance in brain tissues of Nile tilapia Oreochromis niloticus - Wesam A. Neamatallah; Kadry M. Sadek; Yasser S. El-Sayed; Ebeed A. Saleh; Asmaa F. Khafaga (Environmental Science and Pollution Research, 2022)

Chloride-binders and their effect on the physico-mechanical properties of sulfate-resisting cement (SRC) hardened pastes upon exposure to sea water attack - Mai M. Yousef; Hamdy A. El-Sayed; Ayman M. Kandeel; Mahmoud Gharieb; Ayman A. Abdel Aziz (Environmental Science and Pollution Research, 2022)

Assessment of reproductive toxicity of carbofuran and copper sulfate in male Nile tilapia (Oreochromis niloticus) - Samah S. Oda; El-Sayed M. El-Manakhly; Mohamed A. Abou-Srag; Hossam G. Tohamy (Environmental Science and Pollution Research, 2022)

The promising anti-virulence activity of candesartan, domperidone, and miconazole on Staphylococcus aureus - Amira M. El-Ganiny; Amany I. Gad; Mona A. El-Sayed; Moataz A. Shaldam; Hisham A. Abbas (Brazilian Journal of Microbiology, 2022)

Thermal treatment of Kalabsha kaolin deposits, south of the Western Desert, Egypt: contribution to geopolymer production as green building materials - Mohamed W. Abd El-Moghny; Hatem M. El-Desoky; Abdeen M. El-Nagar; Nabil A. Abd El-Hafez; Hossam K. Sharaka; Sayed A. Abouellaban (Arabian Journal of Geosciences, 2022)
Kaolin samples were collected to study the mineralogical, texture, chemical composition, thermal behavior, and treatment and also the possibility to convert kaolinite mineral into metakaolin and use it as a natural pozzolanic and/or as geopolymer materials. Kaolinite is the main constituent of clay mineral, which related to many of the chemical weathering of parent rocks and complete leaching of alkali elements under warm, humid to semi-arid climatic conditions. However, quartz, anatase, and iron oxide are considered non-clay minerals. Cement substituted by metakaolin under different ratios in the concrete industry was carried out to enhance the physical and mechanical properties of the concrete. The best results are detected at 10% and 15% of cement replacement by metakaolin. Geopolymer production using Metakaolin (MK) was mixed with NaOH and Na 2 O-3SiO 2 to replace the Portland cement in the concrete industry and the obtained results are suitable and match with the green building material concept.

Sunshine duration measurements and predictions in Saharan Algeria region: an improved ensemble learning approach - El-Sayed M. El-kenawy; Abdelhameed Ibrahim; Nadjem Bailek; Kada Bouchouicha; Muhammed A. Hassan; Mehdi Jamei; Nadhir Al-Ansari (Theoretical and Applied Climatology, 2022)

Swimming exercise versus L-carnosine supplementation for Alzheimer’s dementia in rats: implication of circulating and hippocampal FNDC5/irisin - Maha A. Hegazy; Doaa A. Abdelmonsif; Teshreen M. Zeitoun; Norhan S. El-Sayed; Doaa M. Samy (Journal of Physiology and Biochemistry, 2022)

Could Cisplatin Loading on Biosynthesized Silver Nanoparticles Improve Its Therapeutic Efficacy on Human Prostate Cancer Cell Line and Reduce Its In Vivo Nephrotoxic Effects? - Sawsan M. A. El-Sheikh; Nagah Edrees; Hend EL-Sayed; Tarek Khamis; Ahmed Hamed Arisha; Mohamed M. M. Metwally; Naglaa Z. Eleiwa; Azza A. A. Galal (Biological Trace Element Research, 2022)

Bioethanol production from defatted biomass of Nannochloropsis oculata microalgae grown under mixotrophic conditions - Nashwa A. H. Fetyan; Abo El-Khair B. El-Sayed; Fatma M. Ibrahim; Yasser A. Attia; Mahmoud W. Sadik (Environmental Science and Pollution Research, 2022)

New phytoconstituents, anti-microbial and cytotoxic activities of Acacia etbaica Schweinf - Akram M. Kayed; Ezzat A. M. Genady; Hazem A. Kadry; El-Sayed M. Elghaly (Natural Product Research, 2021)

Hepatoprotective effects of phytochemicals berberine and umbelliferone against methotrexate-induced hepatic intoxication: experimental studies and in silico evidence - Abdel-Gawad S. Shalkami; Emad H. M. Hassanein; Ahmed M. Sayed; Wafaa R. Mohamed; Marwa M. Khalaf; Ramadan A. M. Hemeida (Environmental Science and Pollution Research, 2021)

Optical detection of microplastics in water - Ahmet H. Iri; Malek H. A. Shahrah; Ali M. Ali; Sayed A. Qadri; Talha Erdem; Ibrahim T. Ozdur; Kutay Icoz (Environmental Science and Pollution Research, 2021)

Dose-Dependent Cardioprotective Effect of Hemin in Doxorubicin-Induced Cardiotoxicity Via Nrf-2/HO-1 and TLR-5/NF-κB/TNF-α Signaling Pathways - Marwa M. M. Refaie; Sayed Shehata; Randa Ahmed Ibrahim; Asmaa M. A. Bayoumi; Seham A. Abdel-Gaber (Cardiovascular Toxicology, 2021)

Multipotential Trace Metal Concentrations in Soil Associated with the Ecological and Human Health Risk near the Rooppur Nuclear Power Plant, Pabna, Bangladesh - M. Safiur Rahman; M. Mahtab Ali Mollah; M. Rakib-uz- Zaman; Yeasmin N. Jolly; Shirin Akhter; M. Jamiul Kabir; Hirofumi Tazoe; Sayed M. A. Salam (Water, Air, & Soil Pollution, 2021)

Impeding Virulence of Candida albicans by Candesartan and Domperidone - Hisham A. Abbas; Amany I. Gad; Mona A. El-Sayed; Amira M. El-Ganiny (Current Microbiology, 2021)

Solution blowing spinning technology and plasma-assisted oxidation-reduction process toward green development of electrically conductive cellulose nanofibers - Hanadi A. Katouah; Refat El-Sayed; Nashwa M. El-Metwaly (Environmental Science and Pollution Research, 2021)

MoS2-based nanocomposites: synthesis, structure, and applications in water remediation and energy storage: a review - M. I. A. Abdel Maksoud; Ahmed G. Bedir; Mohamad Bekhit; Marwa Mohamed Abouelela; Ramy Amer Fahim; A. S. Awed; Sayed Y. Attia; Said M. Kassem; M. Abd Elkodous; Gharieb S. El-Sayyad; Saad G. Mohamed; Ahmed I. Osman; et al. (Environmental Chemistry Letters, 2021)
The world is currently facing critical water and energy issues due to the growing population and industrialization, calling for methods to obtain potable water, e.g., by photocatalysis, and to convert solar energy into fuels such as chemical or electrical energy, then storing this energy. Energy storage has been recently improved by using electrochemical capacitors and ion batteries. Research is actually focusing on the synthesis of materials and hybrids displaying improved electronic, physiochemical, electrical, and optical properties. Here, we review molybdenum disulfide (MoS 2 ) materials and hybrids with focus on synthesis, electronic structure and properties, calculations of state, bandgap and charge density profiles, and applications in energy storage and water remediation.

Screening the biochemical composition of some marine microalgal species for feeding Cyclops abyssorum divergens - Heba S. El-Sayed; Hoda H. Senousy; Aml Z. Ghoneim; Gihan M. El-Khodary; Mohamed A. El-Sheikh; Hanan M. Khairy; Salwa A. El-Saidy (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Impact of plasma irradiation on Tribolium castaneum - Waheed A. A. Sayed; Reda S. Hassan; Thanaa M. Sileem; Birgit A. Rumpold (Journal of Pest Science, 2021)
Radio frequency plasma (RFP) could provide reliable, compact, cost-effective irradiation applications against insect pests of stored food and feed products. Sensitivity of red flour beetle Tribolium castaneum to RFP has been investigated using an irradiation applicator system with the two types of inert gases, argon (Ar) and helium (He), at 100 W for five exposure time levels of 0, 20, 40, 60 and 90 s, respectively. We demonstrated that He RFP was more efficient against T. castaneum than Ar RFP. In addition, a positive correlation was observed between mortality percentages of treated insect stages and exposure times for both He and Ar RFP. The adult stage showed the highest tolerance to RFP irradiation followed by larvae and pupae; however, it was more susceptible than larvae within 24 h after He RFP treatments. The optimum exposure time was 90 s with He RFP, where a full mortality at all tested stages was accomplished, while mortalities of 71.4, 65.3 and 36.7% were recorded for pupae, larvae and adult stage, respectively, after an Ar RFP treatment of 90 s. In case of treated adults, the reproduction rate was higher than treated larvae and pupae. Our findings indicated that He RFP was an effective method for inhibiting T. castaneum development and impacting the insect life cycle and could be considered a promising tool for pest control of stored food.

4-Nonylphenol induced brain damage in juvenile African catfish (Clarias garepinus) - Zainab Eid; Usama M. Mahmoud; Imam A. A. Mekkawy; Hanem S. Abdel-Tawab; Alaa El-Din H. Sayed (Toxicology and Environmental Health Sciences, 2021)

Eco-friendly larvicide of Amphora coffeaeformis and Scenedesmus obliquus microalgae extracts against Culex pipiens - Marwa E. Hassan; Samia M. M. Mohafrash; Sahar A. Fallatah; Abo El-Khair B. El-Sayed; Abdel-Tawab H Mossa (Journal of Applied Phycology, 2021)

The COVID-19 pandemic: prediction study based on machine learning models - Zohair Malki; El-Sayed Atlam; Ashraf Ewis; Guesh Dagnew; Osama A. Ghoneim; Abdallah A. Mohamed; Mohamed M. Abdel-Daim; Ibrahim Gad (Environmental Science and Pollution Research, 2021)

Triggering the biosynthetic machinery of Taxol by Aspergillus flavipes via cocultivation with Bacillus subtilis: proteomic analyses emphasize the chromatin remodeling upon fungal-bacterial interaction - Ashraf S.A. El-Sayed; Ahmed A. Shindia; Azza AbouZeid; Alaa Koura; Sameh E. Hassanein; Rania M. Ahmed (Environmental Science and Pollution Research, 2021)

Development of the soil-inhabiting stages of Ceratitis capitata infected with entomopathogenic nematodes: insights on survival - El-Sayed H. Shaurub; Nehad A. Soliman; Magda M. Sabbour (Invertebrate Reproduction & Development, 2021)

Adjuvant effect of saponin in an oil-based monovalent (serotype O) foot-and-mouth disease virus vaccine on the antibody response in guinea pigs and cattle - Abdel-Hamid I. Bazid; Hayam A. El-Alfy; Gamal El-Didamony; Wael K. Elfeil; Magdy M. El-Sayed; Mohamed Fawzy (Archives of Virology, 2021)

New antimicrobial metabolites from the medicinal herb Artemisia herba-Alba - Tarik A. Mohamed; Abeer A. Abd El Aty; Abdelaaty A. Shahat; Nahla S. Abdel-Azim; Khaled A. Shams; Abdelsamed A. Elshamy; Mehawed M. Ahmed; Sabry H. H. Youns; Taher M. El-Wassimy; Sayed A. El-Toumy; Mohamed-Elamir F. Hegazy (Natural Product Research, 2021)

Risk assessment of horizontal curves using reliability analysis based on Google traffic data - Eman K. Ali; Ibrahim H. Hashim; Sayed A. Shwaly; Zaki M. Zidan; Sherif M. El-Badawy (Innovative Infrastructure Solutions, 2021)

Investigating the effects of copper sulfate and copper oxide nanoparticles in Nile tilapia (Oreochromis niloticus) using multiple biomarkers: the prophylactic role of Spirulina - Hamdy A. M. Soliman; Mohamed Hamed; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2021)

Potential therapeutic effects of Ulva lactuca water fraction on monosodium glutamate-induced testicular and prostatic tissue damage in rats - Aya M. Helal; Mohamed S. Abdel-Latif; Mosleh Mohammed Abomughaid; Doaa A. Ghareeb; Mohamed M. El-Sayed (Environmental Science and Pollution Research, 2021)

The nitrogen and phosphorus footprints of food products in Yemen over the last 57 years - Fawze Alnadari; Aisha Almakas; El-Sayed M. Desoky; Yasir A. Nasereldin; Salah Alden Alklaf; Ahmed S. Elrys (Environmental Science and Pollution Research, 2021)

Genetic polymorphism of lysyl oxidase, glutathione S-transferase M1, glutathione-S-transferase T1, and glutathione S-transferase P1 genes as risk factors for lung cancer in Egyptian patients - Sahar E. M. El-Deek; Soad M. Abdel-Ghany; Randa S. Hana; Aliaa A. R. Mohamed; Naglaa T. El-Melegy; Ayat A. Sayed (Molecular Biology Reports, 2021)

Hepatoprotective potential of Rosmarinus officinalis essential oil against hexavalent chromium-induced hematotoxicity, biochemical, histological, and immunohistochemical changes in male rats - Fatma M. El-Demerdash; Raghda A. El-Sayed; Mohamed M. Abdel-Daim (Environmental Science and Pollution Research, 2021)

Exploration radioactive mineralization using mappable data integration approach: example from Wadi Dahab area, Southeastern Sinai, Egypt - Mohamed O. Arnous; Ali A. ElMowafy; Sayed A. Azzaz; Ali E. Omar; Waheed M. Abdel Hafeez (Arabian Journal of Geosciences, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Slowly seeing the light: an integrative review on ecological light pollution as a potential threat for mollusks - Ahmed A. A. Hussein; Erik Bloem; István Fodor; El-Sayed Baz; Menerva M. Tadros; Maha F. M. Soliman; Nahla S. El-Shenawy; Joris M. Koene (Environmental Science and Pollution Research, 2021)
Seasonal changes in the natural light condition play a pivotal role in the regulation of many biological processes in organisms. Disruption of this natural condition via the growing loss of darkness as a result of anthropogenic light pollution has been linked to species-wide shifts in behavioral and physiological traits. This review starts with a brief overview of the definition of light pollution and the most recent insights into the perception of light. We then go on to review the evidence for some adverse effects of ecological light pollution on different groups of animals and will focus on mollusks. Taken together, the available evidence suggests a critical role for light pollution as a recent, growing threat to the regulation of various biological processes in these animals, with the potential to disrupt ecosystem stability. The latter indicates that ecological light pollution is an environmental threat that needs to be taken seriously and requires further research attention.

Correction to: Treatment of Brucellosis in Guinea Pigs via a Combination of Engineered Novel pH-Responsive Curcumin Niosome Hydrogel and Doxycycline-Loaded Chitosan–Sodium Alginate Nanoparticles: an In Vitro and In Vivo Study - Fatma I. Abo El-Ela; Khaled H. Hussein; Hossny A. El-Banna; Amr Gamal; Sherin Rouby; Ahmed M. S. Menshawy; El-Shaymaa El-Nahass; Shehata Anwar; Mohamed M. A. Zeinhom; Heba F. Salem; Marawa Ahmed Yahia Al-Sayed; Hala A. El-Newery; et al. (AAPS PharmSciTech, 2021)

Full Factorial Design, Optimization, In vitro and Ex vivo Studies of Ocular Timolol-Loaded Microsponges - Radwa M. A. Abd-Elal; Ghada H. Elosaily; Shadeed Gad; El-Sayed Khafagy; Yasser Mostafa (Journal of Pharmaceutical Innovation, 2020)

Microalgae Isolation for Nutrient Removal Assessment and Biodiesel Production - Muhammad Arif; Le Wang; El-Sayed Salama; Mian Sabir Hussain; Xiangkai Li; Mohammed Jalalah; M. S. Al-Assiri; Farid A. Harraz; Min-Kyu Ji; Pu Liu (BioEnergy Research, 2020)

Diclofenac mitigates virulence of multidrug-resistant Staphylococcus aureus - Hisham A. Abbas; Hamada Atallah; Mona A. El-Sayed; Amira M. El-Ganiny (Archives of Microbiology, 2020)

Molecular characterization of pathogenic Escherichia coli isolated from diarrheic and in-contact cattle and buffalo calves - Walid S. Awad; Amr A. El-Sayed; Faten F. Mohammed; Noha M. Bakry; Nadra-Elwgoud M. I. Abdou; Mohamed S. Kamel (Tropical Animal Health and Production, 2020)

Treatment of Brucellosis in Guinea Pigs via a Combination of Engineered Novel pH-Responsive Curcumin Niosome Hydrogel and Doxycycline-Loaded Chitosan–Sodium Alginate Nanoparticles: an In Vitro and In Vivo Study - Fatma I. Abo El-Ela; Khaled H. Hussein; Hossny A. El-Banna; Amr Gamal; Sherin Rouby; Ahmed M. S. Menshawy; EL-Shimaa EL-Nahass; Shehata Anwar; Mohamed M. A. Zeinhom; Heba F. Salem; Marawa Ahmed Yahia Al-Sayed; Hala A. El-Newery; et al. (AAPS PharmSciTech, 2020)

Silencing of tissue factor by antisense deoxyoligonucleotide mitigates thioacetamide-induced liver injury - M. S. Abdel-Bakky; G. K. Helal; E. M. El-Sayed; A. H. Alhowail; A. M. Mansour; K. S. Alharbi; Elham Amin; S. Allam; S. A. Salama; A. S. Saad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Combined effects of surface area of periphyton substrates and stocking density on growth performance, health status, and immune response of Nile tilapia (Oreochromis niloticus) produced in cages - Marwa S. Tammam; Elham A. Wassef; Mohamed M. Toutou; Abdel-Fattah M. El-Sayed (Journal of Applied Phycology, 2020)

17β-Estradiol augments the neuroprotective effect of agomelatine in depressive- and anxiety-like behaviors in ovariectomized rats - Yasmine A. El-Khatib; Rabab H. Sayed; Nada A. Sallam; Hala F. Zaki; Mahmoud M. Khattab (Psychopharmacology, 2020)

The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A Against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2020)

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Annie Page-Karjian; Catherine F. Lo; Branson Ritchie; Craig A. Harms; David S. Rotstein; Sushan Han; Sayed M. Hassan; Andreas F. Lehner; John P. Buchweitz; Victoria G. Thayer; Jill M. Sullivan; Emily F. Christiansen; et al. (Frontiers in Marine Science, 2020)

Segmentation effect on developing safety performance functions for rural arterial roads in Egypt - Sania Reyad Elagamy; Sherif M. El-Badawy; Sayed A. Shwaly; Zaki M. Zidan; Usama Elrawy Shahdah (Innovative Infrastructure Solutions, 2020)

Exendin-4 Ameliorates Cardiac Remodeling in Experimentally Induced Myocardial Infarction in Rats by Inhibiting PARP1/NF-κB Axis in A SIRT1-Dependent Mechanism - Refaat A. Eid; Samah A. Alharbi; Attalla Farag El-kott; Samy M. Eleawa; Mohamed Samir Ahmed Zaki; Fahmy El-Sayed; Muhammad Alaa Eldeen; Hussain Aldera; Abd Al-Rahman Salem Al-Shudiefat (Cardiovascular Toxicology, 2020)

Curcumin phytosome modulates aluminum-induced hepatotoxicity via regulation of antioxidant, Bcl-2, and caspase-3 in rats - Mohammed Al-Kahtani; Mohamed M. Abdel-Daim; Amany A. Sayed; Attalla El-Kott; Kareem Morsy (Environmental Science and Pollution Research, 2020)

Developmental toxicity of carbon nanoparticles during embryogenesis in chicken - Dalia H. Samak; Yasser S. El-Sayed; Hazem M. Shaheen; Ali H. El-Far; Mohamed E. Abd El-Hack; Ahmed E. Noreldin; Karima El-Naggar; Sameh A. Abdelnour; Essa M. Saied; Hesham R. El-Seedi; Lotfi Aleya; Mohamed M. Abdel-Daim (Environmental Science and Pollution Research, 2020)

Phylogenetic analysis of Salmonella species isolated from cows, buffaloes, and humans based on gyrB gene sequences - Lamiaa M. Ahmed; Amal S. M. Sayed; H. A. Abd ElKader; Nagla Hassan Abu Faddan; Amira Adel Taha Al Hosary (Tropical Animal Health and Production, 2020)

Antioxidants and molecular damage in Nile Tilapia (Oreochromis niloticus) after exposure to microplastics - Mohamed Hamed; Hamdy A. M. Soliman; Alaa G. M. Osman; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2020)
Recently, research on the biological effects of microplastics (MPs) has grown exponentially. However, effects of MPs on freshwater fishes and the mechanisms of the biological effects of MPs were limited. So, the purpose of the current study was to clarify the effects of microplastics on oxidative stress response, DNA fragmentation, and proteinogram of the early juvenile stage of Nile Tilapia ( Oreochromis niloticus ). The fishes were assigned into four groups: one control, three MPs-exposed groups as 1 mg/L of MPs, 10 mg/L of MPs, and 100 mg/L of MPs respectively for 15 days and 15 days of recovery. The activities of superoxide dismutase, catalase, total peroxides, and oxidative stress index (OSI), as well as lipid peroxidation and DNA fragmentation, increased in groups exposed to MPs compared to the control group in a dose-dependent manner. In contrast, the activity of total antioxidant capacity decreased in groups exposed to MPs compared to the control group in a dose-dependent manner. The electrophoretic pattern of muscle proteins revealed alteration in the proteinogram in the MPs-exposed groups compared to control. After the recovery period, the activities of superoxide dismutase, catalase, total peroxides, total antioxidant capacity, lipid peroxidation, DNA fragmentation, and the electrophoretic pattern of muscle proteins returned to normal levels in 1 mg/L of MPs-exposed group. Combined with our previous work, these results suggest that MPs cause the overproduction of reactive oxygen species (ROS) and alters the antioxidants parameters, resulting in oxidative stress and DNA damage. The present study fosters a better understanding of the toxic effects of MPs on Tilapia as a freshwater model.

Optimizing the Reduction of Molybdate by Two Novel Thermophilic Bacilli Isolated from Sinai, Egypt - Ali M. Saeed; Hayam A. E. Sayed; Einas H. El-Shatoury (Current Microbiology, 2020)

An integrated water quality assessment of Damietta and Rosetta branches (Nile River, Egypt) using chemical and biological indices - Seleim M. El Sayed; Mahmoud H. Hegab; Hesham R. A. Mola; Nasr M. Ahmed; Mohame E. Goher (Environmental Monitoring and Assessment, 2020)

Significance Assessment of Amphora coffeaeformis in Arsenic-Induced Hemato- Biochemical Alterations of African Catfish (Clarias gariepinus) - Imam A. Mekkawy; Usama M. Mahmoud; Rehab H. Moneeb; Alaa El-Din H. Sayed (Frontiers in Marine Science, 2020)

Does the gradual increase in dietary zinc oxide supplementation can affect egg quality, serum indices, and productive performance of laying hens? - M. E. Abd El-Hack; M. Alagawany; M. T. Chaudhry; M. Saeed; E. A. M. Ahmad; S. A. A. El-Sayed (Tropical Animal Health and Production, 2020)

Protective role of lycopene against metabolic disorders induced by chronic bisphenol A exposure in rats - Rania Abdelrahman Elgawish; Marwa A. El-Beltagy; Rehab M. El-Sayed; Aya A. Gaber; Heba M. A. Abdelrazek (Environmental Science and Pollution Research, 2020)

Utilization of Modified Attapulgite for the Removal of Sr(II), Co(II), and Ni(II) Ions from Multicomponent System, Part I: Kinetic Studies - Amira A. Mohammed; Ola A. Abdel Moamen; Sayed S. Metwally; Ahmed M. El-Kamash; Ibrahim Ashour; Mohammed S. Al-Geundi (Environmental Science and Pollution Research, 2020)

Role of ATP-Sensitive Potassium Channel (KATP) and eNOS in Mediating the Protective Effect of Nicorandil in Cyclophosphamide-Induced Cardiotoxicity - Marwa M. M. Refaie; Sayed Shehata; Maram El-Hussieny; Wedad M. Abdelraheem; Asmaa M. A. Bayoumi (Cardiovascular Toxicology, 2020)

Effects of Silver Nanoparticles on Burn Wound Healing in a Mouse Model - Lamiaa G. Wasef; Hazem M. Shaheen; Yasser S. El-Sayed; Thanaa I. A. Shalaby; Dalia H. Samak; Mohamed E. Abd El-Hack; Abdullah Al-Owaimer; Islam M. Saadeldin; Amany El-mleeh; Hani Ba-Awadh; Ayman A. Swelum (Biological Trace Element Research, 2020)

Pregnane glycoside from Huernia saudi-arabica as latent schistosomicidal mediator - Abeer M. El Sayed; Maha M. Basyoni; Sabah H. ElGayed; Ayman A. El-Badry; Essam Abdel-Sattar (Natural Product Research, 2020)

Co-inheritance of alpha globin gene deletion lowering serum iron level in female beta thalassemia patients - Sayed AbdulAzeez; Noor B. Almandil; Zaki A. Naserullah; Sana Al-Jarrash; Ahmed M. Al-Suliman; Huda I. ElFakharay; J. Francis Borgio (Molecular Biology Reports, 2020)

RETRACTED ARTICLE: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2019)

New antimalarial lanostane triterpenes from a new isolate of Egyptian Ganoderma species - Amir E. Wahba; Ahmed K. A. El-Sayed; Amira A. El-Falal; Eman M. Soliman (Medicinal Chemistry Research, 2019)

Silver nanoparticle–induced nephrotoxicity in Clarias gariepinus: physio-histological biomarkers - Usama M. Mahmoud; Imam A. A. Mekkawy; Mervat Naguib; Alaa El-Din H. Sayed (Fish Physiology and Biochemistry, 2019)

Isotherm and kinetic studies on the adsorption of humic acid molecular size fractions onto clay minerals - Mohamed E. A. El-Sayed; Moustafa M. R. Khalaf; James A. Rice (Acta Geochimica, 2019)

Comparative influence of dietary probiotic, yoghurt, and sodium butyrate on growth performance, intestinal microbiota, blood hematology, and immune response of meat-type chickens - M. N. Makled; K. F. M. Abouelezz; A. E. G. Gad-Elkareem; A. M. Sayed (Tropical Animal Health and Production, 2019)

Synthesis, antimicrobial evaluation, and molecular docking of some new angular allylbenzochromone derivatives - El-Sayed I. El-Desoky; Aya A. El-Sawi; Mohamed A. Abozeid; Mohamed Abdelmoteleb; Mona Shaaban; Eman M. Keshk; Abdel-Rahman H. Abdel-Rahman (Medicinal Chemistry Research, 2019)

Effects of Dietary Supplementation of Probiotic Mix and Prebiotic on Growth Performance, Cecal Microbiota Composition, and Protection Against Escherichia coli O78 in Broiler Chickens - Reda Tarabees; Khaled M. Gafar; Mohamed S. EL-Sayed; Awad A. Shehata; Marwa Ahmed (Probiotics and Antimicrobial Proteins, 2019)

Crops For the Future (CFF): an overview of research efforts in the adoption of underutilised species - Peter J. Gregory; Sean Mayes; Chai Hui Hui; Ebrahim Jahanshiri; Advina Julkifle; Giva Kuppusamy; Ho Wai Kuan; Tan Xin Lin; Festo Massawe; T. A. S. T. M. Suhairi; Sayed N. Azam-Ali (Planta, 2019)

Novel chromenes and benzochromenes bearing arylazo moiety: molecular docking, in-silico admet, in-vitro antimicrobial and anticancer screening - Tarek H. Afifi; Sayed M. Riyadh; Anwar A. Deawaly; Arshi Naqvi (Medicinal Chemistry Research, 2019)

Carnitine Supplementation Attenuates Sunitinib-Induced Inhibition of AMP-Activated Protein Kinase Downstream Signals in Cardiac Tissues - Mohamed M. Sayed-Ahmed; Badr I. Alrufaiq; Ammar Alrikabi; Mashan L. Abdullah; Mohamed M. Hafez; Othman A. Al-Shabanah (Cardiovascular Toxicology, 2019)

Could curcumin ameliorate titanium dioxide nanoparticles effect on the heart? A histopathological, immunohistochemical, and genotoxic study - Eman Ahmed Alaa El-Din; Heba El-Sayed Mostafa; Mai A. Samak; Eman M. Mohamed; Dalia Abdallah El-Shafei (Environmental Science and Pollution Research, 2019)

Ameliorative effect of Spirulina platensis against lead nitrate–induced cytotoxicity and genotoxicity in catfish Clarias gariepinus - Mohamed Hamed; Hamdy A. M. Soliman; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2019)

Using ZnO nanoparticles in fungal inhibition and self-protection of exposed marble columns in historic sites - Mohammad Ateeq Aldosari; Sawsan S. Darwish; Mahmoud A. Adam; Nagib A. Elmarzugi; Sayed M. Ahmed (Archaeological and Anthropological Sciences, 2019)

Evaluation of preventive performance of kaolin and calcium hydroxide nanocomposites in strengthening the outdoor carved limestone - Mohammad A. Aldosari; Sawsan S. Darwish; Mahmoud A. Adam; Nagib A. Elmarzugi; Sayed M. Ahmed (Archaeological and Anthropological Sciences, 2019)

Water quality status and pollution indices of Wadi El-Rayan lakes, El-Fayoum, Egypt - Mohamed E. Goher; El-Sayed M. Mahdy; Mohamed H. Abdo; Farida M. El Dars; Mostafa A. Korium; Aya A. S. Elsherif (Sustainable Water Resources Management, 2019)

Reprotoxicity of 4-nonylphenol to Biomphalaria alexandrina snails at certain temperatures - Marwa T. A. Abdel–Wareth; Sara S. M. Sayed (Environmental Science and Pollution Research, 2019)

Comparative effectiveness of Sumaq and Neem extract cream, Eniloconazole and glycerine iodine on dermatophytosis in Arabian horses: a randomized clinical trial - Mohamed Z. Sayed-Ahmed; Ahmed M. Ahdy; Emad E. Younis; Sabry A. El-khodery; Hany N. Baraka (Tropical Animal Health and Production, 2019)

Syntheses and in silico pharmacokinetic predictions of glycosylhydrazinyl-pyrazolo[1,5-c]pyrimidines and pyrazolo[1,5-c]triazolo[4,3-a]pyrimidines as anti-proliferative agents - Kamal F. M. Atta; Omaima O. M. Farahat; Tareq Q. Al-Shargabi; Mohamed G. Marei; Tamer M. Ibrahim; Adnan A. Bekhit; El Sayed H. El Ashry (Medicinal Chemistry Research, 2019)

In vitro evaluation of the probiotic candidates isolated from the gut of Clarias gariepinus with special reference to the in vivo assessment of live and heat-inactivated Leuconostoc mesenteroides and Edwardsiella sp. - Khaled M. Selim; Hassanin M. El-Sayed; M. A. El-Hady; Rasha M. Reda (Aquaculture International, 2019)

Nutritive utilization of Moringa oleifera tree stalks treated with fungi and yeast to replace clover hay in growing lambs - K. Z. Kewan; F. A. Salem; A. Z. M. Salem; A. R. Abdou; H. M. El-Sayed; S. S. Eisa; E. A. Zaki; N. E. Odongo (Agroforestry Systems, 2019)

Sediment pollution in an urban water supply lake in southern Brazil - Leonardo Capeleto de Andrade; Fabrício Fernandes Coelho; Sayed M. Hassan; Lawrence A. Morris; Flávio Anastácio de Oliveira Camargo (Environmental Monitoring and Assessment, 2019)

Preparation and Using Modified Nanohydroxyapatite Molecules for Wastewater Treatment - Mohamed E. A. El-Sayed; Atef F. Ahmed; Othman A. Farghaly; M. Abd-Elmottaleb; Tarek A. Seaf Elnasr; Mahmoud A. M. Hassan (Water Conservation Science and Engineering, 2018)

In Vitro Selection and Identification of Potential Probiotics Isolated from the Gastrointestinal Tract of Nile Tilapia, Oreochromis niloticus - Rasha M. Reda; Khaled M. Selim; Hassanin M. El-Sayed; M. A. El-Hady (Probiotics and Antimicrobial Proteins, 2018)

Campanian-Lower Paleogene gastropods from the Kharga Oasis, south Western Desert, Egypt - Abdel Galil A. Hewaidy; Gamal M. El Qot; El Sayed M. Moneer (Arabian Journal of Geosciences, 2018)

The molecular and biochemical insight view of lycopene in ameliorating tramadol-induced liver toxicity in a rat model: implication of oxidative stress, apoptosis, and MAPK signaling pathways - Kadry M. Sadek; Mohamed A. Lebda; Tarek K. Abouzed; Sherif M. Nasr; Yasser EL-Sayed (Environmental Science and Pollution Research, 2018)

Toxicological assessment of lambda-cyhalothrin and acetamiprid insecticides formulated mixture on hatchability rate, histological aspects, and protein electrophoretic pattern of Biomphalaria alexandrina (Ehrenberg, 1831) snails - Amina Mohamed Ibrahim; Sara S. M. Sayed; Ibrahim R. A. Shalash (Environmental Science and Pollution Research, 2018)

Influence of different microalgal diets on gonadal development of the carpet shell clam Ruditapes decussatus broodstock - Ahmed S. A. Abbas; Eman El-Wazzan; Amal R. Khafage; Abdel-Fattah M. El-Sayed; Fatma A. Abdel Razek (Aquaculture International, 2018)

Association of Toll-like receptor 3 and Toll-like receptor 9 single-nucleotide polymorphisms with hepatitis C virus persistence among Egyptians - Shaimaa Hamdy; Ahmed M. Osman; Zainab A. Zakaria; Iman Galal; Maha Sobhy; Mohamed Hashem; Walaa R. Allam; Mohamed Abdel-Samiee; Eman Rewisha; Imam Waked; Sayed F. Abdelwahab (Archives of Virology, 2018)

Role of lncRNAs as prognostic markers of hepatic cancer and potential therapeutic targeting by S-adenosylmethionine via inhibiting PI3K/Akt signaling pathways - Kadry M. Sadek; Mohamed A. Lebda; Nasr E. Nasr; Sherif M. Nasr; Yasser EL-Sayed (Environmental Science and Pollution Research, 2018)

Does the application of silicon and Moringa seed extract reduce heavy metals toxicity in potato tubers treated with phosphate fertilizers? - Ahmed S. Elrys; Abdel-Rahman M. A. Merwad; Ahmed I. E. Abdo; Mohamed K. Abdel-Fatah; El-Sayed M. Desoky (Environmental Science and Pollution Research, 2018)

Mitigation of Acute Aluminum Toxicity by Sodium Selenite and N-Acetylcysteine in Adult Male Rats - Naglaa H. Nour-Eldein; El-Sayed A. Hassanin; Wael M. El-Sayed (Biological Trace Element Research, 2018)

RETRACTED ARTICLE: Cytotoxic effect of chlorpyrifos is associated with activation of Nrf-2/HO-1 system and inflammatory response in tongue of male Wistar rats - Norhan M. El-Sayed; Amal A. M. Ahmed; Manar A. A. Selim (Environmental Science and Pollution Research, 2018)

Assessment of Bioavailability of Some Heavy Metals to Wheat and Faba Bean in Sahl El-Tina, Egypt - A. M. Ali; S. M. Ibrahim; Y. A. Abd El-Hady; A. S. A. Sayed (Agricultural Research, 2018)

Comparison of AASHTO 1993 and MEPDG considering the Egyptian climatic conditions - Maha A. El-shaib; Sherif M. El-Badawy; El-Sayed A. Shawaly (Innovative Infrastructure Solutions, 2017)

Variation in biochemical constituents and master elements in common seaweeds from Alexandria Coast, Egypt, with special reference to their antioxidant activity and potential food uses: prospective equations - Mona M. Ismail; Gehan M. El Zokm; Abeer A. M. El-Sayed (Environmental Monitoring and Assessment, 2017)

Biomarkers of oxidative stress in Biomphalaria alexandrina snails for assessing the effects of certain inorganic fertilisers - Fatma A.A. El-Deeb; Mohamed-Assem S. Marie; Wafaa S. Hasheesh; Rehab M. A. Hussein; Sara S. M. Sayed (Molluscan Research, 2017)

Aspartame and Soft Drink-Mediated Neurotoxicity in Rats: Implication of Oxidative Stress, Apoptotic Signaling Pathways, Electrolytes and Hormonal Levels - Mohamed A. Lebda; Kadry M. Sadek; Yasser S. El-Sayed (Metabolic Brain Disease, 2017)

Novel arylazothiazoles and arylazo[1,3,4]thiadiazoles as potential antimicrobial and anticancer agents: synthesis, molecular modeling, and biological screening - Sayed M. Riyadh; Anwar A. Deawaly; Hany E. A. Ahmed; Tarek H. Afifi; Saleh Ihmaid (Medicinal Chemistry Research, 2017)

Selectivity Improvement for Spectrofluorimetric Determination of Oseltamivir Phosphate in Human Plasma and in the Presence of Its Degradation Product - Mahmoud A. Omar; Sayed M. Derayea; Islam M. Mostafa (Journal of Fluorescence, 2017)

Laser Performance of Some Oxazole Laser Dyes in Restricted Matrices - Mahmoud A. S. Sakr; Sayed A. Abdel Gawad; Maram T. H. Abou Kana; El-Zeiny M. Ebeid (Journal of Fluorescence, 2017)

Modulatory Role of Nurr1 Activation and Thrombin Inhibition in the Neuroprotective Effects of Dabigatran Etexilate in Rotenone-Induced Parkinson’s Disease in Rats - Esraa A. Kandil; Rabab H. Sayed; Lamiaa A. Ahmed; Mai A. Abd El Fattah; Bahia M. El-Sayeh (Molecular Neurobiology, 2017)

Caterpillar-Induced Plant Volatiles Attract Adult Tortricidae - D. M. Suckling; A. M. El-Sayed (Journal of Chemical Ecology, 2017)

Bioactive/Natural Polymeric Scaffolds Loaded with Ciprofloxacin for Treatment of Osteomyelitis - Amany A. Mostafa; Mayyada M. H. El-Sayed; Azza A. Mahmoud; Amira M. Gamal-Eldeen (AAPS PharmSciTech, 2017)

Selective Spectrofluorimetric Method with Enhanced Sensitivity for Determination of Silodosine in Dosage Form and Human Plasma. Application to Stability Studies and Content Uniformity Testing - Mahmoud A. Omar; Abdel-Maaboud I. Mohamed; Sayed M. Derayea; Mohamed A. Hammad; Abobakr A. Mohamed (Journal of Fluorescence, 2017)

Modeling and Optimization of Oil Adsorption from Wastewater Using an Amorphous Carbon Thin Film Fabricated from Wood Sawdust Waste Modified with Palmitic Acid - Sherif A. Younis; Mona El-Sayed; Yasser M. Moustafa (Environmental Processes, 2017)

Association between IL28B rs12979860 single nucleotide polymorphism and the frequency of colonic Treg in chronically HCV-infected patients - Minesh Mehta; Helal F. Hetta; Enass A. Abdel-hameed; Susan D. Rouster; MdMonir Hossain; Mohamed A. Mekky; Nasr K. Khalil; Wegdan A. Mohamed; Mohamed A. El-Feky; Shabaan H. Ahmed; Enas A. Daef; Mohamed A. El-Mokhtar; et al. (Archives of Virology, 2016)

Interleukin-10.rs1800896 and Interleukin-18.rs1946518 gene polymorphisms could not predict the outcome of hepatitis C virus infection in Egyptian patients treated with pegylated interferon plus ribavirin - Wedad M. Abdelraheem; Noha A. Hassuna; Sahar M. Abuloyoun; Hend M. Abdel Ghany; Hazem A. Rizk; Sayed F Abdelwahab (Archives of Virology, 2016)

A new acylated flavonol from the aerial parts of Asteriscus maritimus (L.) Less (Asteraceae) - Marwa I. Ezzat; Shahira M. Ezzat; Kadriya S. El Deeb; Ahlam M. El Fishawy; Sayed A. El-Toumy (Natural Product Research, 2016)

Gamma radiolytic decomposition of endosulfan in aerated solution: the role of carbonate radical - Noor S. Shah; Javed Ali Khan; Ala’a H. Al-Muhtaseb; Murtaza Sayed; Hasan M. Khan (Environmental Science and Pollution Research, 2016)

Phylogenetic analysis of human influenza A/H3N2 viruses isolated in 2015 in Germany indicates significant genetic divergence from vaccine strains - Ahmed Mostafa; El-Sayed M. Abdelwhab; Heiko Slanina; Mohamed A. Hussein; Irina Kuznetsova; Christian G. Schüttler; John Ziebuhr; Stephan Pleschka (Archives of Virology, 2016)

Bioavailability of paracetamol with/without caffeine in Egyptian patients with hepatitis C virus - Naglaa M. El-Lakkany; Ahmed S. Hendawy; Sayed H. Seif el-Din; Ahmed A. Ashour; Raafat Atta; Abdel-Aziz H. Abdel-Aziz; Ahmed M. Mansour; Sanaa S. Botros (European Journal of Clinical Pharmacology, 2016)

Geoelectrical and hydrogeological study to delineate the geological structures affecting the groundwater occurrence in Wadi El Khariq Basin, Northwest El Maghara, north Sinai, Egypt - Mohamed A. Khaled; Ayman M. Al Tammamy; Mostafa S. Barseem; Ahmed N. El Sayed; El Sayed A. El Abed (Arabian Journal of Geosciences, 2016)

Occurrence of copper-complexing ligands in the coastal sediments of eastern Red Sea - R. Al-Farawati; M. A. El Sayed; Y. A. Shaban; A. J. Turki (Arabian Journal of Geosciences, 2016)

Petrographical and petrophysical integrated studies, Jurassic rock samples, North Sinai, Egypt - Mohamed A. Kassab; Hesham H. Abuseda; Nahla A. El Sayed; Amir M LaLa; Osama M. Elnaggar (Arabian Journal of Geosciences, 2016)

Antioxidant and anti-inflammatory effects of flavocoxid in high-cholesterol-fed rabbits - Ahmed R. El-Sheakh; Hamdy A. Ghoneim; Ghada M. Suddek; El-Sayed M. Ammar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Giant reed for selenium phytoremediation under changing climate - Hassan R. El-Ramady; Neama Abdalla; Tarek Alshaal; Ahmed S. Elhenawy; Mohamed S. Shams; Salah E.-D. A. Faizy; El-Sayed B. Belal; Said A. Shehata; Mohamed I. Ragab; Megahed M. Amer; Miklós Fári; Attila Sztrik; et al. (Environmental Chemistry Letters, 2015)

Beyond RGD: virus interactions with integrins - Hosni A. M. Hussein; Lia R. Walker; Usama M. Abdel-Raouf; Sayed A. Desouky; Abdel Khalek M. Montasser; Shaw M. Akula (Archives of Virology, 2015)

Optical tweezers: a non-destructive tool for soft and biomaterial investigations - A. Magazzú; D. Spadaro; M. G. Donato; R. Sayed; E. Messina; C. D’Andrea; A. Foti; B. Fazio; M. A. Iatí; A. Irrera; R. Saija; P. G. Gucciardi; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Metabolomics reveals distinct methylation reaction in MeJA elicited Nigella sativa callus via UPLC–MS and chemometrics - Mohamed A. Farag; Abeer M. El Sayed; Ahmed El Banna; Susanne Ruehmann (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Giardia duodenalis assemblages in Egyptian children with diarrhea - H. M. Fahmy; A. O. El-Serougi; H. K. El Deeb; H. M. Hussein; H. M. Abou-Seri; C. Klotz; T. Aebischer; K. El Sayed Khalifa Mohamed (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Occurrence of cyanobacteria and microcystin toxins in raw and treated waters of the Nile River, Egypt: implication for water treatment and human health - Zakaria A. Mohamed; Mohamed Ali Deyab; Mohamed I. Abou-Dobara; Ahmad K. El-Sayed; Wesam M. El-Raghi (Environmental Science and Pollution Research, 2015)

Study of electrical properties and petrography for carbonate rocks in the Jurassic Formations: Sinai Peninsula, Egypt - Mohamed M. Gomaa; Mohamed A. Kassab; Nahla A. El–Sayed (Arabian Journal of Geosciences, 2015)

Late Neoproterozoic Dokhan volcanics, around G. Esh, North Eastern Desert, Egypt: geochemistry and relation of K2O and Nb abundances with crustal thickness - Sayed A. Azzaz; M. Blasy; A. Moharem; O. Amer (Arabian Journal of Geosciences, 2015)

Protective effect of Pelargonium graveolens against carbon tetrachloride-induced hepatotoxicity in mice and characterization of its bioactive constituents by HPLC–PDA–ESI–MS/MS analysis - Eman Al-Sayed; Olli Martiskainen; Sayed H. Seif el-Din; Abdel-Nasser A. Sabra; Olfat A. Hammam; Naglaa M. El-Lakkany (Medicinal Chemistry Research, 2015)

Impact of Bio- and Organic Fertilizers on Potato Yield, Quality and Tuber Weight Loss After Harvest - Sayed F. El-Sayed; Hassan A. Hassan; Mohamed M. El-Mogy (Potato Research, 2015)

Synthesis and quantitative structure activity relationship (QSAR) of arylidene (benzimidazol-1-yl)acetohydrazones as potential antibacterial agents - Yeldez El-Kilany; Nariman M. Nahas; Mariam A. Al-Ghamdi; Mohamed E. I. Badawy; El Sayed H. El Ashry (World Journal of Microbiology and Biotechnology, 2015)

A Novel High-Speed Imaging Technique to Predict the Macroscopic Spray Characteristics of Solution Based Pressurised Metered Dose Inhalers - Nicolas A. Buchmann; Daniel J. Duke; Sayed A. Shakiba; Daniel M. Mitchell; Peter J. Stewart; Daniela Traini; Paul M. Young; David A. Lewis; Julio Soria; Damon Honnery (Pharmaceutical Research, 2014)

GC estimation of organic hydrocarbons that threaten shallow Quaternary sandy aquifer Northwestern Gulf of Suez, Egypt - M. F. Zawrah; M. A. Ebiad; A. M. Rashad; E. El-Sayed; Moustafa Gamal Snousy; M. A. Tantawy (Environmental Monitoring and Assessment, 2014)

Structural and functional effects of early exposure to 4-nonylphenol on gonadal development of Nile tilapia (Oreochromis niloticus): a-histological alterations in ovaries - T. El-Sayed Ali; S. H. Abdel-Aziz; A.-F. M. El-Sayed; S. Zeid (Fish Physiology and Biochemistry, 2014)

Structural and functional effects of early exposure to 4-nonylphenol on gonadal development of Nile tilapia (Oreochromis niloticus): b-histological alterations in testes - T. El-Sayed Ali; S. H. Abdel-Aziz; A.-F. M. El-Sayed; S. Zeid (Fish Physiology and Biochemistry, 2014)

Rock slope stability and design in Arafat–Muzdalifa area, Saudi Arabia - Ali M. A. Abd-Allah; E. K. El-Sawy; El-Sayed Sedek Abu Seif; Abdelhamid El-Fakharani; Mohammed Amin M. Sharaf (Arabian Journal of Geosciences, 2014)

New quinoline alkaloid from Ruta graveolens aerial parts and evaluation of the antifertility activity - Josline Y. Salib; Sayed A. El-Toumy; Emad M. Hassan; Nabila H. Shafik; Sally M. Abdel-Latif; Ignacio Brouard (Natural Product Research, 2014)

Inhibition of Gene Expression of Carnitine Palmitoyltransferase I and Heart Fatty Acid Binding Protein in Cyclophosphamide and Ifosfamide-Induced Acute Cardiotoxic Rat Models - Mohamed M. Sayed-Ahmed; Meshan L. Aldelemy; Othman A. Al-Shabanah; Mohamed M. Hafez; Khaled A. Al-Hosaini; Naif O. Al-Harbi; Shakir D. Al-Sharary; Mohamed M. Al-Harbi (Cardiovascular Toxicology, 2014)

In vitro anti-nitrosative, antioxidant, and cytotoxicity activities of plant flavonoids: a comparative study - Hanem M. Awad; Howaida I. Abd-Alla; Khaled H. Mahmoud; Sayed A. El-Toumy (Medicinal Chemistry Research, 2014)

Erratum to: Evaluation of Tadalafil Nanosuspensions and Their PEG Solid Dispersion Matrices for Enhancing Its Dissolution Properties - Wasfy M. Obeidat; Al-Sayed A. Sallam (AAPS PharmSciTech, 2014)

Pharmacological evaluation of some novel synthesized compounds derived from spiro(cyclohexane-1,2′-thiazolidines) - Eman M. Flefel; Hayam H. Sayed; Ahmed I. Hashem; Emad A. Shalaby; Walaa El-Sofany; Farouk M. E. Abdel-Megeid (Medicinal Chemistry Research, 2014)

Loss of P2Y2 Nucleotide Receptors Enhances Early Pathology in the TgCRND8 Mouse Model of Alzheimer's Disease - Deepa Ajit; Lucas T. Woods; Jean M. Camden; Christina N. Thebeau; Farid G. El-Sayed; Glen W. Greeson; Laurie Erb; Michael J. Petris; Douglas C. Miller; Grace Y. Sun; Gary A. Weisman (Molecular Neurobiology, 2014)

Assessment of the mutual impact between climate and vegetation cover using NOAA-AVHRR and Landsat data in Egypt - Mohammed A. El-Shirbeny; Mohamed A. Aboelghar; Sayed M. Arafat; Abdel-Ghany M. El-Gindy (Arabian Journal of Geosciences, 2014)

Evaluation of Tadalafil Nanosuspensions and Their PEG Solid Dispersion Matrices for Enhancing Its Dissolution Properties - Wasfy M. Obeidat; Al-Sayed A. Sallam (AAPS PharmSciTech, 2014)

Efficient pan-sharpening of satellite images with the contourlet transform - Mohamed R. Metwalli; Ayman H. Nasr; Osama S. Faragallah; El-Sayed M. El-Rabaie; Alaa M. Abbas; Saleh A. Alshebeili; Fathi E. Abd El-Samie (International Journal of Remote Sensing, 2014)

Novel Comparative Synchronous Spectrofluorimetric Study of Benzo(a)pyrene Using Beta-Cyclodextrin and Calix(8)arene as Fluorescence Enhancers - Omar Abdel-Aziz; A. M. El Kosasy; S. M. El-Sayed Okeil (Journal of Fluorescence, 2014)

Novel Method for Determination of Anthracene by Coupling Dispersive Liquid-Liquid Extraction to First-Derivative Synchronous Spectrofluorimetry - Omar Abdel-Aziz; A. M. El Kosasy; Sherif Mahmoud El-Sayed Okeil (Journal of Fluorescence, 2014)

6-Pentyl-2H-pyran-2-one: A Potent Peach-Derived Kairomone for New Zealand Flower Thrips, Thrips obscuratus - A. M. El-Sayed; V. J. Mitchell; D. M. Suckling (Journal of Chemical Ecology, 2014)

Bioactive terpenoids from the Red Sea soft coral Sinularia polydactyla - El-Sayed A. Aboutabl; Shadia M. Azzam; Camilia G. Michel; Nabil M. Selim; Mohamed F. Hegazy; Abdel-Hamid A.M. Ali; Ahmed A. Hussein (Natural Product Research, 2013)

Influence of Magnetic Field on Brain Activity During Administration of Caffeine - M. I. El Gohary; A. A. Salama; A. A. EL Saeid; T. M. El Sayed; H. Sh. Kotb (Cell Biochemistry and Biophysics, 2013)

Pterocladia (Rhodophyta) and Ulva (Chlorophyta) as feed supplements for European seabass, Dicentrarchus labrax L., fry - Elham A. Wassef; Abdel-Fattah M. El-Sayed; Eman M. Sakr (Journal of Applied Phycology, 2013)

Biochemical Changes Observed After PUVA Versus PUVA Plus Methotrexate Therapy in Mycosis Fungoides Using Synchrotron Infrared Microspectroscopy - Ahmed E. L. Bedewi; Randa Youssef; Dalia M. Abdel Halim; Rehab A. Hegazy; William Willis; Lisa M. Miller; Safinaz S. Sayed; Medhat E. L. Mofty (International Journal of Peptide Research and Therapeutics, 2013)

Novel 4(3H)-quinazolinone analogs: synthesis and anticonvulsant activity - Adel S. El-Azab; Sami G. Abdel-Hamide; Mohamed M. Sayed-Ahmed; Ghada S. Hassan; Tariq M. El-Hadiyah; Othman A. Al-Shabanah; Omar A. Al-Deeb; Hussein I. El-Subbagh (Medicinal Chemistry Research, 2013)

Synthesis, molecular modeling study, preliminary antibacterial, and antitumor evaluation of N-substituted naphthalimides and their structural analogues - Adel S. El-Azab; Amer M. Alanazi; Naglaa I. Abdel-Aziz; Ibrahim A. Al-Suwaidan; Magda A. A. El-Sayed; Magda A. El-Sherbeny; Alaa A.-M. Abdel-Aziz (Medicinal Chemistry Research, 2013)

A new isoflavone from Blepharis ciliaris of an Egyptian origin - Mohamed A. El-Shanawany; Hanaa M. Sayed; Sabrin R. M. Ibrahim; Marwa A. A. Fayed; Mohamed M. Radwan; Samir A. Ross (Medicinal Chemistry Research, 2013)

Novel nanocomposites based on gelatin/HPET/chitosan with high performance acid red 150 dye adsorption - Ahmed A. Haroun; Hamada M. Mashaly; Nabil H. El-Sayed (Clean Technologies and Environmental Policy, 2013)

The role of Periodic Safety Update Reports in the safety management of biopharmaceuticals - Hans C. Ebbers; Aukje K. Mantel-Teeuwisse; Fakhredin A. Sayed-Tabatabaei; Ellen H. M. Moors; Huub Schellekens; Hubert G. M. Leufkens (European Journal of Clinical Pharmacology, 2013)

Exploration of copper deposits in Wadi El Regeita area, Southern Sinai, Egypt, with contribution of remote sensing and geophysical data - S. M. Salem; Sultan Awad Arafa; T. M. Ramadan; El Sayed A. El Gammal (Arabian Journal of Geosciences, 2013)

Interactions between the surface water and groundwater in the western shoreline of Lake Nasser, Upper Egypt - Ali M. Hamdan; Sayed A. Selim; Mohamed M. Abdallah (Arabian Journal of Geosciences, 2013)

Composition, age, and origin of the ~620 Ma Humr Akarim and Humrat Mukbid A-type granites: no evidence for pre-Neoproterozoic basement in the Eastern Desert, Egypt - Kamal A. Ali; Abdel-Kader M. Moghazi; Ayman E. Maurice; Sayed A. Omar; Qiang Wang; Simon A. Wilde; Ewais M. Moussa; William I. Manton; Robert J. Stern (International Journal of Earth Sciences, 2012)

Development of Artificial Seed Technology and Preservation in Sugar Beet - Aida A. Rizkalla; Awatef M. Badr-Elden; Mahmoud El-Sayed Ottai; M. I. Nasr; Marwa N. M. Esmail (Sugar Tech, 2012)

Catastrophic movement of rocks and proposed solutions to avoid its risks in the Abu El-Reesh area, northeast Aswan City, Egypt - Ashraf Emam; Abdel Hamid S. El-Fakharani; Adel W. Felesteen; Sayed A. Selim; Kamal M. Hafez (Arabian Journal of Geosciences, 2012)

Potential anti-inflammatory activity and ulcerogenicity study of some novel pyrimido[4′,5′:4,5]pyrimido[1,6-a]azepine derivatives - Nehad A. El-Sayed; Fadi M. Awadallah; Nashwa A. Ibrahim; Mohamed T. El-Saadi (Medicinal Chemistry Research, 2012)

A survey of selected essential and heavy metals in milk from different regions of Egypt using ICP-AES - Elham M. El Sayed; Ahmed M. Hamed; Sanna M. Badran; Amr A. Mostafa (Food Additives & Contaminants Part B-Surveillance, 2011)

Design, synthesis, and anticonvulsant activity of novel quinazolinone analogues - Nagwa M. Abdel Gawad; Hanan Hanna Georgey; Riham M. Youssef; Nehad A. El Sayed (Medicinal Chemistry Research, 2011)

Effects of Chemical Reaction, Heat, and Mass Transfer on Non-Newtonian Fluid Flow Through Porous Medium in a Vertical Peristaltic Tube - M. F. El-Sayed; N. T. M. Eldabe; A. Y. Ghaly; H. M. Sayed (Transport in Porous Media, 2011)

Trends in whey protein fractionation - Mayyada M. H. El-Sayed; Howard A. Chase (Biotechnology Letters, 2011)

Molecular aspects in elevation of sunflower tolerance to drought by boron and calcium foliar sprays - Nemat M. Hassan; Ahmed K. A. El-Sayed; Heba T. Ebeid; Mamdouh M. Nemat Alla (Acta Physiologiae Plantarum, 2011)

Identification of microsatellite markers linked with yield components under drought stress at terminal growth stages in durum wheat - M. Golabadi; A. Arzani; S. A. M. Mirmohammadi Maibody; B. E. Sayed Tabatabaei; S. A. Mohammadi (Euphytica, 2011)

Antihypercholesterolaemic effect of ginger rhizome (Zingiber officinale) in rats - El-Sayed M. ElRokh; Nemat A. Z. Yassin; Siham M. A. El-Shenawy; Bassant M. M. Ibrahim (Inflammopharmacology, 2010)

Choanephora rot of floral tops of Hyoscyamus muticus caused by Choanephora cucurbitarum - Fatma F. Abdel-Motaal; Magdi A. El-Sayed; Soad A. El-Zayat; Mortada S. M. Nassar; Shin-ichi Ito (Journal of General Plant Pathology, 2010)

Effects of ultraviolet A on the activity of two metabolic enzymes, DNA damage and lipid peroxidation during early developmental stages of the African catfish, Clarias gariepinus (Burchell, 1822) - Imam A. A. Mekkawy; Usama M. Mahmoud; Alaa G. Osman; Alaa El-Din H. Sayed (Fish Physiology and Biochemistry, 2010)

Effect of pH on growth and biochemical responses of Dunaliella bardawil and Chlorella ellipsoidea - Zeinab I. Khalil; Mohsen M. S. Asker; Salwa El-Sayed; Imam A. Kobbia (World Journal of Microbiology and Biotechnology, 2010)

Antifungal activities of hyoscyamine and scopolamine against two major rice pathogens: Magnaporthe oryzae and Rhizoctonia solani - Fatma F. Abdel-Motaal; Soad A. El-zayat; Yuki Kosaka; Magdi A. El-Sayed; Rumi Kashima; Yukie Maeda; Mortada S. M. Nassar; Shin-ichi Ito (Journal of General Plant Pathology, 2010)

Sustained Release Tablets Containing Soluble Polymethacrylates: Comparison with Tableted Polymethacrylate IPEC Polymers - Wasfy M. Obeidat; Alaa H. Abuznait; Al-Sayed A. Sallam (AAPS PharmSciTech, 2010)

Leaf spot disease of Hyoscyamus muticus (Egyptian henbane) caused by Cladosporium herbarum - Fatma F. Abdel-Motaal; Magdi A. El-Sayed; Soad A. El-Zayat; Mortada S. M. Nassar; Shin-ichi Ito (Journal of General Plant Pathology, 2009)

Bioactive lipids and antioxidant properties of wild Egyptian Pulicaria incise, Diplotaxis harra, and Avicennia marina - M. F. Ramadan; M. M. A. Amer; H. T. Mansour; K. M. Wahdan; R. M. El-Sayed; S. El-Sanhoty; W. A. El-Gleel (Journal of Consumer Protection and Food Safety, 2009)

Serum levels of TNF-α and antioxidant enzymes and placental TNF-α expression in unexplained recurrent spontaneous miscarriage - M. El-Far; I. H. El-Sayed; A. E. El-Motwally; I. A. Hashem; N. Bakry (Journal of Physiology and Biochemistry, 2009)

Attraction of New Zealand Flower Thrips, Thrips obscuratus, to cis-Jasmone, a Volatile Identified from Japanese Honeysuckle Flowers - A. M. El-Sayed; V. J. Mitchell; G. F. McLaren; L. M. Manning; B. Bunn; D. M. Suckling (Journal of Chemical Ecology, 2009)

responses of fungi to tropane alkaloids produced by a medicinal plant Hyoscyamus muticus (Egyptian Henbane) - F. F. Abdel-Motaal; M. S. M. Nassar; S. A. El-Zayat; M. A. El-Sayed; S. Ito (Folia Microbiologica, 2009)

Pheromone Disruption of Argentine Ant Trail Integrity - D. M. Suckling; R. W. Peck; L. M. Manning; L. D. Stringer; J. Cappadonna; A. M. El-Sayed (Journal of Chemical Ecology, 2008)

Fructose-amino acid conjugate and other constituents from Cyperus rotundus L. - Hanaa M. Sayed; Mahmoud H. Mohamed; Salwa F. Farag; Gamal A. Mohamed; Olanrewaju R.M. Omobuwajo; Peter Proksch (Natural Product Research, 2008)

Cytotoxic and genotoxic potentials of newly synthesized antiviral aminopyrazoloquinoline derivatives - Jamal M. Arif; Mohammed Kunhi; Manogaran P. Subramanian; Adnan A. Bekhit; Ola A. El-Sayed; Khalid Al-Hussein; Hassan Y. Aboul-Enein; Fahad M. Al-Khodairy (Medicinal Chemistry Research, 2008)

Can Ménage-À-Trois be Used for Controlling Insects? - D. M. Suckling; E. B. Jang; L. A. Carvalho; J. T. Nagata; E. L. Schneider; A. M. El-Sayed (Journal of Chemical Ecology, 2007)

Follicular dendritic cells stimulated by collagen type I develop dendrites and networks in vitro - M. E. El Shikh; R. M. El Sayed; J. G. Tew; A. K. Szakal (Cell and Tissue Research, 2007)

A new steroid glycoside and furochromones from Cyperus rotundus L. - Hanaa M. Sayed; Mahmoud H. Mohamed; Salwa F. Farag; Gamal A. Mohamed; Peter proksch (Natural Product Research, 2007)

Antiproliferative potential of sarcophine and its semisynthetic sulfur-containing derivatives against human mammary carcinoma cell lines - Jamal M. Arif; Swapnali S. Sawant; Khalid A. El Sayed; Muhammad Kunhi; Manogaran P. Subramanian; Yunus M. Siddiqui; Diaa T. A. Youssef; Khalid Al-Hussain; Mohammed N. Al-Ahdal; Fahad Al-Khodairy (Journal of Natural Medicines, 2007)

Identification of Sex Pheromone Components of a New Zealand Geometrid Moth, the Common Forest Looper Pseudocoremia suavis, Reveals a Possible Species Complex - A. R. Gibb; D. Comeskey; L. Berndt; E. G. Brockerhoff; A. M. El-Sayed; H. Jactel; D. M. Suckling (Journal of Chemical Ecology, 2006)

Synthesis and evaluation of 2,6-piperidinedione derivatives as potentially novel compounds with analgesic and other CNS activities - S. A. El Batran; A. E. N. Osman; M. M. Ismail; A. M. El Sayed (Inflammopharmacology, 2006)

Transcriptional profiling of the hyperthermophilic methanarchaeon Methanococcus jannaschii in response to lethal heat and non‐lethal cold shock - Boonchai B. Boonyaratanakornkit; Anjana J. Simpson; Timothy A. Whitehead; Claire M. Fraser; Najib M. A. El‐Sayed; Douglas S. Clark (Environmental Microbiology, 2005)
Summary Temperature shock of the hyperthermophilic methanarchaeon Methanococcus jannaschii from its optimal growth temperature of 85°C to 65°C and 95°C resulted in different transcriptional responses characteristic of both the direction of shock (heat or cold shock) and whether the shock was lethal. Specific outcomes of lethal heat shock to 95°C included upregulation of genes encoding chaperones, and downregulation of genes encoding subunits of the H + transporting ATP synthase. A gene encoding an α subunit of a putative prefoldin was also upregulated, which may comprise a novel element in the protein processing pathway in M. jannaschii . Very different responses were observed upon cold shock to 65°C. These included upregulation of a gene encoding an RNA helicase and other genes involved in transcription and translation, and upregulation of genes coding for proteases and transport proteins. Also upregulated was a gene that codes for an 18 kDa FKBP‐type PPIase, which may facilitate protein folding at low temperatures. Transcriptional profiling also revealed several hypothetical proteins that respond to temperature stress conditions.

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Optimization of Pheromone Lure and Trap Characteristics for Currant Clearwing, Synanthedon tipuliformis - D. M. Suckling; A. R. Gibb; G. M. Burnip; C. Snelling; J. De Ruiter; G. Langford; A. M. El-Sayed (Journal of Chemical Ecology, 2005)

Relative Attractiveness of (10E)-Dodecen-1-yl Acetate and (4E,10E)-Dodecadien-1-yl Acetate to Male Spotted Tentiform Leafminers Phyllonorycter blancardella (F.) - A. M. El-Sayed; L. I. Wainman; E. M. Santangelo; C. R. Unelius; R. M. Trimble (Journal of Chemical Ecology, 2004)

ROLE OF INTERMEDIARY BIOMARKERS IN DETERMINING THE ANTICANCER EFFICACY OF MARINE COMPOUNDS - Jamal M. Arif; Mohammed Kunhi; Yunus M. Siddiqui; Khalid A. El Sayed; Khaled Y. Orabi; Amal Al-Hazzani; Mohammed N. Al-Ahdal; Fahad M. Al-Khodairy (Medicinal Chemistry Research, 2004)

Seismicity and Seismic Hazard in Alexandria (Egypt) and its Surroundings - A. El-Sayed; I. Korrat; H. M. Hussein (Pure and Applied Geophysics, 2004)

Measurements of 210Pb Concentrations in Airborne in Kuwait - A. M. Sayed; D. Al-Azmi; N. A. Khuraibet (Environmental Monitoring and Assessment, 2002)

Inhibitory Effect of Monoterpenes on Response of Pityogenes bidentatus to Aggregation Pheromone Released by Piezoelectric Sprayer for Precision Release of Semiochemicals - Ashraf M. El-Sayed; John A. Byers (Journal of Chemical Ecology, 2000)

An alkalophilic thermostable lipase produced by a new isolate of Bacillus alcalophilus - Essam H. Ghanem; Hashim A. Al-Sayed; Kareema M. Saleh (World Journal of Microbiology and Biotechnology, 2000)

Purification and characterization of two chitinases from Streptomyces albovinaceus S-22 - El-S.A. El-Sayed; S.M. Ezzat; M.F. Ghaly; M. Mansour; M.A. E1-Bohey (World Journal of Microbiology and Biotechnology, 2000)

Effect of temperature and soil moisture on the survival and symbiotic effectiveness of Frankia spp. - W. F. Sayed; C. T. Wheeler; H. H. Zahran; A. A. M. Shoreit (Biology and Fertility of Soils, 1997)

Bioenergetic consequences of glucoamylase production in carbon-limited chemostat cultures ofAspergillus niger - M. Metwally; M. el Sayed; M. Osman; P. P. F. Hanegraaf; A. H. Stouthamer; H. W. van Verseveld (Antonie van Leeuwenhoek, 1991)